One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (EdTech Hub, 2025)
This case study explores One Teacher Thailand (OTT), a teacher-led learning network that supports holistic professional development rooted in the real needs of classrooms. Driven by a core team of volunteer teacher leaders, OTT integrates educational technology with broader concerns such as mental health, safety, and student engagement. The report examines the network’s evolution, identifies key factors behind its success, and offers recommendations to guide its continued growth and scaling across Thailand. Keywords: teacher networks; Thailand; peer learning; teacher leadership; teacher professional development A version of this report in Thai has been published by UNICEF and available by following the link to this provided with this record below. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Working Towards Education Success Using Data: A review of Ghana's journey towards improved learning outcomes using data - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2024)
The sub-Saharan Africa region is trapped in a learning crisis with devastating implications for children. The Covid-19 pandemic further exacerbated the situation, with children losing an estimated equivalent of an additional year’s learning. Not addressing the regional learning crisis will have a detrimental impact on economic development and well-being and risks restricting future national and regional economic growth and productivity and fuelling social unrest. Education research has shown that good quality education system data, when judiciously used, can support improved learning outcomes among a host of other positive impacts on national education systems. This case study is the first in a series documenting the journey of Ghana’s Ministry of Education towards the effective use of data to guide its decision-making for policy and practice. Keywords: data for decision making; data governance; data management; Ghana; education data systems; evidence-based policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Case study: Building strong institutional capacity and expertise in data for decision-making through developing a unified data management system. - Ampofo, Rudolph; Simiyu, Genevieve; Ayinga, Ussif (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

EdTech in Timor-Leste: A Rapid Scan - Honda, Delanie; Thinley, Sangay; Thang, Sarah; Flam, Rebekka; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Timor-Leste. This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert at the Australian Council for Educational Research. Keywords: out-of-school children and youth; girls' education; Southeast Asia; learners with special education needs and disabilities; digital education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Distance learning in the context of COVID-19: the case of Rwanda - Ngabonzima, Ernest; Isimbi, Roberte; Mwali, Marie Merci; Pellini, Arnaldo (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

UNICEF Education COVID-19 case study: Malaysia – Empowering teachers to deliver blended learning after school reopening | UNICEF Evaluation - UNICEF (2020)
In Malaysia, schools were closed on 18 March 2020, disrupting learning for five million students. To keep children learning, the Ministry of Education launched an online teaching and learning platform nationwide. The national platform has kept 3 million children learning during school closures and will continue to play an important role after gradual school reopening starting 24 June 2020 as part of the country’s approach of blending face-to-face and online learning. A critical part of the platform is the Komuniti Guru Digital Learning or Teacher Digital Learning Community, established with support from UNICEF, that aims to equip teachers with the skills and knowledge required to deliver distance classes effectively and efficiently through a five-module online teacher training course that includes notes, video tutorials, and quizzes on how to plan, build and launch digital content for remote teaching and learning. To date, around 2,400 teachers from over 1,600 schools all over the country have participated in the online teacher training. Originally published OCHA Humanitarian Response and ReliefWeb

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

EdTech in Vietnam: A Rapid Scan - Honda, Delanie; Halla, Ken; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Vietnam. This report was originally written in March 2024. It is based primarily on desk research, with quality assurance provided by country experts at Southeast Asian Ministers of Education Organization (SEAMEO) centres. Keywords: out-of-school children and youth; digital education; Southeast Asia; girls’ education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

What Matters Most for Teacher Deployment? A case study of teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman; Bernard-Jones, Lydia; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

China: testing a decade of online education preparation - Liangdi, Xu; Groenewegen-Lau, Jeroen (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Jordan’s EdTech response to COVID-19 - Al-Hindawi, Hind; Hashem, Lina (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Teacher reflections and praxis: a case study of Indian teachers of English as a foreign language - Makarani, Sakilahmed A. R. (University of Hawai'i at Mānoa, 2012)
This case study engaged Gujarati English as Foreign Language (EFL) teachers in video-based reflection with the goal of increasing their reflective abilities and uncovering their understandings about reflective teaching practices in the Indian pedagogical and cultural context. The study aimed to explore, and gain a deeper understanding of how structural, institutional, and social dynamics of the larger socio-political cultural context of India affected the classroom teachers' thinking and their teaching practices. It was hoped that not only would the Gujarati teachers demonstrate an ability to reflect on their practice, but that they would also engage in a critical examination of the factors that impacted their context. The computer-based qualitative data analysis software, Atlas.ti, was used to analyze data using a grounded theoretical approach. The findings indicated that participants successfully engaged in reflection about their teaching using video as the tool for their professional development. Initially teacher participants had mixed feelings about recording and watching videos of their classroom instruction; however, teacher participants later enjoyed the experience, explicitly stating that such reflection helped them. The study also revealed that teacher participants perceived parental, social, institutional, and economic factors as influences on their students' learning, however these were simply identified as problems or conditions without any type of deeper critical analysis. Further, it was found that the teachers did not reach a critical level of reflection, nor did they consider taking action to address fundamental contextual issues. While this study showed that teacher reflection using digital video recordings of classroom practice can be a productive approach to meaningful teacher reflection in India, the study also demonstrated that teachers need specific exposure to deeper critical pedagogical thinking to go beyond simply identifying or blaming the social or economic issues embedded in their context. The study concludes with recommendations on how to reach critical teacher reflection. It is hoped that this case study will add to the growing body of research literature related to teacher self-reflection as a means to improving teaching practice and preparing teachers to take on social challenges in the Indian context. [The dissertation citations contained here are published with the permission of ProQuest LLC. Further reproduction is prohibited without permission. Copies of dissertations may be obtained by Telephone (800) 1-800-521-0600. Web page: http://www.proquest.com/en-US/products/dissertations/individuals.shtml.]
Keywords: Case Studies; Computer Software; Cultural Context; ERIC, Resources in Education (RIE); Economic Factors; English (Second Language); Foreign Countries; Grounded Theory; India; Indians; Language Teachers; Qualitative Research; Reflective Teaching; Second Language Instruction; Second Language Learning; Social Influences; Teacher Attitudes; Teaching Methods; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096525; __finaldtb

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

The effectiveness of integrating interactive technology in reading comprehension: A case study of Jamaica's grade school - Iyare, Ngozi F.; James, Julia; Amonde, Tom M. (Journal of Information Technology Education: Research, 2018)
Aim/Purpose: There is growing number of countries embarking on large-scale, government-supported initiatives (e.g., Antigua & Barbuda, Australia, Brazil, India, Iran, Jamaica, Kazakhstan, Pakistan, Russia, Turkey, and the United Arab Emirates) to distribute tablet devices to students in the K-12 schooling sector. The review of the government-supported initiatives concluded that the majority of these initiatives have been driven not by educational frameworks or research-based evidence but by the tablet hype. The goal of this study is to provide research-based evidence by investigating if the learning experience for grade-three learners with interactive technology improves knowledge and skills in reading comprehension compared to learning in the traditional chalk and talk environment. Background: Prior studies provided limited evidence based mainly on data from developed countries about the influence of the use of interactive technology on reading comprehension at lower grade school level. Methodology: Employing a mixed-method case study research approach, this study aims to investigate the effects of integrating interactive technology in reading comprehension and examine the perspectives of students. This case study employed a sample of 30 public school third-grade students located in a relatively poor residential area in St Catherine, Jamaica as well as the two classroom teachers. Thirty students were divided into two groups -- an experimental group, which included 16 participants and a control group, which included 14 participants. The intervention program was carried out over a period of eight weeks. Contribution: This study has provided (a) additional data to show evidence for the effectiveness of interactive technology in reading comprehension and (b)research based evidence for the distribution of computer devices to students in the K-12 schooling sectors. Findings: We found empirical support for the positive effects of technology-based approaches for addressing reading comprehension and vocabulary skills. Our results were based on the pre-test and post-test assessments. Additional data was collected using a survey questionnaire which was given to the students before and after the intervention. The change from pretest to posttest was significantly different between the two groups as measured by the Mann Whitney U test. Recommendations for Practitioners: The empirical support for the effects of technology-based approaches for addressing reading comprehension and vocabulary skills identified in this study will assist teachers with strategies and programs that should improve students' motivation as well as their grades. Recommendation for Researchers: For future studies, we recommend focusing on a longer intervention period and using a larger sample size that would likely yield more definitive and generalizable results.
Keywords: Case Studies; Control Groups; Conventional Instruction; ERIC, Current Index to Journals in Education (CIJE); Elementary Education; Elementary School Students; Experimental Groups; Foreign Countries; Grade 3; Instructional Effectiveness; Jamaica; Mastery Learning; Outcomes of Education; Reading Comprehension; Reading Improvement; Reading Instruction; Teaching Methods; Technology Integration

EdTech in Malawi: A Rapid Scan - Rui, Yang (Tingting) (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but not exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Malawi. Keywords: Malawi, EdTech, Policy, ICT An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

The Impact of ICT as Another Route to Overcome Learning Barriers for Students with SEN: A Case Study in an Egyptian Context - Al-Gawhary, Wedad; Kambouri, Maria (International Association for the Development of the Information Society, 2012)
The purpose of this case study was to measure the impact of using ICT in Individual Learning Programmes of students with learning disabilities. Twenty five students and thirteen teachers took part in the research which was based on classroom observations. The Kappa coefficient was employed as a measure to statistically quantify the students' acquisition and progress in learning computer and literacy skills through raters' observations. A high correlation between Keyboard, PowerPoint, and literacy skills (writing, reading, and maths) was revealed suggesting the significance and impact of keyboard training as an essential component towards achieving educational objectives. Moreover, thematic analysis of the teachers' interviews provided a further dimension for understanding factors influencing the ICT integration process. These results further confirmed the positive impact of computer skills training on the students' learning experience which also revealed a strong belief in the right of every child to all learning opportunities, particularly ICT regardless of his/her abilities.(Contains 2 tables.) [For the complete proceedings, "Proceedings of the International Association for Development of the Information Society (IADIS) International Conference on Cognition and Exploratory Learning in Digital Age (CELDA) (Madrid, Spain, October 19-21, 2012)," see ED542606.]
Keywords: Autism; Barriers; Case Studies; Cerebral Palsy; Communications; Computer Literacy; Computer Mediated Communication; Computer Software; Down Syndrome; Foreign Countries; Heterogeneous Grouping; Information Technology; Interrater Reliability; Mixed Methods Research; Semi Structured Interviews; Semitic Languages; Special Needs Students

A case study of using an online community of practice for teachers' professional development at a secondary school in China - Wang, Qiyun; Lu, Zhiping (Learning, Media and Technology, 2012)
In this case study, an online community was designed at a secondary school in China for the teachers to prepare their lessons collectively, reflect on their teaching practices, collect comments from peers, and share resources. A survey was administered to the teachers to investigate their perceptions on the online community for their professional development. Two hundred and eighty-three teachers responded to the survey and eight teachers were further interviewed by email. The result showed that most teachers liked using the online community as they could gain subject knowledge and could obtain support from peers, share experiences and get feedback, and exchange resources. Also, online entries confirmed that transformational changes in teaching pedagogy and students' learning activities occurred along the time. However, certain teachers did not participate in the online community frequently. This paper describes the context of the case study, design dimensions of the online community, teachers' positive perceptions on using the online community, and transformational changes. Also, strategies for promoting effective use of the online community are discussed and follow-up studies to address the challenges involved in this study are proposed. [PUBLICATION ABSTRACT]
Keywords: Case Studies; China; Communities of Practice; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Education--Teaching Methods And Curriculum; Educational Practices; Electronic Learning; Electronic Mail; Foreign Countries; Interviews; Learning; Lesson Plans; Mail Surveys; Online instruction; Participant Satisfaction; Pedagogy; Polls & surveys; Professional Development; Professional development; Secondary Education; Secondary School Teachers; Secondary school teachers; Teacher Surveys; Teaching Methods; Technology Uses in Education; Transformative Learning; __:import:01; __:match:final; __:matched; __:study_id:2096477; __finaldtb; community of practice; lesson planning; professional development; reflection; technology

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Mapping EdTech interventions within the Ministry of Education of Ghana. Preliminary Data - Ampofo, Rudolph; Korboe, David; Radford, Kate; Mazari, Haani (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Bringing Digital Learning to Rural Schools: A Rapid Evaluation of Lyra in Africa - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech in Lao People's Democratic Republic: A Rapid Scan - Afzal, Nimra; Thang, Sarah; Tulivuori, Jukka; Thinley, Sangay; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive. Nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, and in this case, Lao People’s Democratic Republic (PDR). This report was originally written in February 2024. It is based primarily on desk research, with quality assurance provided by a country expert based at the Australian Council for Educational Research. Keywords: Ministry of Education and Sports; digital skills; training programmes; government expenditure; learning outcomes; disparities An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

EdTech in Cambodia: A Rapid Scan - Thinley, Sangay; Hayat, Amal; Thang, Sarah; Mazari, Haani (EdTech Hub, 2024)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These include policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Cambodia. This report was originally written in January 2024. It is based primarily on desk research, with quality assurance provided by a country expert — an Education Specialist with the UNICEF Cambodia office. Keywords: out-of-school populations; girls and gender; Southeast Asia; learners with special educational needs and disabilities; primary education; secondary education An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Resilient by Design: Ukraine’s EdTech Response during Wartime - Bhatt, Margi (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _comingsoon; _r:AddedByMyEducationEvidence

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Understanding language teachers' practice with educational technology: A case from China - Li, Li (System, 2014)
This article explores how eight secondary school teachers integrated educational technology into English language teaching in Beijing, China and considers their views of the factors influencing technology use. Analysing data from classroom recordings and follow-up interviews, this study revealed that PowerPoint was the most frequently used technological application in the classroom, while the internet and other technological tools were also used by the teachers. They employed educational technology for different pedagogical purposes, including addressing professional needs in improving teaching, designing materials and conducting professional development. Teachers also claimed that they used technology to address learners' needs, such as improving engagement, enhancing language acquisition, facilitating understanding and establishing a context for language use. The study identified four important factors in influencing teachers' use of technology, including sociocultural contexts, teachers' beliefs, access to resources, and technology competence and confidence. This study suggests that a critical reflective approach is useful in assisting teachers to understand their needs and pedagogical beliefs concerning technology use. Ongoing professional development is also valuable in promoting teachers' technology competence and confidence, thereby improving the use of technology in their teaching.
Keywords: Case study; China; Socio-cultural context; Teachers' perceptions; Technology use

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Teachers’ Learning Communities for Developing High Order Thinking Skills—A Case Study of a School Pedagogical Change - Miedijensky, Shirley; Sasson, Irit; Yehuda, Itamar (Interchange (Toronto. 1984), 2021)
This study deals with an elementary school that is undergoing a process of pedagogical change. The teachers understood that their weak point was excessive use of teaching based on memorization rather than developing high-order thinking (HOT) skills. The school therefore established teachers’ learning communities for peer learning and designing learning tasks that encourage the development of HOT skills. Quantitative and qualitative research tools were used in this study as a formative assessment. The data included learning tasks and interviews with teachers. The findings indicate an increase in the expression of critical thinking and the cognitive levels of application, analysis, and synthesis. The national test scores indicate an increase in students’ performance in most subjects. It appears that educators recognize the need for a transition from teaching that emphasize memorizing information to methods that develop students’ thinking skills and independent learning and initiated a successful pedagogical change.
Keywords: Case studies; Collaboration; Critical thinking; Education; Educational Philosophy; Educational Policy and Politics; Elementary schools; Formative assessment; High-order thinking; Learning; Memorization; Pedagogical change; Pedagogy; Peer learning; Qualitative research; Teachers; Teachers’ learning communities; Teaching; Teaching methods; Test scores; Thinking skills

Professional Development on Digital Literacy and Transformative Teaching in a Low‐Income Country: A Case Study of Rural Kenya - Kerkhoff, Shea N.; Makubuya, Timothy (Reading research quarterly, 2022)
In recent years, the government of Kenya has implemented programs with the hope of moving the country to middle‐income status. The government has implemented the Digital Literacy Programme, distributing tablets to schools across the country, and also a new curriculum, promoting innovative teaching that includes digital literacy, learner‐centered teaching, and relevance to students’ lives. Our purpose in this research was to explore culturally sustaining teaching methods in line with the Kenyan government’s push for innovative teaching and digital literacy attainment for all students. We used case study methods to describe Kenyan teachers’ perceptions of innovative teaching and digital literacy while participating in the Inquiry Initiative, a three‐day professional development series. Participants included preschool, primary, and secondary teachers from Trans Nzoia County. Data sources were pre‐ and post‐surveys, participant‐generated artifacts, and interviews. Our participants perceived the following needs: new literacies for learners, creativity for learners, collaboration and group work, and creativity to overcome technological challenges. Overall, participants embraced learner‐centered teaching theoretically but found that the lack of technological resources created barriers to teaching digital literacy in a learner‐centered fashion. We found that teachers reported mostly using technology for teaching preparation and record keeping rather than engaging students in digital literacy practices. To solve technological challenges, teachers described having students work in groups and using smartphones. Future research could share more creative solutions to technical challenges in low‐income countries.
Keywords: 1‐Early childhood; 2‐Childhood; 3‐Early adolescence; 4‐Adolescence; 6‐Adult; Case Studies; Collaboration; Collaborative Learning; Computer literacy; Constructivism; Creative ability; Creativity; Critical Pedagogy; Culturally Responsive Pedagogy; Digital Literacies; Digital literacy; Digital/media literacy; Education & Educational Research; Educational technology; Gloablization and Literacy; Group work in education; Information literacy; Instructional strategies; methods and materials; Kenya; Literacies; Literacy; Literacy programs; Policy; Postcolonialism; Professional Development; Psychology; Psychology, Educational; Qualitative Research; Social Constructivism; Social Sciences; Socio‐cultural; Students; Study and teaching; Survey Research; Teacher attitudes; Teacher education; Teacher education; professional development; Teachers; Teaching; Teaching methods; Team learning approach in education; Transformative

School-based professional development in a developing context: Lessons learnt from a case study in Zambia - Haßler, Björn; Hennessy, S.; Cross, A. (Professional Development in Education, 2014)
This paper reports on the development and outcomes of the second phase of OER4Schools, a school-based professional development programme supporting interactive forms of subject teaching in conjunction with Open Educational Resources (OER) and technology in Zambian primary schools. We worked with partners to identify the needs of school-based continuing professional development adapted to the local context; the programme was based on participatory, collaborative and inquiry-based pedagogies for both classroom learning and teacher development. We worked over a one-year period with four experienced teachers in two basic (primary) schools serving disadvantaged communities. Data were collected from observations, interviews, surveys, lesson planning/review meetings and team workshops. All participants integrated OER and technology into mathematics and science lessons and developed more interactive practices, including collaborative learning. Professional dialogue, quality conversations, reflective practice, cultural sensitivity, peer learning and cooperation were pivotal mechanisms through which teachers shifted their focus from teaching (and teacher exposition) to student learning. Seeing students as capable individuals, teachers raised their expectations and developed insight into interactive practices such as group work, providing meaningful opportunities for student collaboration and active learning by all.
Keywords: Author:Haßler; Open Educational Resources; Zambia; digital technology; dode_eth-src-dode; dode_eth-trf2-dode; interactive pedagogy; reflective practice; school-based professional development; sub-Saharan Africa

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.

A case study of blended e-learning in Thailand - Wongwuttiwat, Jittima; Buraphadeja, Vasa; Tantontrakul, Tanakom (Interactive Technology and Smart Education, 2020)
Purpose This case study aims to analyze and compare the learning achievements of two groups of university students taught by: traditional face-to-face learning (TDL) and blended e-learning (BEL). To the best of the authors’ knowledge no previous study of the use of BEL in the context of Thailand has addressed the same purpose as this study. It is expected that the findings from this study will suggest areas for additional research and will be of interest to researchers and professional educators, especially those involved in the development and use of BEL systems. Design/methodology/approach This case study compares two groups of undergraduate students who completed a course designed to develop skills in using productivity software at a university in Thailand. After establishing the groups, one group learned in a BEL environment and the other in a TDL environment. In particular, the online training and assessment software application SIMnet was used in the BEL environment. Comparisons between results using BEL and TDL are made for different assessment results. Additional analyses of results for the BEL group examined gender differences and correlations between the number of attempts made on assessments and the levels of achievement. Findings The findings indicated that for all of the assessments, the BEL group had a better performance than the TDL group. For the BEL group, additional analyses found no significant differences between the achievements of males and females and significant correlations between the numbers of attempts made on assessments and the results. Limitations of this case study are discussed, and the findings are expected to be of interest to researchers and professional educators, especially those involved in the development and use of BEL. Research limitations/implications Learning content was restricted to the Excel spreadsheet in which different areas of content need to be studied. The software SIMnet was used by the BEL group, additional BEL software needs to be studied. The participants’ characteristics – age, gender, culture and computer competency – were narrow scoped in which the study could include more varieties and also a larger sample size. Further studies should be designed to include more comparisons such a comparison between TDL group males and females. Originality/value The findings from this limited case study suggest that a BEL learning environment is superior to a TDL environment. Also, a BEL environment is equally beneficial for male and female students. In particular, the BEL feature, which allows students to retake assessments, leads to improved learning performance equally for both males and females. In general, these findings support those reported in previous studies.
Keywords: ⛔ No INSPIRE recid found

Brazil Case Study - Mello, Ursula; Loureiro, Andre; Cruz, Louisee (World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.
Keywords: Education; Education Equity; Education Finance; Education Outcomes; Education Spending; Fiscal Decentralization; Fiscal Transfers; Public Expenditure

Digital storytelling and reflection in higher education: a case of pre-service student teachers and their lecturers at a university of technology - Ivala, Eunice; Gachago, Daniela; Condy, Janet; Chigona, Agnes (Journal of Education and Training Studies, 2014)
Employers in South Africa are calling for students graduating from higher education institutions (HEIs) to exhibit the capacity for reflection. However, many tertiary institutions fall short in allowing opportunities for reflection. As a result, HEIs are grappling to find ways of fostering reflection amongst their students. This paper argues that digital storytelling if implemented properly is one of the ways which can be used to help HEIs in this accomplishment. It documents results of production of digital stories by 29 final-year pre-service student teachers at the Cape Peninsula University of Technology (CPUT), South Africa, as part of their assessment in their professional development course. The study was informed by structuration theory and levels of reflection and cognitive processing to help the researchers understand the potential of digital storytelling in enhancing reflection. Qualitative methods of collecting data were utilized. Focus group interviews were conducted with the students and their facilitators to elicit whether production of digital stories led to reflection. Findings showed that the production of digital stories promoted the three levels of reflection and thus deep learning and higher-order thinking skills.
Keywords: Case Studies; Cognitive Processes; College Faculty; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Focus Groups; Foreign Countries; Higher Education; Personal Narratives; Postsecondary Education; Preservice Teachers; Professional Development; Qualitative Research; Reflection; Skill Development; South Africa; Story Telling; Teaching Methods; Technology Uses in Education; Video Technology; __:import:02; __:match:final; __:matched; __:study_id:2096367; __finaldtb

Policy adoption of learner-centred pedagogy in Rwanda: A case study of its rationale and transfer mechanisms - van de Kuilen, Hester S.; Altinyelken, Hulya Kosar; Voogt, Joke M.; Nzabalirwa, Wenceslas (International Journal of Educational Development, 2019)
This study explores why and how learner-centred pedagogy (LCP) as a policy has been adopted in Rwanda, despite ample evidence of the failure of LCP in developing countries. The case of Rwanda, as a late adopter, shows that at this stage of pedagogy diffusion the influence of global mechanisms and actors has been amplified. This study draws upon interviews with key stakeholders and relevant documents during the 2011–2016 period. The transfer process is examined by analysing the rationale offered and mechanisms deployed by the Rwandan government and aid agencies.
Keywords: Competence-based education; Curriculum reform; Education policy transfer; Learner-centred pedagogy; Policy adoption; Rwanda

EdTech in Rwanda: A Rapid Scan - Kimenyi, Eric; Chuang, Rachel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Rwanda. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert
Keywords: C:Rwanda; F: Country scan; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Low-connectivity Educational Technology: A Case Study of Supporting Learning during Covid-19 via SMS with ‘Keep Kenya Learning’ - Jordan, Katy; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (Journal of Learning for Development, 2024)
The use of Short Messaging Service (SMS) for education has grown in recent years, drawing particular attention to supporting school-level learners, due to the Covid-19 pandemic. This renewed interest has prompted questions about how this form of educational technology could be used in the longer term. However, despite being used in many Covid-19 responses, there are few documented examples of innovative applications in this field during the pandemic, which represents a gap in the literature. As a medium for education, SMS offers potential benefits such as being cost-effective and having positive impacts on learning. In this paper, we present a case study of an educational programme rapidly implemented during the pandemic as part of the ‘Keep Kenya Learning’ program, to support learners remotely in terms of literacy, numeracy, and social and emotional learning topics. Through the case study, we describe the innovative process used to rapidly develop content for SMS, and draw upon usage statistics, quiz scores and user feedback to gain insights into its implementation with learners and caregivers in Kenya. The case study demonstrated that educational television content can be effectively adapted to mobile delivery. Furthermore, we present practical reflections on the development and implementation of SMS educational technology which will help inform future initiatives. These include considering timing in relation to school terms when planning a supporting intervention, and designing content in a modular way to allow flexibility for learners in navigating through courses.

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Distance learning for Indonesian mathematics students with hearing impairments in pandemic situation: A case study - Rahmawati, Fadhilah; Pamungkas, Megita Dwi; Chasanah, Aprilia Nurul; Wicaksono, Arief Budi; Franita, Yesi; Hendrastuti, Zuida Ratih (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to identify the distance learning process of deaf students during the pandemic. This research is qualitative research with a case study approach. The subjects of this study were mathematics teachers, deaf students, and stakeholders. The research was carried out at the SLBN Kota Magelang and SLB-B YPPALB Magelang . Data collection techniques in this study were carried out by questionnaires, interviews, and document studies. The main instrument in this study was the researcher, while the auxiliary instruments were questionnaires and interview guidelines. The validity used in this research is source triangulation. The results showed that the mathematics distance learning process for deaf students could be implemented in various ways and could be adapted to school conditions and student conditions. Distance learning can be done with the help of media in hand-out modules taken at school before the mathematics learning schedule is implemented. In addition, the distance learning process on the mathematics topic of deaf students can also be carried out through learning videos with additional translated texts. Deaf students can simultaneously watch videos and read explanations from math teachers.
Keywords: Learning process; deaf; distance learning

Using Tactile Letters As An Assistive Technology In Teaching Alphabet For Dyslexic Children: A Case Study - Mohamed, Mariam; Tan, Abdullah (13th International Scientific Conference "eLearning and Software for Education", 2017)
Dyslexia is a specific learning disability characterized by difficulties with accurate and/or fluent word recognition, poor spelling and poor decoding abilities. Dyslexic children are having language learning disorder and makes them difficult mastering the skill to read, spell and write. This research explores the design from tactile letters to mobile application that support alphabet recognition and early reading acquisition in children, particularly dyslexic children. The research design of this study is qualitative based on case study methodology. The approach of tactile letters and mobile application which could foster learning and help dyslexic children to improve some of their fundamental skills, such as recognizing alphabet and pronunciation. This study describes the design and evaluation of an assistive technology based in lieu of teaching alphabet for dyslexic children. The combination of tactile letters and mobile application may be the ground-breaking of stimulating and interactive experience for children that could encourage the learning process.

Teachers’ perspectives on their use of ICT in teaching and learning: A case study - Kafyulilo, Ayoub; Keengwe, Jared (Education and information technologies, 2014)
This article presents the perspectives of science and mathematics teachers on their use of information and communication technology (ICT) in teaching and learning in Tanzania. The findings show that few teachers used computers for teaching and learning purposes while majority of them used computers for administrative purposes. Additionally, teachers were found to have limited confidence in using technology to facilitate specific concepts or skills, to support creativity, and to support students to learn complex concepts. Therefore, it is suggested that schools explore strategies ICT integration strategies that focus more on making a shift from teaching technology or using technology for administrative purpose to appropriate pedagogical uses that could enhance student learning.
Keywords: Case studies; Communication; Computer Appl. in Social and Behavioral Sciences; Computer Science; Computers and Education; Education; Educational Technology; Information Systems Applications (incl.Internet); Information technology; Learning; Learning strategies; Mathematics; Pedagogy; Science; Student Learning; Study and teaching; Teacher attitudes; Teachers; Teaching; Technology Integration; Technology application; Training; User Interfaces and Human Computer Interaction

Female Teachers' Perceptions of Quality Education for Adolescent Girls in Rural Bangladesh: A Case Study - Rahim, N (2017)
The education of adolescent girls in Bangladesh must be pursued with the right combination of technology, practicality, and cultural sensitivity to achieve, among other objectives, the objectives of Millennium Development Goals (MDGs). The problem this study address is despite the availability of mobile-based curricula, such as video, mobile phones, and Short Message System (SMS) technology, female teachers in rural areas are not trained to plan and deliver curricula using mobile platforms. The purpose of this qualitative single case study is to explore barriers associated with female teachers’ training of the use of mobile-based technology in rural areas in Bangladesh. The sample is, randomly selected a minimum of eight local female teachers who had been teaching at least for two years in a rural school in Bangladesh. The data were collected to determine the local teachers’ perception on establishing quality education through virtual (email, mobile phone, IMO, zoom or Skype) interviews administered to these 8 local female teachers. The researcher gathered data from the local female teachers’ point of view based on their motivation to receive training in becoming proficient in English and the use of mobile technology in teaching. A content analysis tool was used for analyzing, interpreting, coding, and categorizing textual data where themes identified based on a comprehensive classification system. The findings from the data analysis would aid schools in recruiting, training, and retaining local female teachers to provide quality education to the adolescent girls. The data from the single case study provided information as to the use of mobile and web technologies in teaching and learning while local female teachers gain proficiency in the English language. The insight gained from this single case study may help develop future technology budgets, infrastructure, and curriculum needs. The findings from research revealed that the rural Bangladeshi school teachers noted that there is limited use of videos in the classrooms for teaching due to, in some parts, the lack of training by school administrators on strategies to use videos in their teaching. Some barriers to the use of videos is due to the lack of Internet connection, the lack of knowledge on the proper use of videos in their teaching, and the lack of administrators’ support for this type of curriculum change in the schools.

EdTech in Tanzania: A Rapid Scan - Groeneveld, Caspar; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private-sector partnerships, and the digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, Tanzania. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Tanzania; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Parental Roles in Provision of Mobility and Educational Resources for Children with Physical Challenges a Case of Joytown Special School, Kiambu County, Kenya - Kamau, Joyce (Journal of Education and Practice, 2017)
Children with physical challenges have developmental needs and rights like other children and due to their exceptionality they call for more attention in provision of adequate quality mobility and educational resources to enhance their holistic development. However, it is apparent that provision of resources to children with physical challenges has not been possible in Kenya due to various factors which are not yet understood. The study drive was to explore parental role in the provision of mobility and educational resources to children who are physically challenged. The study sought to establish parents' involvement in provision of mobility and educational resources. The study was carried out in Joytown Primary School for the Physically Challenged in Thika Town. The school was purposefully selected because it is best suited for the study since it caters for children in the category of special needs being addressed in the study that is physical challenges. Case study design was used. Target population of the study was 100 children with physical challenges, 200 parents and 4 teachers and the head teacher. Stratified random sampling method was employed to arrive at a Sample size of 30 children with physical challenges, purposive and opportunity sampling to arrive at 30 parents and purposive sampling to arrive at 4 teachers. Therefore, the total sample size was 64. The data were collected using various techniques which included questionnaires for the teachers, interview guides for parents and observation guides for children. Collected data were analyzed using both quantitative and qualitative methods. Quantitative methods entailed use of descriptive statistics such as frequencies and percentages which enhanced discussion of qualitative data which was organized into themes and categories and presented in discussion form. The study established that parental involvement in provision of mobility and educational resources is minimal. The main recommendation of the study is that government should have a budgetary allocation meant specifically for purchase of mobility and educational resources and maintenance of facilities since it's a noble course which would ensure that children are actively involved in learning activities therefore enhancing holistic development hence molding children with physical challenges to become self-reliant and productive citizens.
Keywords: Assistive Technology; Case Studies; Child Development; Educational Resources; Elementary School Students; Elementary School Teachers; Foreign Countries; Interviews; Observation; Parent Participation; Parent Role; Physical Disabilities; Physical Mobility; Questionnaires; Resource Allocation; Special Schools; Statistical Analysis; ⛔ No DOI found

ICT integration in teaching and learning activities in higher education: a case study of Nepal's teacher education - Rana, Kesh; Rana, Karna (Malaysian Online Journal of Educational Technology, 2020)
This article reports an examination of information and communication technology (ICT) integration in teaching and learning activities in higher education in Nepal. ICT education policy by the government of Nepal emphasises the need to develop teachers' ICT competencies and suggests the use of ICT will transform traditional models of teaching to ones that are student-centred. The case study reported the lack of clear strategy to implement the ICT education policy and to fund for the ICT infrastructure and professional development of university staff to integrate ICT in teacher education. In this case, the Faculty of Education in the university, where there is no funding from the government and university for the ICT in education project, received funding from an international organisation to install ICT infrastructure and provide ICT training for teachers and other staff. It is argued that, to realise the policy in practice, more sustainable mechanisms need to be developed to provide ICT facilities for teachers and to train them how to use ICT in teaching activities.
Keywords: ERIC, Current Index to Journals in Education (CIJE); Educational Policy; Foreign Countries; Higher Education; Information Technology; Nepal; Postsecondary Education; Preservice Teacher Education; Program Implementation; Sustainability; Technology Integration; __:import:01; __:match:final; __:matched; __:study_id:2095751; __finaldtb

Performance Oriented Information and Communication Technology (ICT): Model for Education Purpose in Pakistan. A Bahawalpur District Case Study - Qadri, Salman; Shah, Rehan Ali; ul Rehman, Muzammil; Ullah, Saleem; Shah, Ali Nawaz; Ali, Muhammad Zaman; Ahmed, Muhammad Munawer (International Journal of Computer Science and Network Security, 2017)
Information technology brought a dramatic change in our society. In third world countries such as Pakistan is also trying to get involve this technology in every field of life. In this decade, information technology is being used in several disciplines such as education, health, agriculture and business etc. It has given a positive impact on all of these disciplines especially E-banking, E-learning and E-commerce etc. This study focuses the implementation of information and communication technology (ICT) framework to boost the progress of different less develops areas in Pakistan. This study also describes the complete methodology with all of its benefits and constraints on implementation and also proposed a framework to improve the efficiency and accuracy in education department in primary to higher level in Bahawalpur district and its five sub districts (tehsil) and also take the case study of The Islamia University Bahawalpur within city sub campuses by utilizing the successful implementation of information and communication technology for the betterment of education.
Keywords: E-Classes; ICT Infrastructure; IT-Centers; Information and Communication Technology; integration; teachers; ⛔ No DOI found

EdTech in Pakistan: A Rapid Scan - Baloch, Imdad; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, Pakistan. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Pakistan; F: Country scan; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Blended learning implementation in secondary education for girls: case study Tatweer project Saudi Arabia - Bukhari, Eman Gasim (International Journal of Academic Research and Reflection, 2016)
Blended learning (BL) has been the subject of much research recently, and the present research adds to this growing body of knowledge as the first substantial study on BL in secondary education for girls in Saudi Arabia. Based on field work comprising interviews and questionnaires this research reports the results of an exploratory, empirical case study of a large-scale programme (Tatweer project) for the introduction of blended learning into 25 traditional secondary girls' schools in Saudi Arabia. Adopting the interpretive research paradigm the objective of the study is to gain rich insight into blended learning guided by the effect of BL on female education. The study demonstrates a number of positive effects of BL on students' engagement and self-development, however, problems with the workloads of students and the failure of teachers to integrate face-to-face learning with e-learning are also observed. Throughout the research Sharpe et al.'s (2006) 8-dimensional framework of BL is applied in a new way to assess the implementation level of BL. This results in the recommendation to extend this framework with an ethical dimension. Further recommendations of the work are to actively seek feedback from key stakeholder groups during BL implementation, to use BL for teacher training in BL, and to measure performance indicators like students' workloads during the transition of traditional schools to BL.
Keywords: ⛔ No DOI found

Integration of ICT in Education in a Secondary School in Kenya: A Case Study - Kisirkoi, Florence (Literacy Information and Computer Education Journal, 2015)
Amidst reports that there was very little integration of Communication Information Technology (ICT) in curriculum delivery in many secondary schools in Kenya, it was reported that one secondary school was using ICT in instruction and practicing learner centered instructional approaches and there was improved learning outcomes. The school’s mean score in the Kenya Certificate of Secondary Education had improved from 6.2 to 8.4 between 2007 and 2013. This study teacher computer literacy levels, motivation for integration, perceived reason for the intervention and the impact on teaching and learning. A case study was conducted and observation and interview schedules were used to collect data. The study population was the 535 students and the 28 teachers in the school. Simple random sampling was used to sample 30 students and 18 teachers. It was established that the students and teachers were computer literate and were able to manage computer applications for teaching and learning. The Learning process was found to be practical with learner interactions and activities based learning. The motivation was desire to teach better coupled with visionary, supportive school leadership. The school was using ICT as teaching learning tool and there was improvement of learning environment and outcomes. Many schools ought to emulate the school.

EdTech in Kenya: A Rapid Scan - Otieno, J.; Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private-sector partnerships, and the digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Kenya. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Kenya; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Inclusive education in an international school: A case study from Hong Kong - Chan, T.; Yuen, Mantak (International Journal of Special Education, 2015)
This case study provides an overview of current policy, practices and problems concerning inclusion in one international secondary school in Hong Kong. A total of 13 interviews were conducted with the school management team, teachers, students and parents, supplemented by 12 classroom observations and two ‘student-shadowing’ exercises. Findings suggest that the school has been reasonably successful in raising teachers’ awareness of inclusive education principles, creating a whole-school culture of inclusiveness, and forming a partnership with parents. However, the commitment of individual teachers to implementation of inclusive practices in their own classrooms varies. Some teachers are not adaptive enough in their teaching approach, and have difficulties differentiating instruction and learning activities. Improvements are also needed in the way that teachers work with their education assistants (classroom aides). Implications for improvement are discussed. © 2015, International Journal of Special Education. All rights reserved.

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Sierra Leone; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Jordan: A Rapid Scan - Khalayleh, A.; Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private-sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries, in this case, in Jordan. This report was originally written in June 2020. It is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Jordan; F: Country scan; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-src-eth; dode_eth-trf2-dode

Interrogating Gender Divides in Technology for Education and Development: the Case of the One Laptop per Child Project in Ghana - Steeves, Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
Keywords: C: Ghana

A case study of innovations that address constraints on the effectiveness of early-grade reading achievement - Comings, John P. (PROSPECTS, 2020)
The United States Agency for International Development, World Vision, and the Australian government established All Children Reading: A Grand Challenge for Development (ACR GCD) to address problems that prevent children from gaining foundational reading skills. ACR GCD mobilizes the private sector, academia, and nongovernmental organizations in problem-solving dialogues that support the development, testing, and promotion of new solutions to these problems. It also advances EdTech innovation and research to improve reading outcomes for marginalized children in low-resource contexts to effectively build bridges over system constraints in ways that lower the risk of pilot-testing and eventual large-scale replication. This case study describes some of ACR GCD’s funded innovations and its nontraditional approach to employing grant competitions (in which innovators propose solutions to broadly described problems) and prizes (in which innovators develop solutions to specifically identified problems). For innovations that have been evaluated, this article summarizes the findings on their impact on learning.

Emergency remote teaching and students’ academic performance in higher education during the COVID-19 pandemic: A case study - Iglesias-Pradas, Santiago; Hernández-García, Ángel; Chaparro-Peláez, Julián; Prieto, José Luis (Computers in Human Behavior, 2021)
The COVID-19 pandemic has caused a massive disruption in the way traditional higher education institutions deliver their courses. Unlike transitions from face-to-face teaching to blended, online or flipped classroom in the past, changes in emergency remote teaching –a temporary shift of instructional delivery to an alternate remote delivery mode due to crisis circumstances– happen suddenly and in an unplanned way. This study analyzes the move to emergency remote teaching at the School of Telecommunication Engineering (Universidad Politécnica de Madrid), and the impact of organizational aspects related to unplanned change, instruction-related variables –class size, synchronous/asynchronous delivery– and use of digital supporting technologies, on students' academic performance. Using quantitative data of academic records across all (N = 43) courses of a bachelor's degree programme in Telecommunication Engineering and qualitative data from a questionnaire delivered to all (N = 43) course coordinators, the research also compares the academic results of students during the COVID-19 pandemic with those of previous years. The results of this case study show an increase in students' academic performance in emergency remote teaching, and support the idea that organizational factors may contribute to successful implementation of emergency remote teaching; the analysis does not find differences across courses with different class sizes or delivery modes. The study further explores possible explanations for the results of the analysis, considering organizational, individual and instruction-related aspects.

Design for scalability: A case study of the River City curriculum - Clarke, Jody; Dede, Chris (Journal of Science Education and Technology, 2009)

Remote Learning: Rapid Evidence Assessment - Education Endowment Foundation (Education Endowment Foundation, 2020)
This rapid evidence assessment aimed to investigate methods that schools could use to support remote learning during school closures caused by the 2020 coronavirus pandemic (Covid-19). The review sought to find the best evidence behind the wide array of approaches that schools might choose to use during the crisis. The review systematically searched for/through existing meta-analyses and systematic reviews to find the best evidence for a wide range of approaches. In addition to the direct teaching of pupils online by teachers, the review also found evidence for approaches that pupils can use independently, including with technology that adapts the content of tasks in order to provide additional challenge or support, educational games, and for approaches that support peer interaction. The review also examined blended learning approaches, which combine remote and classroom teaching. While these approaches may not be directly applicable during school closures, they were included in case there were useful lessons to be learned that were relevant to the current context of home learning. This report summarises the findings from 60 systematic reviews and meta-analyses answers under five key topic areas: - General remote teaching and learning - Blended learning - Computer-supported collaborative learning - Computer assisted instruction - Educational games Another crucial aspect of supporting pupil’s learning is parental engagement. Parental engagement approaches are beyond the scope of this review, but an existing EEF guidance report, Working with Parents to Support Children’s Learning (2019), and accompanying evidence review summarise the best available evidence for engaging parents in their children’s education. In each section, we have detailed the included reviews and listed Findings and implications drawn from the evidence. We have also highlighted case studies from projects funded by the Education Endowment Foundation in which similar approaches have been rigorously evaluated in English schools.
Keywords: Methods; _DOILIVE; _EdTechHub_Output; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Online and distance teaching and learning A32ARSFK; _cover:other:ok; _zenodo:submitted; _zenodoETH

Using Bronfenbrenner’s ecological theory to understand community partnerships: A historical case study of one urban high school - Leonard, Jack (Urban Education, 2011)

Technology in education: a case study on Lao People's Democratic Republic - Nietschke, Yung; Dabrowski, Anna (International Education Research, 2023)
This paper was commissioned by the Global Education Monitoring Report as background information for the development of the 2023 Global Education Monitoring (GEM) Report: technology and education, Southeast Asia. Digital technology has the potential to transform learning and offer a solution to persistent challenges in equity of access and quality of learning for all students. COVID-19 has accelerated the adoption of technology to deliver alternative modes of education. It has also put the spotlight on the digital divide that technology creates. This Case Study explores the progress of technology integration in the education sector in Lao PDR in line with its aspirations for a thriving digital economy driven by a digitally-skilled workforce. It explores the current conditions that facilitate or inhibit digitalization of the education sector and considers the impact across the system, sector-wide and school levels. This includes issues relating to digital access, digital literacy of teachers and students, technology infrastructure investments and the regulatory environment. The findings suggest that many of these challenges are not unique to Lao PDR. However, with a clear strategy, political commitment and sustainable resourcing of the education sector, there are opportunities for the Government of Lao PDR and its partners, to set a strong foundation for digitalizing the education system.
Keywords: accepted; checks the GP(disadvntaged group-OOS)T, publisher: Global education Monitering report; ⛔ No DOI found; ⛔ No INSPIRE recid found

An Investigation on Learning Performance among Disabled People Using Educational Multimedia Software: A Case Study for Deaf People - Masitry, Ananthi Krishnasami; Majid, Mazlina Abdul; Toh, M Zulfahmi; Herawan, Tutut (2013)
The increasing number of people with hearing-impaired in Malaysia attracts to produce a variety of technologies, which can assist the deaf people in carrying out their tasks in everyday life as normal people. New technology can help to decrease the difficulty that hearing-impaired people faces in daily life to use the information services like normal people. Thus, this paper focuses on: i) developing a new multimedia courseware for pre-school students with hearing problem, and ii) comparing the deaf student’s learning performance before and after using the courseware. Four modules were developed for e-MSL courseware consist of alphabets, numbers, words and quizzes with colorful text, animation, sounds, video and pictures using Malaysian Sign Language (MSL). Sekolah Rendah Pendidikan Khas (SRPK) Indera Mahkota II, Kuantan has been chosen as the case study for data collection and for investigating the student learning performance on the courseware. The survey results show that 100% of the respondents have agreed that using e-MSL courseware managed to reduce the student learning time more than 80%. The result has indicated that students have shown better learning performance using e-MSL compared to traditional learning.

An investigation on learning Performance among disabled people using educational multimedia software: A case study for deaf people - Masitry, Ananthi Krishnasami; Majid, Mazlina Abdul; Toh, M. Zulfahmi; Sutarman, Sutarman; Herawan, Tutut (International Journal of Bio-Science and Bio-Technology, 2013)
The increasing number of people with hearing-impaired in Malaysia attracts to produce a variety of technologies, which can assist the deaf people in carrying out their tasks in everyday life as normal people. New technology can help to decrease the difficulty that hearing-impaired people faces in daily life to use the information services like normal people. Thus, this paper focuses on: i) developing a new multimedia courseware for pre-school students with hearing problem, and ii) comparing the deaf student’s learning performance before and after using the courseware. Four modules were developed for e-MSL courseware consist of alphabets, numbers, words and quizzes with colorful text, animation, sounds, video and pictures using Malaysian Sign Language (MSL). Sekolah Rendah Pendidikan Khas (SRPK) Indera Mahkota II, Kuantan has been chosen as the case study for data collection and for investigating the student learning performance on the courseware. The survey results show that 100% of the respondents have agreed that using e-MSL courseware managed to reduce the student learning time more than 80%. The result has indicated that students have shown better learning performance using e-MSL compared to traditional learning.
Keywords: ⛔ No INSPIRE recid found

Design and development of a Web Based Learning System in lower primary schools: A Case study of Makini Primary School, Kenya - Akinyi, Beatrice Ochieng (Moi University, 2015)
Web design technology arises from continued technological trend of computing. Globally the rise of application of information communication technology to the learning programme of primary schools is not much emphasized on. There is empirical evidence to prove that information communication technology is highly beneficial wherever it is applied. The study aimed at designing and developing a web based system of learning that can enhance the academic and social growth of lower primary school pupils. The objectives of the study were: to examine the correlation between the increased use of web based systems of learning and learner‟s academic performance; to identify the set of skills required for lower primary pupils to fully exploit the potential of web based systems of learning; to find out the specification and technical attributes of web based systems of learning that facilitate learning and lastly to design a web based learning system for lower primary school pupils. The study focused on Makini lower primary school in Nairobi County. The study employed case study method and qualitative approach. Rapid Application Development life cycle was used in software development process. Purposive sampling method was used to identify the respondents. Data was collected using interviews and focus group discussions. Findings of the study were: increased use of web based system that enhanced the learner‟s academic performance, the web based system of learning was able to identify games which exploit the pupils‟ skill in learning hence reducing monotony and lastly the web based system was able to identify some technical attributes such as use of graphics and access rights that facilitated learning and testing. The conclusion showed that developing of a web based learning system would reduce monotony in learning and enabled pupils to be in control and also increased the creativity and thinking level. The study recommends that: additions be made to the system such as a module to generate a feasible master timetable for each teacher; the web application of the system be further expanded to help attendance recording by the class teacher and for the parents to be able to view the status of their children performance using the Internet or Intranet of the school and lastly the system be made for every teacher to have some specific free periods or some part of days off and that will require an efficient search technique.
Keywords: ___working_potential_duplicate

Assessment of accelerated education to catch up with missed school programme in post crisis settings: Case study of selected IDP camps in Maiduguri metropolitan council - Wali, Yagana S; Muhammad Ali, Mustapha (British Journal of Educational Studies, 2019)
Keywords: ⛔ No DOI found

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech in Nigeria: A Rapid Scan. An overview of EdTech policies and interventions in Nigeria with a focus on northern Nigeria - Ramesh Vasudevan, Sharanya; Oyedele, Oluwatomisin (EdTech Hub, 2024)
Commissioned as a Helpdesk request from the FCDO-funded Partnership for Learning for All in Nigeria (PLANE) project, this EdTech Hub rapid scan provides an overview of the EdTech landscape in Nigeria. Given the PLANE programme’s focus on northern Nigeria, this rapid scan also assesses state-level policies and infrastructural challenges in three northern Nigerian states — Jigawa, Kaduna, and Kano. Furthermore, this rapid scan builds on the evidence presented in the previous EdTech Hub rapid scan from 2020, which focused on all states and the situation before the Covid-19 pandemic. Keywords: EdTech; policies; interventions; northern Nigeria; Partnership for Learning for All in Nigeria An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How to Design EdTech Programmes That Lead to Gender-Transformative Change - Samuels, Fiona; Leon-Himmelstine, Carmen; Marcus, Rachel; Myers, Christina (EdTech Hub, 2022)
This paper outlines how EdTech programming can adopt a gender-transformative approach to improve gender equity in access and learning outcomes. It explains what the term ‘gender-transformative change’ means, and why it is needed. Some key dimensions of gender-transformative approaches in the specific context of EdTech initiatives are outlined, looking at how different approaches can enhance access to education and learning opportunities and improve outcomes, and challenge discriminatory gender norms and stereotypes. Based on a desk review of grey and published materials, this paper then presents and discusses insights from the approaches taken by four EdTech programmes. Keywords: EdTech; gender-transformative; country case studies; education; girls’ education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Let’s learn together’: co-creating mental health solutions with adolescents in Tanzania and Viet Nam - Myers, Christina; Samuels, Fiona (ODI, 2022)

EdTech in Senegal: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Senegal; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; pu

EdTech in Nigeria: A Rapid Scan - Dele-Ajayi, Opeyemi; Taddese, Abeba (EdTech Hub, 2020)
Keywords: C:Nigeria; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Liberia: A Rapid Scan - Upadhyay, Arjun; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive. The aim is to provide a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Liberia. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Liberia; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

Education technology: An evidence-based review - Escueta, Maya; Quan, Vincent; Nickow, Andre Joshua; Oreopoulos, Philip (National Bureau of Economic Research, 2017)
In recent years, there has been widespread excitement around the potential for technology to transform learning. As investments in education technology continue to grow, students, parents, and teachers face a seemingly endless array of education technologies from which to choose—from digital personalized learning platforms to educational games to online courses. Amidst the excitement, it is important to step back and understand how technology can help—or in some cases hinder—how students learn. This review paper synthesizes and discusses experimental evidence on the effectiveness of technology-based approaches in education and outlines areas for future inquiry. In particular, we examine RCTs across the following categories of education technology: (1) access to technology, (2) computer-assisted learning, (3) technology-enabled behavioral interventions in education, and (4) online learning. While this review focuses on literature from developed countries, it also draws upon extensive research from developing countries. We hope this literature review will advance the knowledge base of how technology can be used to support education, outline key areas for new experimental research, and help drive improvements to the policies, programs, and structures that contribute to successful teaching and learning.
Keywords: ___working_potential_duplicate

E-learning tools for public awareness programme education in disaster risk management: Case study of the city of Cape Town disaster risk management centre - Kabaka, Martha; Stoltenkamp, Juliet (Proceedings of the International Conference on e-Learning, ICEL, 2013)
Disaster occurrence around the world has in the past few decades increased at an alarming rate necessitating an urgent need for mitigation strategies. As a result, research has indicated the usefulness of Information Communication Technology (ICT) in disaster risk management. Furthermore, ICT generally plays a critical role in all aspects of disaster risk management such as: early warning prediction; informing and circulating information relating to disasters to communities especially those at risk as promptly as possible and providing communication structures immediately after a disaster occurrence. As part of its planning and precautionary measures in responding to disasters, the City of Cape Town Disaster Risk Management Centre (CoCTDRMC) implements public awareness programmes across the city. The most acclaimed is an annual awareness programme especially for high school learners selected from various schools across the city. The learner participants are expected to act as change agents in their communities. In 2012, learners from twelve different schools across the city benefited from this programme. They were expected to educate families, friends, schoolmates and communities generally on the topical issues surrounding disaster risk management. This study uses a case study approach. Since the target audience of the programme is the youth, there is need to shift towards utilising ICT. The aim of this paper is to look at how e-learning as an ICT tool can be integrated in the implementation of Public Awareness Education Programme (PAEP), so as to target broader audience and create an increased capacity building across the City of Cape Town (CoCT). The examination considers providing tools that are accessible, dependable, resilient and flexible among the residents so as to reach the grassroots levels where communities are mostly affected. The paper considers a combination of tools so as to support behavioural change. Some of the research findings are that, the 2012 programme was very beneficial and successful. Henceforth there is need to target a broader audience, and although the CoCTDRMC does make use of some relevant ICTs, there is need for additional and upgraded technological resources. Also pertinent is the fact that e-learning can play a major role in making sure that a broader audience is reached if applied effectively. The findings of the research are of relevance to the CoCTDRMC and other municipalities across South Africa. The Centre for Innovative Educational and Communication Technologies (CIECT) at the University of the Western Cape can also use these findings to develop and implement an e-learning course for both employees of CoCTDRMC and other interested community members. This will guide them on how e-learning can assist in fostering a successful implementation of PAEP across the city.
Keywords: Disaster; Disaster risk management; E-learning; Information communication technology; Public awareness education programme; ⛔ No DOI found

Learning through Video Games: A Case Study of Private Schools of Pakistan - Khalid, Tooba; Batool, Syeda Hina (Ieee, 2018)
This study investigated video game based academic and information literacy (IL) learning of teenagers of private schools of Lahore city. Lahore is one of the big city and knowledge hub of Pakistan. Previous literature highlighted the importance of video games in learning academic and IL skills; therefore, the present study aims to reveal this fact in local context. The presented study adopted qualitative research approach and utilized phenomenological research method to achieve its objectives. The data was collected through interviews. The study participants were teenagers (13 to 19 years) of elite economic class private schools who were frequent video game players. Based on the study findings, it can be concluded that playing video games has positive impact on teenagers' learning. The majority of the participants were of view that challenges of completing various stages of games and interacting with online competitors enhanced their social (communication) and information literacy (searching/locating and evaluating) skills. The results of the study are benefitted for the game developers, teachers, librarians and parents.
Keywords: Pakistan; academic learning; information literacy; learning; skills; video games

EdTech Horizon Scan: Blockchain technology in education - Beoku-Betts, Iman; Kaye, Tom (EdTech Hub, 2022)
EdTech Hub horizon scans are publications designed to provoke thinking on a range of topics related to the design, implementation, oversight, and monitoring and evaluation of educational technology (EdTech) tools, products, services, and related ideas. This EdTech Horizon Scan examines the use of blockchain technology in education. Beginning with an overview of blockchain technology, the scan explains what blockchain technology is and how it works. The next section focuses on how blockchain technology can be used in education. In particular, it looks at the benefits of using blockchain technology for micro-credentialing and ownership of learning credentials, the transfer of credits and smart contracts, storing student credentials, identity verification and intellectual property protection. Section 4 gives a summary of the use of blockchain technology, noting the different challenges that may be associated with adopting blockchain technology into education systems. Section 5, gives real examples of the use of blockchain technology in education and different education institutions. Key words: blockchain; cryptography; data; decentralised database; digitalisation; education; micro-credentialing; smart contracting; student credentials; verification An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers - Hanemann, Ulrike; Scarpino, Cassandra (UNESCO Institute for Lifelong Learning, 2016)
The UNESCO Institute for Lifelong Learning (UIL) has published a second edition of "Harnessing the Potential of ICTs: Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets and Computers." This compilation of case studies from all world regions presents promising literacy and numeracy programmes that use information and communication technologies (ICTs) in their access and outreach strategies. The twenty-six case studies illustrate how ICTs such as radio, TV, mobile phones, tablets and computers can be used as media of instruction, can supplement face-to-face teaching, and can help to develop and strengthen youth and adult literacy, language and numeracy skills. The case studies featured in this publication can also be found in the UNESCO Effective Literacy and Numeracy Practices Database (LitBase). [For the 1st Edition: "Harnessing the Potential of ICTs for Literacy Teaching and Learning: Effective Literacy and Numeracy Programmes Using Radio, TV, Mobile Phones, Tablets, and Computers," see ED560504.]
Keywords: Adult Literacy; Case Studies; Distance Education; Educational Technology; Foreign Countries; Handheld Devices; Instructional Materials; Literacy Education; Mathematics Education; Numeracy; Program Content; Program Effectiveness; Radio; Teaching Methods; Technology Integration; Technology Uses in Education; Telecommunications; Television; Videoconferencing

Factors affecting the E-learning acceptance: A case study from UAE - Salloum, Said A.; Al-Emran, Mostafa; Shaalan, Khaled; Tarhini, Ali (Education and Information Technologies, 2019)
The main objective of this article is to study the factors that affect university students’ acceptance of E-learning systems. To achieve this objective, we have proposed a new model that aims to investigate the impact of innovativeness, quality, trust, and knowledge sharing on E-learning acceptance. Data collection has taken place through an online questionnaire survey, which was carried out at The British University in Dubai (BUiD) and University of Fujairah (UOF) in the UAE. There were 251 students participated in this study. Data were analyzed using SmartPLS and SPSS. The Structural Equation Modelling (SEM) has been used to validate the proposed model. The outcomes revealed that knowledge sharing and quality in the universities have a positive influence on E-learning acceptance among the students. Innovativeness and trust were found not to significantly affect the E-learning system acceptance. By identifying the factors that influence the E-learning acceptance, it will be more useful to provide better services for E-learning. Other implications are also presented in the study.

Advancing women’s digital skills and economic empowerment through girls in tech Indonesia: A case study - Afiani, Isyfi (Salasika, 2018)
The advancing Information and Communication Technology (ICT) has massively supported the economy in the digital era as it disseminates, stores, brings added value and manages information to provide unlimited opportunities for economic development. However, ICT may contribute to discrimination and existing inequalities reinforcement so-called the digital divide. Since all aspects of human interaction with ICT are gendered, this study tackles the digital gender divide issue, that is, the gap between men and women regarding access to, content and use of ICT. Accordingly, in 2016, the gender gap of global internet users was 12% and it grows every year. In response to this condition, a global movement promoting women engagement in ICT has emerged. This study, therefore, depicts the role of Girls in Tech Indonesia community as a chapter of Global Girls in Tech movement in advancing women economic empowerment through ICT by implementing transformational leadership concepts and Longwe’s empowerment framework. In the core of qualitative studies, this study shows that Girls in Tech Indonesia’s leadership performance contributes positively to women empowerment.
Keywords: Empowerment; Girls in Tech; ICT; Leadership; ⛔ No INSPIRE recid found

Challenges and opportunities for e-learning in education: A case study - Kafyulilo, Ayoub C. (Handbook of Research on Educational Technology Integration and Active Learning, 2015)
This chapter presents a review of literature on the existing opportunities and challenges of adopting e-learning in education in Tanzania and the possible measures to overcome some challenges. The study also assessed the primary factors contributing to the slow and limited use and integration of tec...

A case study of students’ and teachers’ perceptions in a Finnish high school during the COVID pandemic - Niemi, Hannele Marjatta; Kousa, Päivi (International Journal of Technology in Education and Science, 2020)
This study describes one local upper secondary school in Finland during the COVID-19 pandemic. All teaching was changed to distant for around two months. The study describes students’ and teachers’ perceptions during that time. Participants responded to the survey four times and freely described their experiences five times. The number of participants varied from 56 to 72 students and 9 to 15 teachers at different times. The data were analyzed by descriptive statistics, cluster analysis, and qualitative content analysis. The main findings indicate that distance teaching was implemented very successfully. However, open comments and cluster analysis revealed many challenges. Students complained of heavy workloads and fatigue. Some students lost motivation. These difficulties did not disappear over time. The main challenges for teachers included non-authentic interaction and a lack of the spontaneity that in-person teaching provides. Teachers quickly learned to use technological platforms, but interaction through it was not of as high quality. Teachers were also worried about students’ progress. Teachers did not recognize students’ heavy workload and motivation problems in the way that students described them. The study provides several recommendations for future remote teaching.

Using Educational Games for Sign Language Learning - A SignWriting Learning Game: Case Study - Bouzid, Yosra; Khenissi, Mohamed Ali; Essalmi, Fathi; Jemni, Mohamed (Journal of Educational Technology & Society, 2016)
ABSTRACT Apart from being used as a means of entertainment, computer games have been adopted for a long time as a valuable tool for learning. Computer games can offer many learning benefits to students since they can consume their attention and increase their motivation and engagement which can then lead to stimulate learning. However, most of the research to date on educational computer games, in particular learning versions of existing computer games, focused only on learner with typical development. Rather less is known about designing educational games for learners with special needs. The current research presents the results of a pilot study. The principal aim of this pilot study is to examine the interest of learners with hearing impairments in using an educational game for learning the sign language notation system SignWriting. The results found indicated that, overall, the application is useful, enjoyable and easy to use: the game can stimulate the students' interest in learning such notations.
Keywords: ⛔ No DOI found

Scrutinizing practicum for a more powerful teacher education: a longitudinal study with pre-service teachers - Tülüce, Serdar Hande; Çeçen, Sevdeger (Educational Sciences: Theory and Practice, 2016)
This study aims to explore the role of school-based practicum in promoting pre-service English language teachers' professional development through the use of a longitudinal design in combination with qualitative methods. To achieve this aim, pre-service teachers were asked to successively reflect on video-recordings of their micro-lessons in their university-based methodology courses directly after delivering the micro-lessons and retrospectively after their practicum experience. The participants of this study were 13 pre-service English language teachers studying at a foundation university in Istanbul, Turkey. The same data collection methodology was adapted before and after the practicum to gain a deeper understanding of the learning stemming from school-based practicum. The data for the study came from pre- and post-self-evaluation reports as well as pre- and post-focus-group interviews that had been collected based on the pre-service teachers' video-recorded microteaching simulations. The findings indicate that pre-service teachers commented on the same pedagogical, psychological, and physical factors they had noticed regarding their micro-lesson before and after the practicum. However, some qualitative changes were detected in their views over time as they had become more learner-oriented and had developed a more reflective view of teaching following the practicum. These findings have implications for the impact of practicum for future teacher education programs.
Keywords: Attitude Change; Case Studies; ERIC, Current Index to Journals in Education (CIJE); English (Second Language); Focus Groups; Foreign Countries; Higher Education; Language Teachers; Learning Processes; Longitudinal Studies; Microteaching; Physical Characteristics; Postsecondary Education; Practicums; Preservice Teacher Education; Preservice Teachers; Pretests Posttests; Professional Development; Psychological Patterns; Qualitative Research; Reflective Teaching; Second Language Instruction; Self Concept; Self Evaluation (Individuals); Simulation; Student Teacher Attitudes; Teaching Methods; Transformative Learning; Turkey (Istanbul); Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096126; __finaldtb

The impact of online learning as emerging technology on parents: Case study of parents of primary school children in Nairobi, Kenya. - Emmanuel, Jadesola; Oduor, Collins (Journal of Language, Technology & Entrepreneurship in Africa, 2021)
Kenya, as a nation has a stable schooling system based on synchronous classroom learning. The advent of the COVID 19 pandemic has led to the sudden shift in paradigm to remote schooling learning systems. Several studies have been carried out on remote schooling systems and the impact of parent’s involvement in children’s remote school, but none has been sighted on its impact on parents. The objective of this study was to determine the impact of the sudden paradigm shift on parents of remote schooling pupils in Kenya during this pandemic. A descriptive survey design was utilized. Primary data was collected by online questionnaires and secondary data from past studied. The analysis was done with a statistical application. It was found out that, remote schooling may be easily accepted by many Kenyan parents with 39.8% of parents indicating that they will recommend remote schooling having indicated some benefits derived from it and 24.8% indicating that they will not. It was therefore recommended that the national government should address factors that may hinder effective remote learning, thus encouraging parental involvement and support. It was also recommended that the government and education practitioners should officially develop and implement standards and curriculum for the implementation of remote learning in Kenya in preparation for future pandemics. Keywords: remote schooling, remote learning, descriptive survey design
Keywords: ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)
This report was prepared by Bjöern Haßler for the Research for Equitable Access and Learning (REAL) Centre, University of Cambridge, UK, with support from the Global Education & Skills Forum (GESF) Alliance on Assessment and Impact for Learning. This Alliance was co-chaired by Pauline Rose (REAL Centre, University of Cambridge, United Kingdom) and Baela Raza Jamil (Idara-e-Taleem-o-Agahi, Pakistan) and included the following members: Emma Broadbent (The Varkey Foundation, United Kingdom), Andrew Cunningham (Aga Khan Foundation, Switzerland), Joseph Chimombo (Ministry of Education, Malawi), Rashmi Kauthria (Global Teacher Prize Finalist 2017, India), Lucy Lake (Camfed, United Kingdom), Shajia Sarfraz (Independent Researcher, Pakistan) and Miguel Szekely (Center for Education and Social Studies, Mexico).
Keywords: _DOILIVE; ___working_potential_duplicate; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Online learning community: A case study of teacher professional development in Indonesia - Sari, Eunice (Intercultural Education, 2012)
This paper investigates the concept of online learning community (OLC) to address the issues of teacher professional development practice in twenty-first-century Indonesia. Teachers in Indonesia are trained in a 'conventional way', hence, not ready to prepare the younger generations for entrance into the twenty-first-century complex life and work environment. The pedagogical transformation of a teacher can be facilitated through teacher professional development. Recent studies show that OLC holds great promise in improving teachers' professional practice. This paper presents key results of the introduction and trialling of OLC with Indonesian teachers and teacher educators between 2009 and 2010 and aims to explore the feasibility of this model to support professional development of teachers in this era. The social learning interactions among community members were examined using Scardamalia's Twelve Socio-Cognitive Determinants of Knowledge Building and Hoftsede's Cultural Dimension Review for Indonesia.

Evaluation of the application of mobile phone technology in teaching and learning: A case study of Kamwenja Teacher' college, Nyeri County, Kenya. - Gitome, Mwangi Joseph (Mount Kenya University, 2015)
This research was designed to investigate the application of mobile phone technology in teaching and learning among tutors and students of Kamwenja Teachers College in Nyeri County in Kenya. The problem this study addressed was to establish whether mobile phones in the hands of students and tutors were beneficial for teaching and learning or if they impede learning process in Teacher Training Colleges in Kenya. The variables under consideration were: quality teaching and learning as dependent variable and owning mobile phones, awareness of educational potential of mobile phones, acceptance of mobile phones, and mobile phones influence as alternative learning and instructional methods as independent variables. The data was collected from 71 tutors and 498 students. The sample size was worked out at 20% to be 15 tutors and 100 second year teacher trainees in the college. Stratified random sampling was used to ensure the sample was a true representation of the whole population. Data was collected through questionnaires that were both quantitative and qualitative to ensure high quality of information for the study where 98.2% response rate was achieved. To ensure Validity and Reliability of Research Instruments a pre-test of the questionnaire was conducted on tutors and students of Kagumo Teachers College. A reliability coefficient of 0.7 was adopted for the items while an expert, the supervisor, guided in validity of the items. The study was guided by the activity theory also known as Cultural Historical Activity Theory. Primary data was analysed with the aid of Statistical Package for Social Sciences (SPSS version 20) software to generate descriptive statistics, correlation and multiple regression analysis. The findings of the study revealed that ownership of mobile phone had a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly and even when regressed together with other factors. Further, the study revealed that awareness of the educational potential of mobile phone technology, acceptance of mobile phone technology and mobile phone technology as an alternative learning and instructional methods were found to have a positive and significant effect on application of mobile phone technology in teaching and learning when considered singly, however when all the factors were regressed together they were found to have a positive and but insignificant effect on application of mobile phone technology in teaching and learning. In order to enhance use of mobile phone technology in teaching and learning students and teachers should be encouraged to acquire mobile phones with internet connectivity features. The general usage of mobile phone in teachers training colleges was found to be very high. However the rate at which mobile phones are used for exchanging learning information is low. The researcher recommends that policies be put in place on use of mobile phone technology in teaching and learning and train tutors on how to teach differently using mobile phone technology. Future researchers should try to establish hindrances of application of mobile phone technology in teaching and learning.

Girls’ Education and EdTech: A Rapid Evidence Review - Webb, Daniel; Barringer, Katie; Torrance, Rebecca; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of technology in supporting girls’ education in low and middle-income countries (LMICs). The RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread global shutdown of schools. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations to the continuation of schooling caused by COVID-19. Established approaches to maintaining continuity of education for the most marginalised have particular salience during this period because of the significant increase in the number of students at risk of disruption. Research consistently shows that while education across the board is negatively affected by crisis situations, the schooling of girls is disproportionately impacted. The RER aims neither to advocate nor discourage the use of technology in girls’ education in response to the present COVID-19 pandemic, but rather to provide an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential role of technology in delivering education for girls.
Keywords: L:English UXZJW5DR; L:Gender and education; LP: English; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Towards the development of mobile learning model for Tanzania secondary schools: Case study Kilimanjaro region - Chambo, F. F.; Laizer, L. S.; Nkansah-Gyekye, Y.; Ndume, V. (2013 Pan African International Conference on Information Science, Computing and Telecommunications (PACT), 2013)
This paper explores the factors that influence the implementation of m-learning and proposes a model for implementing m-learning in Tanzania. The study was conducted in ten secondary schools in the Kilimanjaro region in Tanzania. Purposive and convenience sampling techniques were used to determine students majoring in science subjects. Findings indicate that majority of students own mobile phones and have access to the Internet connectivity. However, m-learning platforms that are currently in place are not viable solution in all contexts and not necessarily the best solution. Therefore, the design of m-learning content should focus on learning profile and personal needs such as location and affordability. A framework that considers four factors: user satisfaction, pedagogy, technology, and economy of use are proposed for Tanzanian context. It is concluded that education stakeholders should consider the opportunities of technology in education in order to boost knowledge sharing among students.
Keywords: Computational modeling; Context modeling; Educational institutions; Internet; Internet connectivity; Interoperability; Kilimanjaro region; Learning Science; M-Learning; Materials; Mobile handsets; Secondary School; Tanzania secondary school; computer aided instruction; economy of use; education stakeholder; emerging technology; knowledge sharing; m-learning; mobile learning; mobile learning model; mobile phone; pedagogy; sampling methods; sampling technique; science subject; user satisfaction

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

Live video classroom observation: an effective approach to reducing reactivity in collecting observational information for teacher professional development - Liang, Jiwen (Journal of Education for Teaching: International Research and Pedagogy, 2015)
This paper examines the significance of live video classroom observations of teaching practice to reduce reactivity (the observer effect) so as to obtain more credible observational information for teacher professional development in a secondary school in the largest city in southern China. Although much has been discussed regarding the use of remote live video classroom observation for professional development, the advantage of remote live video classroom observation in reducing reactivity has often been overlooked. Using the case study method, the research reported here focuses on two components: conducting live video classroom observation and the use of the live video classroom observation in reducing reactivity. This paper suggests that live video classroom observation is effective in reducing reactivity and helps avoid subjective judgement and increase feedback sources, thus providing a solution to compensate for the limitations of traditional classroom observations.
Keywords: Administrator Attitudes; Case Studies; Case studies; China; Classroom Observation Techniques; Classroom observation; ERIC, Current Index to Journals in Education (CIJE); Education; Effectiveness; Faculty Development; Feedback; Feedback (Response); Foreign Countries; Interviews; Principals; Professional development; Qualitative Research; Secondary Education; Secondary School Teachers; Secondary schools; Teacher Attitudes; Teacher education; Teaching; Teaching Methods; Teaching methods; Video; Video Technology; Video recordings; __:import:01; __:match:final; __:matched; __:study_id:2096967; __finaldtb

JIME - The Open Learning Initiative: Measuring the Effectiveness of the OLI Statistics Course in Accelerating Student Learning - Lovett, Marsha; Meyer, Oded; Thille, Candace (Journal of Interactive Media in Education, 2008)
The Open Learning Initiative (OLI) is an open educational resources project at Carnegie Mellon University that began in 2002 with a grant from The William and Flora Hewlett Foundation. OLI creates web-based courses that are designed so that students can learn effectively without an instructor. In addition, the courses are often used by instructors to support and complement face-to-face classroom instruction. Our evaluation efforts have investigated OLI courses’ effectiveness in both of these instructional modes – stand-alone and hybrid. This report documents several learning effectiveness studies that were focused on the OLI-Statistics course and conducted during Fall 2005, Spring 2006, and Spring 2007. During the Fall 2005 and Spring 2006 studies, we collected empirical data about the instructional effectiveness of the OLI-Statistics course in stand-alone mode, as compared to traditional instruction. In both of these studies, in-class exam scores showed no significant difference between students in the stand-alone OLI-Statistics course and students in the traditional instructor-led course. In contrast, during the Spring 2007 study, we explored an accelerated learning hypothesis, namely, that learners using the OLI course in hybrid mode will learn the same amount of material in a significantly shorter period of time with equal learning gains, as compared to students in traditional instruction. In this study, results showed that OLI-Statistics students learned a full semester’s worth of material in half as much time and performed as well or better than students learning from traditional instruction over a full semester. Editor: Stephen Godwin (Open University, UK). Reviewers: Tim de Jong (Open University, NL), Elia Tomadaki (Open University, UK), and Stephen Godwin (Open University, UK). Interactive elements: A demonstration of the StatTutor statistics tutorial is available for playback from http://jime.open.ac.uk/2008/14/stattutor_tour/ . The demonstration is in Flash format. http://jime.open.ac.uk/2008/14/stattutor_tour/
Keywords: IDR; Mathematics Learning; case studies; design patterns; games; methodology; open learning; pattern languages

“He is suitable for her, of course he is our relative”: a qualitative exploration of the drivers and implications of child marriage in Gezira State, Sudan - Dean, Laura; Obasi, Angela; Sony, Asma El; Fadul, Selma; Hassan, Hanaa El; Thomson, Rachael; Tolhurst, Rachel (BMJ Global Health, 2019)
Introduction Child marriage is a fundamental development challenge for women and girls, with significant negative health and social outcomes. Sudan has a high rate of child marriage, with 34% of women aged 20–24 married before their 18th birthday. Since limited preventive interventions exist, we aimed to inform the evidence base to strengthen strategic action, using mixed qualitative methods to enhance study credibility. This study is the first to conduct a rigorous qualitative examination of the drivers of child marriage from the perspective of key stakeholders involved in marriage decision making within Sudan, and makes a significant contribution towards global knowledge by developing an evidence-based conceptual framework. Methods Initially, we completed 14 focus group discussions separated by gender with mothers, fathers, and girls married as adolescents, and 23 key informant interviews. We then used a critical incident case study approach to explore 11 ‘cases’ of child marriage (46 interviews). Results Findings indicate that gendered social norms and values, underpinned by religious beliefs and educational accessibility, interconnect to shape marriage decisions. In this context, many child marriages are triggered by an intrakinship proposal and further enabled by the relative lack of autonomy and influence of girls and women in marriage decision-making processes. Discussion Interconnected drivers demand context-specific holistic and multisectoral approaches, which should include simultaneous strategies to expand access to education, health services and livelihood opportunities, and evoke legal change, and participatory social and attitudinal processes that include the engagement of religious leaders and men.
Keywords: child health; qualitative study

MOOCs for in-service teachers: the case of Uganda and lessons for Africa - Oyo, B.; Kalema, B.M.; Byabazaire, J. (Revista Española de Pedagogía, 2017)
In recent times, computers and internet have penetrated secondary schools in Africa but with greater attention to students’ computer literacy than teachers. At the same time, previous studies on digital literacy of teachers are unsustainable and mainly skewed on pre-service teachers than in-service teachers. These realities point to the need to investigate and implement effective and sustainable initiatives for improving digital literacy and online life-long learning for in-service teachers in Africa. This paper therefore presents a specialised MOOC platform known as TEP (Teachers’ E-learning Portal) for digital literacy and online life-long learning for in-service teachers in Uganda. TEP is built for environments with inadequate access to computers, internet and technical assistance. As such, TEP is accessible online or offline, managed by accredited local universities in collaboration with beneficiary secondary schools, and runs on existing resources in schools (technical personnel, computers and internet). Results from initial implementation of a computer literacy MOOC through TEP indicate that irrespective of age, when teachers are adequately supported internally by their schools and externally by a university, can improve their digital literacy and subsequently engage in online life-long learning. In addition, the results both in terms of high percentage of teacher participants’ completions (89%) and high volume of educational e-content generated, confirm TEP as an effective, attractive, and self-sustainable MOOC platform for in-service teachers’ in resource constraint environments. The paper finishes with an analysis of the relevance of TEP to Africa.
Keywords: _Source:Intuitive; _THEME: Education management; _THEME: Teacher Professional Development; __:import:03; __:match:final; __:matched; __:study_id:2426079; __finaldtb

MOOCs for in-service teachers: the case of Uganda and lessons for Africa - Oyo, B.; Kalema, B.M.; Byabazaire, J. (Revista Española de Pedagogía, 2017)
In recent times, computers and internet have penetrated secondary schools in Africa but with greater attention to students’ computer literacy than teachers. At the same time, previous studies on digital literacy of teachers are unsustainable and mainly skewed on pre-service teachers than in-service teachers. These realities point to the need to investigate and implement effective and sustainable initiatives for improving digital literacy and online life-long learning for in-service teachers in Africa. This paper therefore presents a specialised MOOC platform known as TEP (Teachers’ E-learning Portal) for digital literacy and online life-long learning for in-service teachers in Uganda. TEP is built for environments with inadequate access to computers, internet and technical assistance. As such, TEP is accessible online or offline, managed by accredited local universities in collaboration with beneficiary secondary schools, and runs on existing resources in schools (technical personnel, computers and internet). Results from initial implementation of a computer literacy MOOC through TEP indicate that irrespective of age, when teachers are adequately supported internally by their schools and externally by a university, can improve their digital literacy and subsequently engage in online life-long learning. In addition, the results both in terms of high percentage of teacher participants’ completions (89%) and high volume of educational e-content generated, confirm TEP as an effective, attractive, and self-sustainable MOOC platform for in-service teachers’ in resource constraint environments. The paper finishes with an analysis of the relevance of TEP to Africa.
Keywords: _Source:Intuitive; _THEME: Education management; _THEME: Teacher Professional Development; __:import:03; __:match:final; __:matched; __:study_id:2426079; __finaldtb

Interrogating gender divides in technology for education and development: The case of the one laptop per child project in Ghana - Steeves, H. Leslie; Kwami, Janet (Studies in Comparative International Development, 2017)
The One Laptop per Child (OLPC) project aims to make low-cost computers accessible to the “world’s poorest children,” presuming that the gadgets will support their empowerment via education. The project’s success globally, however, has been mixed at best, with many countries terminating their purchases due to cost, inadequate infrastructure, and negative side effects. In October 2010, Ghana suspended the country’s 3-year participation. This study examines the complex history and failure of OLPC Ghana in two pilot schools, one urban and one rural, with particular attention to gender bias. The analysis draws on interviews with government personnel, students, and teachers in the pilot classes. Despite lacking electric power in the rural community, UNDP’s Millennium Villages Project played a strong support role, making OLPC somewhat more effective with less of a gender divide in the rural school than in the urban school in Accra. Both pilot schools faced severe sustainability challenges raising decade-old questions about modernity and technological determinism. Further, in both schools, particularly the urban school, a digital divide by gender was evident.
Keywords: Development; Gender; Ghana; Information communication technology (ICT); Internet; ⛔ No INSPIRE recid found

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

#CostingEquity: The case for disability-responsive education financing - Myers, Juliette; Pinnock, Helen; Baboo, Nafisa; Lewis, Ingrid (International Disability and Development Consortium, 2018)
The #CostingEquity research project investigated the benefits of financing disability-inclusive education, the current state of education financing with regard to inclusion, and what needs to change in order for education financing to effectively support the realisation of SDG 4. The #CostingEquity research report addresses three broad questions: • How do international donors and domestic governments currently fund disability-inclusive education? • What are the gaps and challenges in financing disability-inclusive education? • What needs to change to increase quality, equitable financing for learners with disabilities? The report aims to contribute to a better understanding of the issues related to equitable financing for education for learners with disabilities. It considers additional marginalising factors such as gender, socio-economic status, social circumstances and urban/rural location. It offers key arguments for civil society activists, donors and government advisors to make the case for building and strengthening inclusive education systems. Detailed case studies provide useful examples of financing gaps, challenges and promising practice from developing country contexts, major education donors, and new and emerging philanthropic donor foundations. The focus of case studies and examples is on low and lower-middle income countries and were chosen to reflect a broad range of regions and countries.The report concludes with a series of recommendations for domestic and external financing approaches.

Curriculum flexibility in a blended curriculum - Jonker, Herma; März, Virginie; Voogt, Joke (Australasian Journal of Educational Technology, 2020)
This study offers insights into the processes that play a role in realising curriculum flexibility. Curriculum flexibility is conceptualised in terms of adaptability and accessibility of the curriculum to students’ needs and capabilities. To realise curriculum flexibility, the teacher education institution in this study designed a blended curriculum with face-to-face and online components. This flexible curriculum aimed at increasing student enrolment and allowing for variety in students’ graduation portfolios. Through semi-structured interviews with 10 teacher educators, conditions that could foster or hinder the realisation of flexibility were investigated. Results indicate that different contextual, teacher-, and student-related conditions were perceived to affect (further) curriculum flexibility. Furthermore, teacher educators identified several challenges related to these influential conditions, which were recognised as tensions. Based on a discussion of these findings, recommendations for research and practice are given.
Keywords: blended curriculum; case study research; collaborative design; curriculum flexibility; curriculum implementation; perceived curriculum; qualitative research

Behaviour change key principles for EdTech | MASTER framework - Rahman, Asad; Carter, Alice; Wambûi Kuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries, to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool aims to help you get started with ways to design for innovation behaviours or mindsets and make them stick. Keywords: behavioural change; behavioural design; behavioural innovation; EdTech; innovation; sandbox; intervention design An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Sandbox Model: A Novel Approach to Iterating while Implementing an Emergency Education Program in Lebanon during the COVID-19 Pandemic - Boujikian, Michèle; Carter, Alice; Jordan, Katy (2022)
Jusoor’s Refugee Education Program helps Syrian refugee children living in Lebanon integrate back into formal schooling. When schools closed due to the COVID-19 pandemic, the refugee program adapted to distance learning by developing Azima, a novel program that used WhatsApp to enable children to keep learning. Azima had to respond immediately to the emergency context while maintaining high education standards, and it also needed to find an effective way to test and refine its content quickly. To do this, the Azima program adopted an innovative experimental approach called a sandbox. A sandbox model operates in rapid iterative cycles and uses multiple methods to quickly test a program’s assumptions about how it will meet its goals. In this field note, we use Azima as a case study to report on our experience of applying the sandbox model. We reflect on the benefits and limitations of this novel approach in supporting the use of education technology in a crisis situation.

Education for people and planet: creating sustainable futures for all - UNESCO (2016)
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Scopus AI Beta: functional analysis and cases - Aguilera Cora, Elisenda; Lopezosa, Carlos; Codina, Lluís (2024)
Academic databases are a fundamental source for identifying relevant literature in a field of study. Scopus contains more than 90 million records and indexes around 12,000 documents per day. However, this context and the cumulative nature of science itself make it difficult to selectively identify information. In addition, academic database search tools are not very intuitive, and require an iterative and relatively slow process of searching and evaluation. In response to these challenges, Elsevier has launched Scopus AI, currently in its Beta version. As the product is still under development, the current user experience is not representative of the final product. Scopus AI is an artificial intelligence that generates short synthesis of the documents indexed in the database, based on instructions or prompts. This study examines the interface and the main functions of this tool and explores it on the basis of three case studies. The functional analysis shows that the Scopus AI Beta interface is intuitive and easy to use. Elsevier's AI tool allows the researcher to obtain an overview of a problem, as well as to identify authors and approaches, in a more agile search session than conventional search. Scopus AI Beta is not a substitute for conventional search in all cases, but it is an accelerator of academic processes. It is a valuable tool for literature reviews, construction of theoretical frameworks and verification of relationships between variables, among other applications that are actually impossible to delimit.
Keywords: ⛔ No DOI found

Using online peer assessment in an instructional technology and material design course through social media - Demir, Mehmet (Higher Education: The International Journal of Higher Education Research, 2018)
This study was designed to investigate the student teachers perceptions about and benefits and challenges of using Facebook as an online peer assessment tool for the student teachers' works. The study group included 24 student teachers in science education department of a state university located in the southeast region of Turkey. A case study approach of the qualitative method was employed in the research. Semi-structured interviews were conducted to collect the data. The interviews were audio recorded, and records of all the interviews were transcribed into full text in Turkish. Collected data were analyzed using an emergent coding approach. Codes, then, were categorized to constitute themes and subthemes. The findings indicated that the student teachers were able to give objective feedback on their peers' work and engaged more actively in class after participating in online peer assessment. Additionally, the students found it exciting and productive to use Facebook as a peer assessment tool in their learning.
Keywords: Case Studies; Case studies; Coding; College students; Computer Uses in Education; ERIC, Current Index to Journals in Education (CIJE); Education--Higher Education; Educational Technology; Educational technology; Feedback; Feedback (Response); Foreign Countries; Higher Education; Higher education; Instructional Technology and Material Design; Internet; Interviews; Learner Engagement; Learning; Mass media; Peer Evaluation; Peer assessment; Peers; Preservice Teachers; Qualitative Research; Qualitative research; Science education; Semi Structured Interviews; Social Media; Social classes; Social media; Social networks; Structured interviews; Student Attitudes; Student teachers; Students; Teachers; Technology; Turkey; __:import:01; __:match:final; __:matched; __:study_id:2097831; __finaldtb

Digital Gender Divide or Technologically Empowered Women in Developing Countries? A Typical Case of Lies, Damned Lies, and Statistics - Hilbert, Martin (Social Science Research Network, 2011)
The discussion about women’s access to and use of digital Information and Communication Technologies (ICT) in developing countries has been inconclusive so far. Some claim that women are rather technophobic and that men are much better users of digital tools, while others argue that women enthusiastically embrace digital communication. This article puts this question to an empirical test. We analyze data sets from 12 Latin American and 13 African countries from 2005-08. This is believed to be the most extensive empirical study in this field so far. The results are surprisingly consistent and revealing: the reason why fewer women access and use ICT is a direct result of their unfavorable conditions with respect to employment, education and income. When controlling for these variables, women turn out to be more active users of digital tools than men. This turns the alleged digital gender divide into an opportunity: given women’s affinity for ICT, and given that digital technologies are tools that can improve living conditions, ICT represent a concrete and tangible opportunity to tackle longstanding challenges of gender inequalities in developing countries, including access to employment, income, education and health services.
Keywords: Damned Lies; Digital Gender Divide or Technologically Empowered Women in Developing Countries? A Typical Case of Lies; Martin Hilbert; SSRN; and Statistics

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Structured Pedagogy and EdTech - Adam, Taskeen; Chuang, Rachel; Haßler, Björn (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _coming soon; _cover:analysis:nopdf; dode_eth-src-eth; dode_eth-trf2-dode

Networks and Power: Why Networks are Hierarchical Not Flat and What Can Be Done About It - Faul, Moira V. (Global Policy, 2016)
Many scholars, policy makers and practitioners associate new, networked forms of collaboration and governance with positive attributes such as speed, flexibility, adaptability and ‘flatness’. This article contrasts the assumptions that networks essentially moderate external asymmetries of power with the network theoretical view that networks may amplify existing hierarchies. The case study network explored supports the network theoretical view that existing power relations may be increased when a multistakeholder partnership network is established. The use of Social Network Analysis facilitates the comparison of the structures and relationships into which global policy actors are organised (the formal network) with the relationships and relational structures into which they choose to organise themselves (informal network). In the conclusions, I introduce the practice of network rewiring that could overcome the network mechanisms that amplify existing power relations. Further research is required that adds more case study evidence in order to raise (and begin to answer) questions that will give a wider view of the social structuring of power in partnership networks in international development, such as those referred to in the recently-adopted Sustainable Development Goals (SDGs).

Trust, Accountability and Capacity in Education System Reform | Taylor & Francis Group - Ehren, Melanie; Baxter, Jacqueline (Taylor & Francis, 2020)
This global collection brings a new perspective to the field of comparative education by presenting trust, capacity and accountability as the three building

Tusome Midline evaluation 2017 final report from DEC - Freudenberger, Elizabeth; Davis, Jeff (2017)
Keywords: ⚠️ Invalid DOI

The Primary Math and Reading Initiative (PRIMR) - RTI International (2014)

Educational technology to improve capacity - integrating adaptive programmes in public schools in Kenya - Kaye, Tom (2021)

An Investigation into Implementation of ICT in ECD and Primary Schools, in the Light of Free Laptops at Primary One: a case study of teachers implementing ICT into their teaching practice - Tonui, Betty C.; Kerich, E.; Koross, R.; J, K.; Moi, Too (2018)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley

Mathematical modelling in teacher education: dealing with institutional constraints - Barquero, Berta; Bosch, Marianna; Romo, Avenilde (ZDM: The International Journal on Mathematics Education, 2018)
Considering the general problem of integrating mathematical modelling into current educational systems, this paper focuses on the "ecological dimension" of this problem--the institutional constraints that hinder the development of mathematical modelling as a normalised teaching activity--and the inevitable step of the professional development of teachers. Within the framework of the Anthropological Theory of the Didactic, this step is approached using the "study and research paths for teacher education" (SRP-TE), an inquiry-based process combining practical and theoretical questioning of school mathematical activities. We present a research study focusing on the design and analysis of an online and distance-learning course for in-service mathematics teachers based on the SRP-TE methodology. This course starts from the initial question of how to analyse, adapt and integrate a learning process related to mathematical modelling and how to sustain its long-term development. Our analysis is based on a case study consisting in four successive editions of a course for Latin American in-service mathematics teachers held at the Centre for Applied Research in Advanced Science and Technology in Mexico. The starting point is a modelling activity about forecasting the number of Facebook users, which includes functional modelling and regression. The results show how the course represents a valuable instrument to help teachers progress in the critical issue of identifying institutional constraints--most of them beyond the scope of action of teachers and students and not approached by previous research--hindering the integration of mathematical modelling in current secondary schools.
Keywords: Anthropological theory of the didactic; Barriers; Case Studies; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Ecological Factors; Ecology; Foreign Countries; Functions; Inservice Teacher Education; Institutional constraints; Instructional Design; Mathematical Models; Mathematical modelling; Mathematics Teachers; Mexico; Online Courses; Prediction; Regression (Statistics); Social Media; Study and research path; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2095891; __finaldtb

Understanding the Potential of Using EdTech to Measure and Mitigate Learning Losses in Latin America and the Caribbean - Wyss, Natalie; Myers, Christina (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and the Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in December 2021. The UNICEF team requested a resource that summarises what is known about the use of technology and other approaches to measure and mitigate learning losses related to Covid-19 impacts on education in the LAC region. This resource aims to support UNICEF country offices and partners in the LAC region to assess learning losses and inform school reopening and the development of hybrid education strategies. Our research found that there are limited EdTech approaches to measuring and mitigating learning losses, and fewer still that are specific to the LAC region. This piece outlines the following: What is understood about learning losses and how they can be quantified; What common guidance and evidence suggest are the most effective ways to mitigate Covid-19-specific learning losses; How established EdTech tools and non-tech-based approaches can be leveraged and applied to both processes. Keywords: learning losses; school reopening; personalised learning; assessment; remedial education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Experiment Types for EdTech - Rahman, Asad; Carter, Alice; WambûiKuria, Catherine; Mbugua, Ciku; Simpson, Lea; Kably, Nathan (EdTech Hub, 2022)
An EdTech Hub sandbox fast-tracks promising EdTech interventions by providing funding, tools, and access to evidence. It provides a space for partners to test and grow ideas in conditions of uncertainty. Since 2020, EdTech Hub has worked with partners in eight countries to test and grow EdTech based on our sandbox methodology. When testing and growing EdTech, this tool provides a non-exhaustive list of ways to design and run experiments. Keywords: sandbox; lean startup; lean impact; experiments; validation; prototype An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Teaching and Learning of Mathematics in the Context of the National Numeracy Programme in Malawi: Findings from a rapid in-depth qualitative study - Correa de Oliveira, André; Kanyoza, Charity; Smart, Theresa; Lurvink, Anne-Fleur; Boilo, Violet; Kadzamira, Esme; Haßler, Björn (EdTech Hub, 2024)
To inform the development of Malawi's National Numeracy Programme (NNP), EdTech Hub worked with the Directorate of Quality Assurance Services (Malawi), Cambridge Education, and the UK Foreign, Commonwealth and Development Office (FCDO) to examine the NNP’s components during its extended pilot phase during the 2022–2023 school year, and explore how these might be refined to improve teaching and learning of mathematics in Malawi. In-depth qualitative research in four schools was undertaken to obtain feedback on the programme’s components from teachers, head teachers, and Primary Education Advisors. The study’s methodology incorporated semi-structured interviews, focus group discussions, lesson observations, learning circle observations, training observations, and ethnographic methods. Additionally, a mathematics specialist conducted an independent, in-depth, desk-based review of the NNP teaching and learning resources to refine the study’s analysis. This report summarises the principal findings from the study. Keywords: Malawi, mathematics, numeracy, teacher continuous professional development, teacher learning circles An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

An Investigation into Implementation of ICT in Primary Schools, in Kenya, in the Light of Free Laptops at Primary One A Case Study of Teachers Implementing ICT into Their Teaching Practice - Tonui, Betty; Kerich, E; Koross, R (Journal of Education and Practice, 2016)
Information and communication technologies (ICTs) have been touted as being potentially powerful tools that can be used to facilitate the implied educational change and reform. Implementation of ICT in higher education learning environments is a complex task. Teachers and students, but also management, administration and ICT support are affected by and affect the implementation. To facilitate the change processes better the first step is to actually understand what problems and challenges implementation of ICT leads to and how it affects practice. Although classical instructional methods will continue to be used in the teaching-learning process, it is also true that Information Communication Technologies (ICTs) can be harnessed to become powerful pedagogical tools. Proceeding from the premise that there are many ways to use new technologies for teaching and learning, the paper presents literature on the possibilities and challenges of integrating ICT into teaching-learning, the rationale for adopting and using ICTs for learning-teaching, as well as the key factors that influence the adoption and use of ICTs in teaching and learning both from a general perspective and in a technical education context. The paper then outlines and discusses findings of a study designed to investigate the possibilities and challenges of using Information Communication Technology (ICT) in teaching-learning procedures in primary school institutions in Kenya using data obtained from a Tinderet District school in the Rift valley region of Kenya. It examines views in pertinent literature as well as teachers’ perceptions of the benefits of integrating ICT into teaching-learning, the success factors and obstacles encountered in their endeavours to do this. Conclusions are drawn and suggestions made to address the challenges and improve on the use of ICT for teaching-learning in teaching institutions.
Keywords: ⛔ No DOI found

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

The Effects of a Technology-Aided Learning Environment on the Improvement of a Primary Special Education School - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people's expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming '"learning" or "effective" schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers' functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed.
Keywords: Academic Achievement; Assistant Principals; Attitude Measures; Case Studies; Cooperation; Educational Innovation; Educational Technology; Elementary Education; Elementary School Teachers; Foreign Countries; Observation; Parents; Principals; Qualitative Research; School Personnel; Semi Structured Interviews; Special Education; Statistical Analysis; Teaching Methods; Technology Uses in Education; ___working_potential_duplicate

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Out-of-School Children and Youth in Southeast Asia: A Rapid Scoping Study - Afzal, Nimra; Barnes, Katrina; Hayat, Amal; Mazari, Haani; Jayasinghe, Neema; Sentillas, Emil (2024)
This rapid scoping study has been conducted by EdTech Hub and the Southeast Asian Ministers of Education Organization (SEAMEO) Secretariat through the ASEAN-UK Supporting the Advancement of Girls Education (ASEAN-UK SAGE) programme. Through the ASEAN-UK SAGE programme, secondary research has been conducted on the current situation of out-of-school children and youth (OOSCY) in Southeast Asia by Dabrowski et al. (2024) and Barnes et al. (2024). Building on these efforts, this study provides an updated and nuanced overview of the reasons for children and youth in the region being out of school and the policies and programmes that support them. The study used new primary data generated by surveys with education actors and interviews with OOSCY, their caregivers, and teachers, combined with a review of existing documentation. It is important to note that this study is deliberately high level, as it seeks to provide a snapshot of the OOSCY situation in the region as a whole. The findings should therefore be considered indicative rather than comprehensive, and deeper, country-specific profiling, analyses and targeted recommendations will be provided through forthcoming country case studies and thematic papers.

Empowered educators: how high-performing systems shape teaching quality around the world - Darling-Hammond, Linda (Jossey-Bass, 2017)
Keywords: Case studies; Education and state; Teachers; Training of

EdTech in Zimbabwe: A Rapid Scan - Dzinotyiweyi, Monica; Taddese, Abeba (EdTech Hub, 2020)
Keywords: C:Zimbabwe; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH

Behavioral Insights for Public Policy: Concepts and Cases - Ruggeri, Kai; Jarke, Hannes; Berkessel, Jana; Benzerga, Amel; Hlavova, Renata; Immonen, Johanna; Kunz, Marvin; Ojinaga Alfageme, Olatz; Paul, Alessandro; Plohl, Nejc; Prinz, Gerhard; Steinnes, Kamilla; et al. (2019)
https://www.routledge.com/Behavioral-Insights-for-Public-Policy-Concepts-and-Cases/Ruggeri/p/book/9781138484238 The first decades of the 21st century have offered a remarkable shift in how policies are made as well as who designs them. Until this period, advisory boards for local, regional, and national policy strategies largely comprised economists, lawyers, and financial experts. These panels made recommendations based on standing theory and, in some cases, subject-matter expertise, such as energy or healthcare. What has changed is how the behavioral sciences, largely psychology, have been embraced within these groups, thanks largely to extensive evidence from empirical research in how populations save, spend, eat, exercise, and work. While the application to policy may have contemporary versions, the behavioral side of economic theory itself is not new. Relevant insights on this go at least as far back as the 18th century with Daniel Bernoulli and Adam Smith, and continued steadily over the next two centuries with significant works from the likes of Wilhelm Wundt, Herbert Simon, and Roald Coase, among many others. However, how it came to be is perhaps more critical than merely who drove it. In each of these waves, a major shift in thinking was often preceded by empirical study that either attempted to explain how humans apply logic, or by surprising deviations from what appears to be rational. This textbook covers a range of topics from the origins of policy through to how recent advances in theory and practice have shifted our thinking on outcomes for society. Each section, including the fundamentals of behavioral sciences, policy development and evaluation, and all of the domains – economic, health, energy, education, workplace – cover examples of how behavioral insights are being used to address some of the most critical challenges we face. The cases and concepts presented in this book demonstrate the considerable value, both realized and potential, in studying as well as implementing behavioral insights into a variety of policy domains. We are still very much in the early days of this field, which means that these are merely fundamentals for educating and inspiring future generations of researchers, policymakers, and government leaders. As progress continues, how ultimate goals relevant to society are defined and targeted will become an increasingly important refrain amongst those involved in developing them. In these ways, we can consistently align our approaches with the most critical matters of local, national, and global communities: our safety, our stability, and our well-being.

Legislating gender and sexuality in Africa: Human rights, society, and the state - Boyd, Lydia; Burrill, Emily (University of Wisconsin Pres, 2020)
In recent decades, a more formalized and forceful shift has emerged in the legislative realm when it comes to gender and sexual justice in Africa. This rigorous, timely volume brings together leading and rising scholars across disciplines to evaluate these ideological struggles and reconsider the modern history of human rights on the continent. Broad in geographic coverage and topical in scope, chapters investigate such subjects as marriage legislation in Mali, family violence experienced by West African refugees, sex education in Uganda, and statutes criminalizing homosexuality in Senegal. These case studies highlight the nuances and contradictions in the varied ways key actors make arguments for or against rights. They also explore how individual countries draft and implement laws that attempt to address the underlying problems. Legislating Gender and Sexuality in Africa details how legal efforts in the continent can often be moralizing enterprises, illuminating how these processes are closely tied to notions of ethics, personhood, and citizenship. The contributors provide new appraisals of recent events, with fresh arguments about the relationships between local and global fights for rights. This interdisciplinary approach will appeal to scholars in African studies, anthropology, history, and gender studies.
Keywords: History / Africa / General; Political Science / Human Rights; Social Science / Gender Studies

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Review of international research on factors underlying teacher absenteeism - Lee, Mary; Goodman, Crystal; Dandapani, Nitara; Kekahio, Wendy (Regional Educational Laboratory Pacific, 2015)
Throughout the U.S.-affiliated Pacific Region, teacher absenteeism has posed a long-standing challenge. This report draws on research literature from international contexts and case studies to identify the underlying factors that may relate to teacher absenteeism. Resources included in this report were selected with a focus on non-U.S. Pacific entities and emerging economy contexts that might be most relevant to the U.S.-affiliated Pacific Islands. Different search parameters were used to determine the scope of U.S./international literature to include in the review. The report found five main themes to consider in relation to teacher absenteeism: pay structure (for example, direct or indirect working relationship with the school), management (for example, school governance), working conditions (for example, school culture or single- vs. multi-grade classroom structure), community conditions (for example, teachers' proximity to the school), and social and cultural responsibilities (for example, illness, funeral attendance, and care of family members). Predictors of absenteeism vary across place and context. Given the diversity of Pacific Region communities, stakeholders should examine the extent to which the context and results of the research in this review correspond to the social, structural, cultural, and environmental characteristics of their own contexts. The following are appended: (1) Data and methodology; and (2) Viewing absenteeism through an international lens. A list of selected literature on teacher absenteeism in the United States is also included.
Keywords: Academic Rank (Professional); Accountability; C:LMIC; Case Studies; Community Characteristics; Correlation; Cross Cultural Studies; Cultural Context; Cultural Influences; Elementary School Teachers; Family Work Relationship; Foreign Countries; LMICs; School Administration; School Culture; School Location; Social Influences; Teacher Attendance; Teacher Salaries; Teaching Conditions; Work Environment; ⛔ No DOI found

Review of International Research on Factors Underlying Teacher Absenteeism. - Lee, Mary; Goodman, Crystal; Dandapani, Nitara; Kekahio, Wendy (Regional Educational Laboratory Pacific, 2015)
Throughout the U.S.-affiliated Pacific Region, teacher absenteeism has posed a long-standing challenge. This report draws on research literature from international contexts and case studies to identify the underlying factors that may relate to teacher absenteeism. Resources included in this report were selected with a focus on non-U.S. Pacific entities and emerging economy contexts that might be most relevant to the U.S.-affiliated Pacific Islands. Different search parameters were used to determine the scope of U.S./international literature to include in the review. The report found five main themes to consider in relation to teacher absenteeism: pay structure (for example, direct or indirect working relationship with the school), management (for example, school governance), working conditions (for example, school culture or single- vs. multi-grade classroom structure), community conditions (for example, teachers' proximity to the school), and social and cultural responsibilities (for example, illness, funeral attendance, and care of family members). Predictors of absenteeism vary across place and context. Given the diversity of Pacific Region communities, stakeholders should examine the extent to which the context and results of the research in this review correspond to the social, structural, cultural, and environmental characteristics of their own contexts. The following are appended: (1) Data and methodology; and (2) Viewing absenteeism through an international lens. A list of selected literature on teacher absenteeism in the United States is also included.
Keywords: Academic Rank (Professional); Accountability; Case Studies; Community Characteristics; Correlation; Cross Cultural Studies; Cultural Context; Cultural Influences; Elementary School Teachers; Family Work Relationship; Foreign Countries; Institutional Characteristics; Predictor Variables; Proximity; Sanctions; School Administration; School Culture; School Location; Social Influences; Teacher Attendance; Teacher Salaries; Teaching Conditions; Work Environment

Digital Study Hall: Lighthouse Case Study - Dover, Mark (Global Solution Networks, 2013)

Stakeholder Analysis and Social Network Analysis in Natural Resource Management - Prell, Christina; Hubacek, Klaus; Reed, Mark (Society & Natural Resources, 2009)
The increasing use of stakeholder analysis in natural resource management reflects a growing recognition that stakeholders can and should influence environmental decision making. Stakeholder analysis can be used to avoid inflaming conflicts, ensure that the marginalization of certain groups is not reinforced, and fairly represent diverse interests. We present a case study from the Peak District National Park in the United Kingdom, where we used social network analysis to inform stakeholder analysis. This information helped us identify which individuals and categories of stakeholder played more central roles in the network and which were more peripheral. This information guided our next steps for stakeholder selection. The article ends with a discussion on the strengths and limitations of combining social network analysis with stakeholder analysis.
Keywords: participatory resource management; social network analysis; stakeholder analysis

Case Study: TEAM Girl Malawi - Link Education International (2021)

Case study: Team Girl Malawi - Link Education International (2021)

A Study on The Implementation of English Interactive Radio Instruction (IRI) in Selected Government Primary Schools in Addis Ababa - Alaro, Meseret (Addis Ababa University, 2007)
As its central objective, this study attempts to assess the implementation of English Interactive Radio Instruction (IRI) in selected government primary schools in Addis Ababa. In line with that, the researcher has framed specific questions that address issues related to classroom management, training given to the teachers, links among different stakeholders and the suitability and clarity of the program. Students and teachers of Grade Three from Biherawi Betemengist, Edget Besira , Karalo , Lafto and Salayish Primary Schools are participants of this study .To undertake the study descriptive research design is used . Accordingly, data that is pertinent to the study is collected using different tools such as questionnaire, observation, focus group discussion, interview and document analysis. The findings of the study reveal that the implementation of the program seems to face grave challenges. These mainly emanate from loose link among stakeholders, failure of supplying basic facilities needed to promote the fruitfulness of the program and failure to arrange suitable conditions for the broadcast. Moreover, based on the opinion of the participants, results of the study highlight that in some cases contents of the program is not suitable compared to the students language proficiency .It is also noticed from the findings of the study that classroom practice is not effectively carried out as per the very goal of the program. Despite that, both students and teachers forward positive comments about the utilization of the program for the teaching of English. Based on the findings recommendations for better service and suggestions for further studies are given.

Should we paint all classroom roofs white to improve learning in Tanzania? - Proctor, Jamie (2022)
A growing literature base has developed from Global North contexts, showing a clear link between classroom temperature and student learning outcomes. However, very little evidence shows how this impact translates to low- and middle-income countries (LMICs), where average classroom temperatures are often high. The hypothesis for the research was that classroom temperatures in Tanzania are high and that a white-paint-cool-roof intervention would help mitigate these high temperatures. This study includes a literature review to understand the classroom policy in Tanzania, establish links between temperature and learning, and assess temperature retrofit options. Following this, the study presents the results of an experiment to trial a white-paint cool roof against a blue-paint roof and an unpainted control roof. Finally, data analysis predicts the intervention effects over an entire year and the subsequent impact on learning outcomes. The learning outcomes analysis includes a cost-effectiveness analysis using the Learning-Adjusted Years of Schooling (LAYS) metric. Empirical evidence of temperatures inside classrooms in Dar Es Salaam suggests that the temperature often exceeds 40℃. Literature searches indicate that this is the first time classroom air temperatures have been recorded and published for East Africa. The experiment involved using a low-cost retrofit intervention to reduce temperature – by painting the classroom roof blue or white over eight days. Results showed that the White Paint Intervention (WPI) reduced the temperature by around 3.7℃ over the course of the school day and up to a maximum of 5℃. The WPI was roughly twice as effective as the Blue Paint Intervention at reducing interior air temperatures. The WPI results were then modelled to estimate the classroom temperature reduction over a year, based on the assumed 3.5℃ reduction. Finally, using estimates from the existing literature, the learning impact of the intervention was calculated. The results suggest that using the WPI intervention can improve learning by 7.1%, which translates to an estimated 3.2 LAYS per classroom per year, at a cost-effectiveness of 5.3 LAYS per USD100. The paper shows that the impact of high temperatures in classrooms is likely undermining the funding currently channelled to improve learning outcomes in the region. Further, a WPI retrofit intervention is effective at reducing classroom temperatures in Tanzania. Due to climate-change-induced temperature increases, the intervention effectiveness is likely to increase over the coming decades. This paper was submitted as a dissertation in fulfilment of an MSc in Sustainability and Adaptation in the Built Environment at the Centre for Alternative Technology, Machynlleth, Powys (Wales)
Keywords: _r:AddedByZotZen

Case Study Report: RET International Kenya - Boisvert, Kayla (University of Massachusetts Amherst, 2017)

Case study: Sisters for Sisters' Education - GEC (VSO, 2021)

Case Study: Sisters for Sisters’ Education - VSO (2021)

UNICEF Education COVID-19 Case Study - UNICEF Malaysia (2020)

Digital mismatch: Expectations and realities of digital competency amongst pre-service education students - Duncan-Howell, Jennifer (Australasian Journal of Educational Technology, 2012)
Pre-service education students entering university can be categorised broadly into two distinct groups, those who are coming directly from secondary school and those who are not. The second group can be quite diverse, ranging in age, academic and/or work experience. However, what both of these groups share is a digital expectation and they expect upon completion of their studies to be more digitally fluent than when they entered university, they expect to be taught via a range of digital technologies and they expect to use their digital skills throughout their personal and professional lives. These expectations have been either largely ignored or have failed to be understood by universities, resulting in a mismatch between student expectations and their experiences. However, the teaching staff within universities may be ill-prepared to meet these demands, either due to being non-users or exhibiting the same or lower levels of digital fluency as their students. The mismatch between student expectations and the reality is highlighted by an empirical case study involving undergraduate students enrolled in pre-service education degrees at an Australian university. The study will present clear evidence that students' digital expectancy should be considered when planning and improving learning environments.

Blog-based professional development of English teachers in Mumbai: the potential of innovative practice under scrutiny - Khan, Atiya (Australasian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.
Keywords: Action Research; Case Studies; Communities of Practice; Diaries; ERIC, Current Index to Journals in Education (CIJE); Electronic Publishing; English (Second Language); Faculty Development; Foreign Countries; India; Language Teachers; Participant Observation; Private Schools; Qualitative Research; Questionnaires; Reflective Teaching; Second Language Instruction; Semi Structured Interviews; Teacher Collaboration; Web Sites; Workshops; __:import:01; __:match:final; __:matched; __:study_id:2096053; __finaldtb

Tiblo: a tangible learning aid for children with dyslexia - Pandey, Sumit; Srivastava, Swati (Association for Computing Machinery, 2011)
Dyslexia is a learning disability, which affects the ability to read and spell correctly. Special schools for children with dyslexia focus on individual growth, learning and psychological difficulties faced by the child. In this paper, we describe the design, development and testing of Tiblo (Tangible Interactive BLOcks), a tangible learning aid for children with dyslexia in the age group of 8 to 12 years. Tiblo has been specifically designed keeping in mind the psychological and emotional effects of dyslexia. We explain the process and results of an ethnographic study conducted at a school for children with dyslexia; the resulting concept development and prototyping. Further, we outline the testing process with the students at the school and the results of the same. The results showed that the children have a greater engagement in their classroom activities and there is an improvement in their retention abilities on using Tiblo. Also, they had a very strong sense of attachment and ownership towards the blocks and like to personalize it. This was in sharp contrast with other digital learning aids which offer a symptomatic and subject specific approach to aiding children with dyslexia and hence do not develop a personal one to one relationship with the child.
Keywords: collaborative learning; design case study; dyslexia; emotional design; interaction design; learning aids; play and learn; tangible user interfaces

Disaster Management Preparedness in the Education Sector in Kenya – A Case of the COVID-19 Pandemic. - Ngari, Prof Fr Stephen Mbugua; Ndung’u, Stephen W. (Editon Consortium Journal of Educational Management and Leadership, 2020)
This study examined the disaster management preparedness in the education sector in Kenya, with a focus on the COVID-19 pandemic period. The study adopted destktop literature review for data collection. The collected data pertains e-learning in Kenya and in other countries during the time of  the novel coronavirus pandemic. Notably, the education sector, like in many other countries, seeks to actualise the Millennium Development Goals (MDGs) in line with the United Nations and the Education for All (EFA) movement lead by UNESCO (MacEwen, et al., 2011). Examples of these events are; accidents such as the one evident in Kakamega Primary School where the school closed for about two weeks (Daily Nation, 2020), attack by militia groups as was the case of Garissa University in 2015, intercommunity wars that lead to displacements, famine, and fires. These disasters and events, whenever they strike, have led to the closure of affected institutions of learning to pave the way for interventions. Garissa University is a leading example since it had to close for about nine months in 2015-2016 (BBC, 2016). In Kenya, disasters and other events disrupt the progress towards achieving MDGs and EFA time to time, and that was the inspiration for this study. The study concludes that disasters like nature patterns, militia groups, electricity faults, and those instigated by learners can derail learning in education and cause loss of lives. As such, online learning comes in handy to lessen such disasters. The possibility of such learning model has been tested and proved during COVID-19 pandemic and it has been successful in many institutions of higher learning and middle level colleges.
Keywords: COVID-19 Pandemic; Disaster Management; Education Sector; Preparedness

Making mobile learning work: case studies of practice - Traxler, J.; Wishart, J. (Discussions in education, 2011)

Realising Affordable Internet in Bangladesh: A Case Study - Shadrach, B. (Alliance for Affordable Internet A4AI, 2016)

Gender-Transformative Programming in UNICEF Selected Case Studies - Marcus, Rachel; Samuels, Fiona; Belachew, H; Jalal, S (2021)
Reflections and Lessons for UNICEF’s Gender Policy and Action Plan (2022-2025), A compendium of papers, Florence: UNICEF Innocenti Research Centre

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Technology in Education: A Case Study on Timor-Leste - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Centre for Quality Improvement for Teacher and Education Personnel in Science (UNESCO, 2023)

Technology in Education: A Case Study on Viet Nam - Le, Anh Vinh; Luong, Minh Phuong; Do, Duc Lan; Tran, My Ngoc; Bui, Thi Dien (Global Education Monitoring Report Team and Viet Nam National Institute of Educational Sciences, 2023)

Technology in Education: A Case Study on the Philippines - Espinosa, Allen A; Gomez, C Arsenia; Praksis, Miranda A; Adonis, David P; Edna Luz, Abuljon R; Hermosisima, Victoria C; Quinosa Jr, Edwin A; Soliman, Abegail A; De Vera, Jayson L; Claros, Ian Harvey; Cruz, Hardie Gieben; Gonzales, Nepthalie SJ (UNESCO, 2023)
Keywords: ⛔ No INSPIRE recid found

Empowering student learning through Tablet PCs: A case study - Li, Sandy C; Pow, Jacky WC; Wong, Emily ML; Fung, Alex CW (Education and Information Technologies, 2010)

Case Study: GEARR-ing Up for Success After School - PEAS (2021)

The iPad as a Tool For Education - a case study - Heinrich, P. (2012)

Investigations into using data to improve learning: Philippines case study - Read, Lindsay; Atinc, Tamar Manuelyan (Global Economy and Development at Brookings, 2017)

One Teacher Thailand: A case study of a teacher learning network - Thang, Sarah; Thinley, Sangay; Wiboonuppatum, Rangsun; Saihjee, Aarti; Khlaisang, Jintavee; Thammetar, Thapanee; Kaosaiyaporn, Ophat; Saiyasit, Pichsinee; Theeraroungchaisri, Natchapat (UNICEF and EdTechHub, 2025)
กรณีศึกษาเครือข่ายครู ประเทศไทย

A case study approach to exploring resilient pedagogy during times of crisis - Clum, Katie; Ebersole, Liz; Wicks, David; Shea, Munyi (Online Learning, 2022)

Technology in Education: A case study on Thailand – UNESCO Digital Library - Dipendra, K.C. (2023)
Keywords: ⛔ No INSPIRE recid found

Use of learning assessment data in the planning cycle. Case study – Ghana - Begue-Aguado, Alberto (United States Agency For International Development (USAID), 2021)

Teacher and problem in student with ADHD in Indonesia: A case study - Hapsari, Iriani Indri; Iskandarsyah, Aulia; Joefiani, Poeti; Siregar, Juke R. (The Qualitative Report, 2020)
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Digital literacy in Ugandan teacher education: Insights from a case study - Andema, Samuel; Kendrick, Maureen; Norton, Bonny (Reading & Writing-Journal of the Reading Association of South Africa, 2013)
Keywords: ⛔ No DOI found

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
Keywords: ___working_potential_duplicate

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
Keywords: ___working_potential_duplicate

Increasing Interactivity in Distance Educations: Case Studies Bangladesh and Sri Lanka - Andersson, Annika; Hatakka, Mathias (Information Technology for Development, 2010)

Synergies between the principles for digital development and four case studies - Haßler, Bjoern (REAL Centre, Faculty of Education, University of Cambridge, 2018)
Keywords: ___working_potential_duplicate

“Urban slum education”: a case study of children’s experience in Jakarta - Cho, InJung (Comparative International & Education Society (CIES), 2020)

Do No Harm teaching case study: Cité Soleil. Reference for workshop participants - Robillard, Sabina Carlson (CDA Collaborative Learning Projects, 2015)
Keywords: ⛔ No DOI found

Synergies Between the Principles for Digital Development and Four Case Studies - Haßler, Björn; Broadbent, E.; Cunningham, A.; Chimombo, J.; Jamil, B. R.; Kauthria, R.; Lake, L.; Rose, P.; Sarfraz, S.; Szekely, M. (Research for Equitable Access and Learning (REAL) Centre, Faculty of Education, University of Cambridge, 2018)

The future of language education in Europe: case studies of innovative practices - Le Pichon-Vorstman, Emmanuelle; Siarova, Hanna; Szőnyi, Eszter (European Journal of Language Policy, 2021)

Technology in education: a case study on Lao People's Democratic Republic - Nietschke, Yung; Dabrowski, Anna (2023)

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

WhatsApp supported language teacher development: A case study in the Zataari refugee camp - Motteram, Gary; Dawson, Susan; Al-Masri, Nazmi (Education and Information Technologies, 2020)

Monitoring basic skills acquisition through rapid learning assessments: A case study from Peru - Abadzi, Helen; Crouch, Luis; Echegaray, Marcela; Pasco, Consuelo; Sampe, Jessyca (PROSPECTS, 2005)

Barriers to the Use of Computer Assistive Technology among Students with Visual Impairment in Ghana: The Case of Akropong School for the Blind - Ampratwum, Joseph; Offei, Yaw Nyadu; Ntoaduro, Afua (Journal of Education and Practice, 2016)
The study aimed at exploring barriers to the use of computer assistive technology among students with visual impairment at Akropong School for the Blind. A case study design was adopted and the purposive sampling technique used to select 35 participants for the study. The researchers gathered qualitative data using an in-depth interview guide to investigate barriers to the use of keyboarding skills and Job Access with Speech (JAWS).Data were transcribed and analysed thematically. That is the key themes were identified in the conversations and these were drawn and discussed. This was done using both the narrative methods and opened quotes from interviews. The findings indicated that challenges limiting effective use of computer assistive technology in the School were more personal than external influences. This was because most of the challenges were due to the individual response to the training and familiarity in developing their competencies in using computer assistive technology. Based on this, it was recommended that efforts should be made to stock the laboratory with additional computers. Directly in line with the first recommendation, it was further suggested that more practice time should be created for the students to maximize computer use. Also, Licensed JAWS must be acquired by the school to advance students’ competence in using computer assistive technology. A number of the challenges were expressed by the students on their non- familiarity with the JAWS. As a result, it was recommended that instructors and trainers at the school should engage the students in revised lessons on introduction to computer. This will help to refresh the minds of students.
Keywords: ⛔ No DOI found

The Kenya Ministry of Education’s response to the COVID-19 pandemic: Case study - Gichuhi, Loise; Kallsta, Jane (UNESCO IIEP, 2022)

Teachers’ perspectives on their use of ICT in teaching and learning: A case study - Kafyulilo, Ayoub; Keengwe, Jared (Education and Information Technologies, 2014)
This article presents the perspectives of science and mathematics teachers on their use of information and communication technology (ICT) in teaching and learning in Tanzania. The findings show that few teachers used computers for teaching and learning purposes while majority of them used computers for administrative purposes. Additionally, teachers were found to have limited confidence in using technology to facilitate specific concepts or skills, to support creativity, and to support students to learn complex concepts. Therefore, it is suggested that schools explore strategies ICT integration strategies that focus more on making a shift from teaching technology or using technology for administrative purpose to appropriate pedagogical uses that could enhance student learning.

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)

Teachers’ perspectives on their use of ICT in teaching and learning: A case study - Kafyulilo, Ayoub; Keengwe, Jared (Education and Information Technologies, 2014)
This article presents the perspectives of science and mathematics teachers on their use of information and communication technology (ICT) in teaching and learning in Tanzania. The findings show that few teachers used computers for teaching and learning purposes while majority of them used computers for administrative purposes. Additionally, teachers were found to have limited confidence in using technology to facilitate specific concepts or skills, to support creativity, and to support students to learn complex concepts. Therefore, it is suggested that schools explore strategies ICT integration strategies that focus more on making a shift from teaching technology or using technology for administrative purpose to appropriate pedagogical uses that could enhance student learning.

Slum dwellers' response to free primary education: a case study of Kibera slum, Nairobi - Njeru, Caroline N. (University of Nairobi, 2010)

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology supported learning and pedagogy in times of crisis: The case of COVID-19 pandemic - Ahmed, Vian; Opoku, Alex (Education and Information Technologies, 2022)
Online teaching within disciplines such as Engineering require experiential learning that equip future graduates with highly intellectual and professional skills to meet the demands of employers and the industry. The outbreak of COVID-19 however, has shifted the academic community into new landscapes that require educators and students to adapt and manage their expectations. Although literature reports on research attempts to study the implications of Covid-19 on the Higher Education curricular, little has been reported on its impact on Engineering Education. This paper therefore uses the theory of Emergency Management Life Cycle (mitigation, preparedness, response, and recover) as a lens to examine the challenges faced by students and academics and coping mechanism during the COVID period. This study adopts a mixed method approach using a case study from the College of Engineering at a Higher Education Institution in the UAE due to the sudden migration to online teaching amid COVID-19. Data is collected through interviews and surveys with both students and instructors on challenges, strategies and online delivery good practices that enhanced students’ learning experience. The results show that, Technology Supported Learning tools are capable of enhancing students’ experiential learning and associated competencies, however there were a number of pedagogical, technological and psychological challenges that faced students and instructors as a result of the sudden migration online, which are likely to play a role in the impediment of the students’ learning cycle, due to the lack of preparedness in response to the state of emergency created by Covid-19. Despite these challenges, the study found that instructors with effective communication skills and teaching style, competent use of technology, flexible, friendly and supportive attitude towards teaching, played a positive role in mitigating for the lack of preparedness in response to sudden migration online. The study also reveals that by overcoming some of the technical challenges such as slow internet connection and interruptions, lessons learnt from the sudden migration to online delivery amid COVID-19, will help create new opportunities for the use of blended learning approaches to meet the needs of the on-going COVID and future online deliveries.

Implementation of Information and Communication Technologies (ICTs) in Education Course: A Case from Teacher Education Institutions in Pakistan - Majoka, Muhammad Iqbal; Fazal, Shawana; Khan, Muhammad Saeed (Bulletin of Education and Research, 2013)
This research was aimed to explore the implementation of Information and Communication Technologies (ICTs) in education in teacher training programs in the Khyber Pakthunkhwa and Punjab provinces in Pakistan. It was the first time that the course "ICTs in Education" was implemented for ADE/B. Ed (Elementary) programs in session 2010-11. In this situation, it was vital to explore how successfully this course was implemented in the pioneer institutions, so as to have baseline information for further improvement in the implementation process. This study was focused to explore: (i) How the course "ICTs in Education" was implemented? (ii) How did the teacher educators follow the course guide and to what extent the course guide was helpful in implementing this course? Seven teacher training institutions (three from the Punjab and four from KP provinces) were selected as target population. The total sample was 40 teacher educators and 200 students from seven institutions. Mixed method research design was adopted to conduct this study. The data was drawn from the surveys for heads and prospective teachers, and semi-structured interviews with teacher educators. Analysis revealed that only in a few classrooms, different activities/ experiences as suggested in the unit were properly implemented, while in most that was not the case due to issues such as shortage of electric power supply, scarcity of ICTs tools and lack of training and skills in ICTs application. The extent to which teachers followed the course guide was another factor contributing to the implementation process.
Keywords: Barriers; Energy; Foreign Countries; Guides; Information Technology; Program Implementation; Teacher Education Programs; Teacher Educators; ⛔ No DOI found

Strengthening education management information systems for increased resilience to crises: A synthesis of case studies - UNESCO (UNESCO, 2021)

Student acceptance of tablet devices in secondary education: A three-wave longitudinal cross-lagged case study - Courtois, Cédric; Montrieux, Hannelore; De Grove, Frederik; Raes, Annelies; De Marez, Lieven; Schellens, Tammy (Computers in Human Behavior, 2014)

iPad in education: A case study of iPad adoption and use in a primary school. - Henderson, S., & Yeow, J. (System Science (HICSS), 2012 45th Hawaii International Conference on, 2012)
Keywords: ⛔ No DOI found

Assessing the policy influence of research: A case study of governance research in Viet Nam - Pellini, Arnaldo; Anderson, James H; Tran, Huong Thi Lan; Irvine, Renwick (Overseas Development Institute, 2012)

Using Tactile Letters As An Assitive Techology in Teaching Alphabet For Dyslexi Children: A Case Study - Mohamad, Mariam; Tan, Abdullah; Sabrina, Jessica (eLearning & Software for Education, 2017)
Keywords: ⛔ No DOI found

Framework for Teacher Support During Remote Teaching in a Crisis: COVID-19, as a Case Study - Denden, Mouna; Tlili, Ahmed; Burgos, Daniel; Jemni, Mohamed; Huang, Ronghuai; Essalmi, Fathi; Chang, Ting-Wen (Radical Solutions for Education in a Crisis Context, 2021)

Sierra Leone Case Study: Review of Technology-Based Interventions to Address Child Marriage and Female Genital Mutilation - Data-Pop Alliance; United Nations Population Fund; UNICEF (2023)

Field-Based Models of Primary Teacher Training: Case Studies of Student Support Systems from Sub-Saharan Africa - Mattson, Elizabeth (Department for International Development, 2006)
Keywords: C:sub-Saharan Africa; ⛔ No DOI found

A Social Informatics Analysis of Refugee Mobile Phone Use: A Case Study of Zaaatari Syrian Refugee Camp - Maitland, Carleen; Xu, Ying (SSRN Electronic Journal, 2015)

Check my school: A case study on citizen's monitoring of the education sector in the Philippines - Shkabatur, Jennifer (World Bank Group, 2012)

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Effective Use of Assistive Technologies for Inclusive Education in Developing Countries: Issues and challenges from two case studies - Grönlund, Åke; Lim, Nena; Larsson, Hannu (International Journal of Education and Development using ICT, 2010)
Developing countries face many obstacles in the process of implementing inclusive education (IE). Effective use of assistive technologies (AT) can help governments in developing countries achieve inclusive education by helping children with disabilities in schools. Despite the importance and positive impact of AT, prior research on the use of AT in inclusive education especially in developing countries is limited. To fill the research gap in this area, this paper investigates the research question of, How can AT be effectively used for IE in developing countries? To address this question,...
Keywords: ⛔ No DOI found

Strengthening Education Management Information Systems (EMIS) and Data for Increased Resilience to Crisis: country case study: South Soudan - Mwaniki, David (UNESCO, 2021)
Keywords: auto_merged

Case Study: Building Girls to Live, Learn, Laugh and ‘SCHIP’ in Strong, Creative, Holistic, Inclusive, Protective, Quality Education - CRANE and Viva (2021)

An Investigation of Provision of Quality Basic Education in Ghana: A Case Study of Selected Schools in the Central Region - Ampiah, Joseph (Journal of International Cooperation in Education, 2008)
Keywords: ⛔ No DOI found

Empowering Teachers to Promote Inclusive Education. A case study of approaches to training and support for inclusive teacher practice - Donnelly, Verity (European Agency for Special Needs and Inclusive Education, 2015)

From Emergency Remote Teaching to Effective Online Learning: A Teacher Professional Development Case Study from Higher Education in India - Raina, Ashutosh; Rane, Archana; Ngeze, Lucian; Murthy, Sahana; Iyer, Sridhar (Global Perspectives on Educational Innovations for Emergency Situations, 2022)
This chapter describes the design and implementation of an educational solution to prepare teachers and instructors in India for various pedagogical and technological transitions during the pandemic. The goal was to move from an emergency remote teaching approach towards adopting effective online teaching strategies. This solution had to address the key challenge of remote professional development for the online medium while accounting for the diversity in the Indian educational context, taking into account varying needs of learners, teachers, institutions, geography, availability of technology, prior experience, and goals. The solution had two parts: i) a web-based repository for self-learning, consisting of research-based principles, pedagogical strategies and tools for effective design and development of online courses, and ii) synchronous interactive workshops to support instructors in practical implementation of the principles, strategies and tools to make domain specific instruction design decisions. Overall, emphasis was paid to learner engagement, diverse learner needs, peer learning, providing effective feedback and meaningful interaction. The resource repository and workshops guided instructors through making decisions and evaluating trade-offs in their context. This article also provides a brief analysis of the data collected from workshops on teachers’ preparedness at effective integration of technology, and the impact of the OTeach resource repository, which can found at Google Sites and has 25,000+ visitors so far. The article concludes with reflections and recommendations based on our experience.
Keywords: Effective online learning; Higher education; Research-based strategies; Teacher professional development

Strengthening Education Management Information Systems (EMIS) and Data for Increased Resilience to Crisis: country case study: Uganda - UNESCO Digital Library - Sparkes, James (UNESCO, 2021)

A case study of the One Laptop per Child Project in Rwanda: Exploring the socio-cultural dimensions of delivery and implementation. - Girgis, R. (University of Cambridge, Cambridge, UK., 2015)

Is 2020 a lost academic year? The impact of COVID-19 on education in eastern Africa: a case study of Kenya - Cordeiro, Vanessa Cezarita (Humanium, 2020)
Despite national efforts and strict measures designed to curb the spread of the virus, the country continues to suffer from the knock-on effects of the pandemic.

Leveraging Community and Government Resources for Gender and Educational Equity in India: A Case Study of Educate Girls | Educate a Child (educate a child, 2019)

Bridging between research and practice: Supporting professional development through collaborative studies of classroom teaching with technology - Hennessy, Sara (Sense Publishers, 2014)
This book presents a fresh approach to bridging the perceived gap between academic and classroom cultures. It describes a unique form of research partnership whereby Cambridge University academics and school teachers together grappled with and reformulated theory – through in-depth case studies analysing practice using interactive whiteboards in five subject areas. The inquiry exploited the collaborators’ complementary professional knowledge bases. Teachers’ voices are particularly audible in co-authored case study chapters. Outcomes included deeper insights into concepts of sociocultural learning theory and classroom dialogue, more analytical mindsets, sustained new practices and ways of working collegially. The book reflects upon the power of lesson video review and details how the co-inquirers negotiated “intermediate theory” – bridging educational theory and specific settings – framed in mutually accessible language and embodied in interactive multimedia resources for teacher development. These include video clips, analytic commentary from multiple perspectives, lesson materials, plus optional prompts for reflection and critique – not models of “best practice”. The resources make pedagogy explicit and vividly illustrate the book’s ideas, offering theory-informed yet practical tools designed with and for practitioners. Hennessy and colleagues have tested a model of ongoing, teacher-led development and innovation, professional dialogue and classroom trialing stimulated by discussing selected multimedia resources. The book will interest academic and teacher researchers, initial teacher educators, professional development leaders, mentors, plus practitioners interested in using interactive whiteboards and dialogic teaching. It explores widening approaches to collegial development to reach educators working in other contexts (with and without technology). This could involve intermediate theory building or shortcutting by sharing and adapting the outcomes – springboarding teachers’ further critique and professional learning. “I cannot recommend this book too highly … it weaves a complex developmental story with a range of facets. It emphasises clearly the rigour of the research that was conducted, while demonstrating the complexity of the inter-relationships, practices and issues for both teachers and researchers in developing practical and theoretical knowledge. Its graphic insights through text and associated media provide exemplars for teachers and those who work with teachers as a rich resource. It shows us all what can be achieved and the means of achieving it.” Prof. Barbara Jaworski, University of Loughborough

Fuzzy Boundaries Between Post-Disaster Phases: The Case of L’Aquila, Italy - Contreras, Diana (International Journal of Disaster Risk Science, 2016)
A number of indices have been developed for measuring vulnerability to disasters, but little attention has been paid to recovery indices. Post-disaster periods are usually divided into four phases. The terms established by the United Nations Development Programme for post-disaster phases—relief, early recovery, recovery, and development—are used in this article. This research examines the hypothesis that the boundaries between post-disaster recovery phases are fuzzy and should be defined by the progress achieved in the recovery process, rather than by the amount of time elapsed since the event. The methodology employed involved four steps: fieldwork, mapping, identification of indicators, and assessment. The case study area was the city of L’Aquila in the Abruzzo region of central Italy, which was struck by an earthquake in April 2009. For each phase of the recovery process in L’Aquila a score was calculated based on the progress observed in 2016, 7 years after the earthquake. The highest score went to the early recovery phase (14 points), followed by the recovery phase (13 points), the development phase (12 points), and the relief phase (4 points). The results demonstrate the possibility of defining post-disaster recovery phases in an affected area based on measuring achievements through indicators rather than defining recovery phases in terms of elapsed time after a disaster.
Keywords: Disaster recovery; Earthquakes; Geographical information system (GIS); L’Aquila; Post-disaster phases; Spatial indicators

Reciprocity among Farmers in Farming System Research: Application of Social Network Analysis - Jana, Rabindranath; Bandyopadhyay, Suraj; Choudhuri, Anil K. (Journal of Human Ecology, 2013)
In course of agricultural activities, farmers interact among themselves to fulfill different kinds of needs, such as getting advice regarding cultivation, obtaining appropriate seeds and plants, getting tools and implements, etc. On the basis of data to whom a farmer sends requests for such help and whether the farmer receives the required help, one can build a social network of help, whether simple or weighted, in agricultural production. The paper intends to study variation in measures of reciprocity among the farmers of the two villages in respect of different activities for agricultural production. For the study, two villages Madhya-Uttar and Astabari consisting of 88 and 79 households respectively were selected from unirrigated, rainfed area in the south-eastern region of the district of East Medinipur of West Bengal. To collect the required data, open-ended check lists were employed. A standardized graph theoretic measure (s3-measure) of reciprocity was applied to carry out social network analysis. In both the villages, values of reciprocity measures for seeds/plants and tools/implements exchange were more than that for advice giving; the measure for the network of agricultural activities as a whole was also greater than the network for social aspects. In case of all networks, values of s3-measure for the village Madhya-Uttar were much higher than Astabari. It indicates that the farming households of a network having greater value of s3-measure are more inter-dependent among themselves in agricultural production.
Keywords: In-degree; Out-degree; Reciprocal Pair; Simple and Weighted Social Networks; s3-measure

Situation analysis on the effects of and responses to COVID-19 on the Education Sector in Asia: Bhutan case study - UNESCO Digital Library - UNESCO (2021)

Online tools supporting the conduct and reporting of systematic reviews and systematic maps: a case study on CADIMA and review of existing tools - Kohl, Christian; McIntosh, Emma J.; Unger, Stefan; Haddaway, Neal R.; Kecke, Steffen; Schiemann, Joachim; Wilhelm, Ralf (Environmental Evidence, 2018)
Systematic reviews and systematic maps represent powerful tools to identify, collect, evaluate and summarise primary research pertinent to a specific research question or topic in a highly standardised and reproducible manner. Even though they are seen as the “gold standard” when synthesising primary research, systematic reviews and maps are typically resource-intensive and complex activities. Thus, managing the conduct and reporting of such reviews can become a time consuming and challenging task. This paper introduces the open access online tool CADIMA, which was developed through a collaboration between the Julius Kühn-Institut and the Collaboration for Environmental Evidence, in order to increase the efficiency of the evidence synthesis process and facilitate reporting of all activities to maximise methodological rigour. Furthermore, we analyse how CADIMA compares with other available tools by providing a comprehensive summary of existing software designed for the purposes of systematic review management. We show that CADIMA is the only available open access tool that is designed to: (1) assist throughout the systematic review/map process; (2) be suited to reviews broader than medical sciences; (3) allow for offline data extraction; and, (4) support working as a review team.
Keywords: Evidence synthesis; Managing systems; Rapid review; Review management; Systematic review software; Text mining; Time management; _Added-ailr-2024

The politics of education in post-colonies: Kreyòl in Haiti as a case study of language as technology for power and liberation - DeGraff, Michel (Journal of Postcolonial linguistics, 2020)
In this contribution, I would like to share some key aspects of my theoretical and applied linguistic agenda in Haiti. This agenda promotes a social vision where linguistics is coupled with digital technology in Haitian Creole (“Kreyòl”) in order to improve research and education toward sustainable development and equal opportunity for all. This agenda also aims at a model for other communities in the Global South where linguistic discrimination has disenfranchised large segments of the population most in need of socio-economic progress. This article will highlight the MIT-Haiti Initiative, whose initial objectives were for improving Science, Technology, Engineering & Mathematics (STEM) education in high schools and universities in Haiti. In collaboration with a broad range of academic institutions in Haiti and beyond, this Initiative has been exploring the strategic use of digital tools in Kreyòl to improve Haitian students’ active learning of STEM, across social classes and beyond any linguistic barrier. More recently, the Initiative has expanded its scope to cover all disciplines at all levels via crowdsourcing, co-creating, curating and sharing of educational materials in Kreyòl. The ultimate goal is to make high-quality education accessible to the greatest numbers of students throughout Haiti, while strengthening the foundations of Haiti’s linguistic and cultural identity and while promoting respect of the human rights of all Haitians. I will consider two important implications of the MIT-Haiti Initiative: for linguistics and for policies related to education writ large, including education that can truly benefit all in Haiti, especially those who speak Kreyòl only (i.e., the vast majority of Haitians). Firstly, Kreyòl is comparable to so called “international” languages, such as English, French, Spanish, Arabic, Chinese, etc., in terms of its development, structures and expressive capacity. Indeed, the success of this Initiative to date doubles as proof of concept that Kreyòl is a full-fledged language with unlimited capacity to express any level of complex thought as in STEM. Secondly, Kreyòl is an essential tool for the education, socio-economic progress and human rights of Haitians, especially in these communities that have long been impoverished through exclusion and injustice. These processes of impoverishment, which started four centuries ago when Haiti was a French colony (then the “richest” colony in the Americas), have been unrelentless throughout Haiti’s history. Language and education are two main vectors for the entrenchment of these processes of exclusion and impoverishment in Haiti. In my view, it is through the innovative, strategic and systematic use of Kreyòl, in conjunction with interactive pedagogy and modern technology, that Haitian students can optimally develop their capacity for acquiring and building additional knowledge in STEM, in the Humanities and Social Sciences, and in second languages such as French, English, Spanish, etc. More generally, it is through Kreyòl as language of instruction and as the language of discourse in every social context that all Haitians can realize their full potential toward joyful and dignified citizenship—and leave behind the trauma of linguistic apartheid that has characterized the history of Haiti since its creation in 1804.
Keywords: ⛔ No DOI found

No Teacher is an Island: A case study on the enablers and barriers for effective school-based teacher professional development in Sierra Leone - Lurvink, Anne-Fleur; Bangura, Zainab; Fortune, Alhaji; George, Alex H.; Godwin, Katie; Mason-Sesay, Miriam; Moseray, David; Tholley, Ibrahim; Turay, Emmanuel B.; Haßler, Björn; Open Development & Education (OpenDevEd, 2022)

Endogenous development in Lao PDR in the era of globalization: Contrastive case studies of external assistance for a sustainable rural development path - Vongxay, Phonemany; Suzuki, Noriyuki (Journal of Mekong Societies, 2021)
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

Enhancing social inclusion through innovative mobile learning in Uruguay: case study by the UNESCO-Fazheng project on best practices in mobile learning - UNESCO Biblioteca Digital - UNESCO (2018)

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

An evaluation of the effectiveness of computer assisted learning strategy and expository method of teaching biology: a case study of lumen Christi international high school, Uromi, Nigeria - Imhanlahimi, E. O.; Imhanlahimi, R. E. (Journal of Social Sciences, 2008)

Teachers’ conception towards the use of social networks as a tool for professional development in Tanzania government secondary schools: the case of Dodoma municipality - Manyama, Charles (University of Dodoma, 2017)
The current study sought to assess teachers' conception toward the use of social networks as a tool for professional development in Tanzania government secondary schools the case of Dodoma Municipality. Thus, the specific objectives of this study were to assess the influence of demographic characteristics on the use of social networks or as a tool for professional development. To assess teachers conception on the available social networks opportunity that can support professional development, to investigate teachers use of social networks available for professional development, to explore the perceived benefits of using social networks opportunity as a tool for professional development and to examine limitation that hinder teachers for professional development. The study was guided by social-cognitive theory, community of practice model (CoP) and technology acceptance model (TAM). A cross-section research design was used to collect data that involved 84 teachers‟ from ten secondary schools, six head of schools three quality assurers and one respondent from DEO office. SPSS computer program was used to analyze the data. Qualitative data were analyzes through content analysis and quantitative data were analyzed statistically using descriptive and inferential statistics by using SPSS Version 20, and Microsoft Excel were highly used. Linear regression techniques were used to seek whether there is a relationship between demographic characteristics and the use of social networks. The survey results showed that there is no significant relationship between demographic factors with the use of social networks as a tool for professional development. Either teachers have positive conceptions towards the use of social networks as a tool for professional development. Furthermore, teachers use SNs for communicating with their fellow from different groups but it is not effectively integrated into professional development. The findings indicate that, to a large extent, teachers agreed that SNs make them to be more creative and help them to improve their communication skills. In addition the findings indicated that teachers lack training on how to integrate SNs in TPD. Finally,the researcher recommend that, educational stakeholders should provide financial and material support to teachers in order to overcome challenge that limit the use of technology in teaching and learning.
Keywords: ⛔ No DOI found

National Policies that Connect ICT-Based Education Reform to Economic and Social Development - Kozma, Robert B. (Human Technology: An Interdisciplinary Journal on Humans in ICT Environments, 2005)
Information and communication technology (ICT) is a principal driver of economic development and social change, worldwide. In many countries, the need for economic and social development is used to justify investments in educational reform and in educational ICT. Yet the connections between national development goals and ICT-based education reform are often more rhetorical than programmatic. This paper identifies the factors that influence economic growth and shows how they supported economic and social development in three national case studies: Singapore, Finland, and Egypt. It describes a systemic framework of growth factors and types of development that can be used to analyze national policies and connect ICT-based education reform to national economic and social development goals. And it discusses how the coordination of policies within and across ministries can support a nation’s efforts to improve economic and social conditions. The paper highlights special concerns and challenges of developing countries.

Nudges to Improve Learning and Gender Parity: Preliminary findings on supporting parent-child educational engagement during Covid-19 using mobile phones - Aurino, Elisabetta; Tsinigo, Edward; Wolf, Sharon (EdTech Hub, 2022)
Key words: parental education engagement; caregiver engagement; nudges; text messages; schooling; learning; Ghana; gender In this study we evaluate a digital intervention to improve low-literate caregivers’ engagement with their children’s education and development in rural Ghana during the Covid-19 pandemic. The programme was a text-message-based behavioural change intervention for parents / caregivers that aimed to improve caregiver engagement in children’s educational activities, caregiver beliefs about returns to education, as well as children’s learning, enrollment, attendance, and gender parity in education. This household-randomised trial, conducted in the North East, Northern, Savannah, Upper East, and Upper West regions of Ghana, tested four variations of the intervention, varying both duration and a gender-parity focus. Households were randomised to one of five conditions: (i) regular behavioural nudges, 12 weeks; (ii) gender-boost behavioural nudges, 12 weeks; (iii) regular behavioural nudges, 24 weeks; (ii) gender-boost behavioural-nudges, 24 weeks; or (v) control. The interventions were implemented from January to April 2021 (for the 12-week groups) and January to June 2021 (for the 24-week groups). We collected data at midline (April–June 2021) and endline (August–September 2021). Our preliminary results suggest that a short, light-touch, SMS-based intervention can change caregiver behaviours and child outcomes in a rural, low-literate sample. However, the results were complex and intervention effectiveness depended on the caregiver having minimum levels of schooling. For caregivers with no education (65% of the sample), the intervention only increased caregiver expectations on reaching the desired level of education, especially among girls, but reduced educational engagement and some measures of children’s school enrollment and attendance. Educational engagement among Ghanaian caregivers is low relative to peer countries (Bornstein & Putnick, 2012; McCoy et al., 2018). The findings suggest that caregivers may need a base level of capital and resource (e.g., exposure to formal education) to enact the messages and increase their educational engagement with their children. Without this base level of capital, messages may increase caregivers’ aspirations for their children without providing enough support to change educational investments in positive ways. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The political economy of bad data: Evidence from African survey and administrative statistics - Sandefur, Justin; Glassman, Amanda (The Journal of Development Studies, 2015)
Across multiple African countries, discrepancies between administrative data and independent household surveys suggest official statistics systematically exaggerate development progress. We provide evidence for two distinct explanations of these discrepancies. First, governments misreport to foreign donors, as in the case of a results-based aid programme rewarding reported vaccination rates. Second, national governments are themselves misled by frontline service providers, as in the case of primary education, where official enrolment numbers diverged from survey estimates after funding shifted from user fees to per pupil government grants. Both syndromes highlight the need for incentive compatibility between data systems and funding rules.

Technology-Supported Personalised Learning: A Rapid Evidence Review - Major, Louis; Francis, Gill A. (EdTech Hub, 2020)
This publication is one part of a series of rapid evidence reviews that has been produced by the EdTech Hub. The purpose of the rapid evidence reviews is to provide education decision-makers with accessible evidence-based summaries of good practice in specific areas of EdTech. They are focused on topics which are particularly relevant in the context of widespread global challenges to formal schooling as a result of COVID-19. All the rapid evidence reviews are available at edtechhub.org.
Keywords: F: Evidence review; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Education, poverty and "purity" in the context of adolescent girls' secondary school retention and dropout: A qualitative study from Karnataka, southern India - Ramanaik, Satyanarayana; Collumbien, Martine; Prakash, Ravi; Howard-Merrill, Lottie; Thalinja, Raghavendra; Javalkar, Prakash; Murthy, Srikanta; Cislaghi, Ben; Beattie, Tara; Isac, Shajy; Moses, Stephen; Heise, Lori; et al. (PLoS ONE, 2018)
Background Gender-related norms and poverty remain important structural barriers to secondary school attendance among adolescent girls in southern India. We analyse how gender norms interact with family deprivation and dynamics to result in girls dropping out of school; we identify the main facilitators of school retention and changes to gender socialisation. Methods Longitudinal qualitative case studies with 36 girls were nested within a cluster randomized trial to evaluate the Samata intervention targeting adolescent girls in Bagalkote and Vijayapura districts in northern Karnataka. We used two rounds of in-depth interviews, conducted in 2014 at a time when respondents were in 8th standard at the age of 13 to 14 and sixteen months later. We combined thematic and narrative analyses. Results Our study found that poverty and socioeconomic realities at the household level strongly affect conformity with discriminatory gender practices such as restricting girls’ mobility. The value placed on education by parents clearly differentiates the regular school goers from those frequently absent and others who dropped out. With active encouragement of the girls’ educational and career aspirations, parents engendered the girl’s agency to communicate openly both at home and at school, allowing subtle changes to gender performance while resisting the pressure of social sanctions. In contrast, where educational aspirations were weak, parents invested more intensely in enforcing correct performance of gender, prioritising her well-being by aiming to secure her future in a good marriage. Among poorer families, girls’ domestic duties came at the cost of schooling with concerns about protecting her sexual purity predominating. Conclusions In contexts where a strong gender ideology of virginity before marriage rules, subtle shifts in harmful gender practices are possible. Interventions aiming to improve education need to target the most deprived families, focussing on trust building through open communication.

Early Childhood Longitudinal Study, Kindergarten Class of 1998–99 (ECLS) correct theta scores for the kindergarten through eighth grade data collections errata - Chapman, Chris (National Center for Education Statistics, 2010)
Find information about and locate all publications and data products on education information from the National Center for Education Statistics--NCES--. In most cases you may also browse the content of publications or download data files.

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AUDIOVISUAL aids in education; AUDIOVISUAL materials; CRITICAL thinking studies; DATA analysis software; DESCRIPTIVE statistics; EDUCATION; FOCUS groups; INTERVIEWING; PROFESSIONAL education; PROFESSIONAL employee training; REFLECTION (Philosophy); RESEARCH funding; Reflective practice; SCHOOL administrators; TEACHER training; TEACHING; THEMATIC analysis; VIETNAM; Vietnam; __:import:01; __:match:final; __:matched; __:study_id:2099873; __finaldtb; critical reflection; professional learning; teacher professional development; vide-flection

Guidance on Community Mobilisation for Girls’ Education - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Real girls, real lives, connected: A global study of girls’ access and usage of mobile, told through 3000 voices. - Vodafone Foundation (Vodafone Foundation, 2018)

Teacher Motivation: Exploring non-financial incentives in school-based teacher professional development in Tanzania - Anonymised for Peer Review (EdTech Hub, 2025)
High-income countries often use external incentives such as remuneration, professional pathways or accreditation to motivate teachers to engage in professional development. This paper reflects on the challenges of engaging teachers in school-based professional development in resource-scarce education environments where the use of such incentives is not feasible and explores practical strategies to motivate their engagement. In such contexts, where qualified teacher status and promotion are not tied to engagement in professional development, other means for encouraging teachers to take up professional learning opportunities are paramount. In this two-year, iterative, design-based implementation research study of a national teacher professional development initiative in Tanzania, non-financial incentives were tested in eight rural schools. Findings show that completion certificates motivated teachers; achievement certificates had mixed results due to doubt around the fairness of the peer-review process. Additionally, teachers were intrinsically motivated by other changes in the programme such as access to relevant digital modules which allowed for teacher agency, and by increased collegial relationships and collaboration. Keywords: teacher motivation; school-based teacher professional development; design-based implementation research; Tanzania, non-financial incentives; intrinsic and extrinsic motivation An output of the EdTech Hub, https://edtechhub.org/
Keywords: Hide; _r:AddedByMyEducationEvidence

Value chain, stakeholders analysis and technology: A holistic and integrated approach for determining the cumulative added value of education - Khudair, Saud Abdullah Ben; Abdalla, Abdalla Khidir (International Journal of Educational Administration and Policy Studies, 2016)
Keywords: ⚠️ Invalid DOI

Computer aided instruction for out-of-school children in India: An impact study in Andhra Pradesh - Karnati, Romilla (University of Pennsylvania, 2008)
India has the largest number of out-of-school children, the majority of whom are girls. Against this backdrop, the Bridges to the Future Initiative (BFI), a computer-aided instruction (CAI) intervention was launched in Andhra Pradesh to bring children back to school. The BFI used multimedia software to teach basic literacy and numeracy skills through interactive stories and activities, in the local language Telugu. The methodology employed in the study was a quasi experimental design on a sample of around 140 children (age range 7-19 years). The research study included BFI sites which offered two hours of CAI a day and comparison sites which provided five hours of teacher-based instruction (TBI) a day. According to several socio-economic indicators on the survey, the sample came from poor families with low literacy levels. Findings from the survey indicated that these out-of-school children had a positive attitude toward education and a favorable perception of educated people. A majority of the sample dropped out of school to assist with domestic tasks or family run businesses and did not earn wages. The impact analysis indicated that learning took place in both contexts and learners achieved similar learning gains between pretest and posttest. However, learners in the BFI intervention were learning at a faster pace per hour than learners in the comparison sites. Learners in the CAI intervention achieved similar gains as learners in the TBI intervention in one-third of the instruction time. As such, there is a strong case to be made for the BFI program being more efficient in raising levels of literacy and numeracy scores. Within the BFI intervention group, there was evidence to suggest that the number of days attended resulted in an increase in posttest scores, particularly in reading. Furthermore, older students in the BFI intervention had consistently shown higher gains in learning across reading, writing, math and information and communication technology (ICT) literacy domains. Finally, girls in the BFI sample outperformed the boys and the biggest difference in test scores was seen in Math. The impact of the BFI intervention could also be documented by the fact that approximately 45% of the BFI sample returned to school in the next academic year. In sum, this research was one of the first to explore the context of out-of-school children in poor communities and the use of CAI in Telugu (local language) to bring these learners back to school. The results support the use of ICT with marginalized sections of society in developing countries in order to improve literacy skills. The findings of this study have the potential to inform policy makers on educational and gender equity issues.
Keywords: Bridges to the Future Initiative; Computer-aided instruction; Education; India; Information and communication technologies; Information and communication technology (ICT); Literacy; Out-of-school children; School dropouts

Outputs Register: The Impact of GIS-Supported Teacher Allocation in Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman; Frazer, Madleen Madina (EdTech Hub, 2023)
EdTech Hub, Fab Inc, and the Education Workforce Initiative have produced the outputs listed in this document as part of the EdTech Hub-commissioned research project on ‘GIS-supported teacher allocation in Sierra Leone’. This research project began in January 2022. This document lists all outputs produced under this project. All outputs are available to the public via the EdTech Hub Evidence Library. An output of the EdTech Hub, https://edtechhub.org
Keywords: Author:OpenDevEd; HLR3; _C:Sierra Leone SLE; _r:AddedByZotZen

How India responded: distance learning in the time of COVID-19 (EdTech Hub, 2020)
As schools began to close earlier in the year, at the EdTech Hub we started to look at how governments pivoted to distance learning, with a number of country case studies exploring this shift. While the full case studies will be released soon, this blog gives an overview of the first of these into India’s response. The onset of COVID-19…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
Keywords: _r:AddedByZotZen

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Girls' Education: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; D'Rozario, Jonny; Thinley, Sangay; Mazari, Haani; Hinks, Jessica (EdTech Hub, 2025)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for girls in Southeast Asia. The review summarises how EdTech is currently being used with girls in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech for girls' education. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for girls, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for girls. An output of the EdTech Hub, https://edtechhub.org/

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Guidance Note 7 Ensuring resilient connectivity From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

School-based teachers’ professional development through technology-enhanced learning in Bangladesh - Shohel, M. Mahruf C.; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers’ teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers’ professional development. Using the case of a pre-pilot intervention in the Underprivileged Children’s Educational Programs schools, it explores the teachers’ professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers’ professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: AUDIOVISUAL education; BANGLADESH; Bangladesh; COMPUTER assisted instruction; ENGLISH language -- Study & teaching -- Foreign speakers; Education--Teaching Methods And Curriculum; Educational technology; LANGUAGE teachers; Learning; PROFESSIONAL education; Professional development; SECONDARY school teachers; TEACHER development; TEACHERS -- Attitudes; Teacher education; UCEP-Bangladesh; __:import:01; __:match:final; __:matched; __:study_id:2099954; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; teachers’ professional development; technology-enhanced learning

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Situation Analysis on the Effects of and Responses to COVID-19 on the Education Sector in Asia - UNICEF & UNESCO (2021)
Case Study from Pakistan

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Transforming education for girls in Tanzania and Nigeria: Cross country analysis of endline research studies - Unterhalter, Elaine; Heslop, Jo (ActionAid, 2012)
This cross country summary of the findings from the endline study conducted for the TEGINT project highlights a number of issues of particular pertinence to the community of policy makers, practitioners, and researchers concerned with gender equality, rights and girls’ education. Firstly, the considerable expansion of education provision at primary and junior secondary levels enhances girls’ enrolment, attendance, progression, attainment and empowerment. However, there are regional and locational differences, and the effects of the emergence of private schools on gender equality and girls’ empowerment merits careful scrutiny. It is a matter of concern, that despite the introduction of free primary education, schools continue to charge levies and that the costs of improving education are being passed down to the poorest. Secondly, there are clear indications that girls’ clubs give an important space for girls to learn about their rights and confidence to articulate solutions to their problems. This is the case both when girls in clubs come from higher performing girls in terms of class position and more marginalised girls. Thus girls clubs, widely used in many projects throughout Africa, but not till now well evaluated, appear an important strategy to continue to support. Thirdly, rurality appears as a particular condition of marginalisation, associated with higher levels of gender inequality. This is evident from the lower levels of girls’ empowerment in rural schools, and differences in articulating solutions. Thus particularly engaged interventions are needed with girls in remote areas to support empowerment. Fourthly, while improving teacher qualifications and engagement with gender equality is a necessary condition for enhancing education rights for all children, this is not a standalone intervention, and needs to be supported by other initiatives, possibly associated with teachers’ pay, work conditions and status. Fifthly, an intervention like TEGINT, appears particularly useful in helping to break the silence around gender based violence, however, such an intervention cannot be seen in isolation from work on other aspects of gender inequalities, poverty, and limited social provision. In a country like Tanzania, where there is more legislation and political action around gender equality than in Nigeria, girls, even the poorest, appear more knowledgeable about rights. Gender equality and girls’ education cannot thus be separated from other initiatives on rights, social development and addressing injustice.

Leadership Roles in Managing Education in Crises: The Case of Kenya During Covid-19 Pandemic - Mbogo, Rosemary Wahu (2020)
Covid-19, a disease caused by a novel coronavirus (SARS-CoV-2) was first reported in Wuhan, China, in December 2019 and in Kenya in March 2020. In Kenya, the Covid-19 pandemic has brought to light some unknown talents among the stakeholders at different levels. The economic sector has had manufacturing potential for goods, and from mass media reports, this has been demonstrated through production of Personal Protective Equipment (PPEs), ventilators and innovations in technology in the creation of apps such as the Linda App for contact tracing and Gumzo, a video conferencing app. Similarly, the education sector has also demonstrated potential for adaptation in some situations. For example, after all institutions of learning were closed to prevent the spread of coronavirus in March 2020, many universities have continued learning through Online, Distance and E-learning (ODEL) platforms, and some have even conducted virtual graduations. Others like Kenyatta University have reported innovations such as development of ventilators and modified testing swabs for Covid-19. This is admirable despite numerous limitations of internet accessibilities and other shortcomings. This remarkable achievement has been possible due to semi-autonomy in the university education sector, where Senates are given the right and power, by the Education Act, to make autonomous decisions for their universities which are regulated and monitored using the standards and regulations set by the Commission of University Education (CUE). However, other levels of the education sector do not have this autonomy and have had to depend on the ministry of education for guidance. On 8th July 2020, the ministry of education announced the result of a consultative meeting with stakeholders, to postpone the reopening of schools to January 2021. This was due to the rising cases of corona virus infections in May and June, steeping the infection curve, expected to reach the peak by November and to have flattened by January 2021 (Magoha, 2020). However, what surprised many was the additional and unforeseen announcement that all basic education students (apart from standard 8 and form 4 examination candidates whose details were not clarified) will repeat their current class levels in 2021. The pronouncement caused anxiety and has attracted mixed reactions from various stakeholders. The purpose of this paper is therefore to explain the leadership decisions made by the ministry of education analyze their impact on basic education and propose possible ways for educational leaders and administrators, community leaders and volunteers to facilitate home-based education during the Covid-19 pandemic. This should be done with a goal for progression and promotion of students to the next class level when the 2020 syllabus is eventually covered. The study method utilized desktop literature research where interactions with educational leaders, scholars and practitioners were used to investigate threats and opportunities in managing education during crises.  Article visualizations

Integrating ICT into Teaching and Learning Biology: A Case for Rachuonyo South Sub-County, Kenya - Mwanda, Gideon; Mwanda, Samwel; Midigo, Ronnie; Maundu, John (American Journal of Education and Information Technologies, 2017)
The purpose of this study was to find out the extent of integration of computer technology into teaching and learning Biology in secondary schools of Rachuonyo South Sub-County, Kenya. The target population consisted of students and biology teachers in the Sub-County. Data was collected by use of questionnaires and an observation check list. From the study, most schools had few computers; teachers had inadequate training on use of computer applications; most teachers did not use computer technology for personal growth and instructional purposes. Inadequate number of computers in the sampled schools was the major challenge facing the integration of computer technology into the instruction process. The study recommends increased accessibility of computers, adequate training on use of computer technology and development of a policy framework to guide on the path to effective computer integration into instruction process.
Keywords: ⚠️ Invalid DOI

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Keywords: ⛔ No DOI found

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using ICT, 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school...
Keywords: ⛔ No DOI found

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine (Distance Education, 2018)
The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.
Keywords: Re-entry; dropouts; open distance e-learning

Prospective teachers' teaching experience: teacher learning through the use of video - Osmanoglu, Aslihan (Educational Research, 2015)
Background: Future teachers need to observe, interpret and analyse teaching during the initial teacher education period. The use of videoed teaching and learning in teacher education promotes reflection, and analysing videos of teaching is helpful in learning effective classroom practices that prospective teachers mostly do not have the chance to observe during fieldwork experiences. The analysis of videos of teaching can be seen as a way to enhance the development of prospective teachers' professional vision, which, in turn, improves instruction. Purpose: The purpose of this study was to examine prospective teachers' reflections on video examples depicting their own teaching experiences. It aimed to create a professional development environment to facilitate the prospective teachers' reflection on their own videos and those of their peers to improve their professional vision. Sample: This study was conducted with over 200 (in 31 groups) third-year prospective mathematics teachers in a university in Western Turkey. The student teachers, receiving training to teach first- to fourth-grade elementary school pupils, were taking a teaching methods course. Design and methods: In the first week of the semester, the student teachers, working in groups, were assigned mathematics topics to teach the elementary school pupils. During the semester, each group prepared by trying out their activities in front of other student teachers in other groups. At the end of the semester, one student teacher from each group presented a short lesson related to their mathematical topic to the elementary school pupils. This lesson was videotaped, then later it was watched and discussed by the student teachers. Of the student teachers who undertook the teaching in the videos, 22 volunteers agreed to be interviewed. All groups of student teachers provided written reflections on their experience. Selected videos of the class discussions about the videos of teaching were also used for triangulation. The data were analysed to identify the issues the prospective teachers reflected upon. A content analysis technique was employed. Results: The data indicated that the prospective teachers were able to reflect on several issues related to effective teaching, connect their theoretical knowledge to their practice and consider issues related to pupil learning and difficulties. Conclusion: The findings suggested that the use of video, together with discussions between the student teachers, had the potential to create promising learning opportunities for prospective teachers.
Keywords: Case Method (Teaching Technique); Case Studies; Case-based pedagogy; Content Analysis; Data Analysis; Discussion (Teaching Technique); EDUCATION of student teachers; EFFECTIVE teaching; ELEMENTARY school teachers; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Electronic Learning; Elementary Education; Elementary School Teachers; Foreign Countries; Higher Education; Knowledge Base for Teaching; Learning Activities; Mathematics Teachers; Methods Courses; Microteaching; Outcomes of Education; PROFESSIONAL education; Postsecondary Education; Preservice Teacher Education; Preservice Teachers; Reflective Teaching; Student Teacher Attitudes; Student Teachers; TEACHER education; TEACHING methods; TRAINING of student teachers; Teacher Effectiveness; Teaching Experience; Theory Practice Relationship; Turkey; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096187; __finaldtb; class discussions; prospective teacher education; reflection; video case study

Parent and Caregiver Engagement in Kenya: Gaps, opportunities, and emerging questions for future research - Flam, Rebekka; Honda, Delanie; Ramesh Vasudevan, Sharanya; Mbugua, Wanjiku (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Tertiary students’ engagement with professional learning networks and emerging technologies in learning: The case of a coastal University in West Africa. - Wiafe, Bernard; Takramah, Florence; Bless, Gloria; Akaadom, Bernard (International Multidisciplinary Research Journal, 2020)
The main aim of this study was to investigate students' views on their engagement with professional learning networks and emerging technologies for students' use and how these impact their studies. A sample of 150 students from the University of Cape Coast, Ghana was used for study. Respondents were selected from second year to final year students pursuing undergraduate degree programmes from three different departments of the university. The research instrument used was a carefully constructed questionnaire. Undergraduate students generally exhibited positive attitude towards the use of professional learning networks and emerging technologies across the five attitudinal subscales they were measured on. As a result, from the findings, it is recommended that the use of professional learning networks and emerging technologies should be taken advantage of at all levels in a university curriculum.
Keywords: ⛔ No DOI found

Culture and Classroom Reform: The case of the District Primary Education Project, India - Clarke, Prema (Comparative Education, 2003)
Reform in teaching and learning forms one of the basic dimensions of educational reform. This study explores the impact of the reform process on teacher thinking and classroom practice in the multi-donor supported District Primary Education Project in Karnataka, India. Using both qualitative and quantitative methodologies, a variety of aspects dealing with teaching and learning are examined in order to understand the extent to which changes are taking place in the classroom. The study analyses the impact of four cultural constructs, which frame teaching and learning in India: holism as a shared worldview that encourages openness to regulation; the hierarchical structure as a regulative social framework; knowledge as discovered and attested collectively; and the ‘sense of duty’ that deﬁnes the role of the teacher (and student). The conclusion of the study is that while there are observable changes in the classroom in the use of instructional aids and activities during instruction, the essential characteristics of traditional practice, namely rote and repetition has not changed. Both teachers’ openness and resistance to reform are portrayed as embedded in the cultural construction of teaching and learning.

Cost-effectiveness of digital personalised learning: Three interventions from Kenya - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Improving the Mouse Skills of Basic School Learners Using the Optical Mouse and Self Instructional Software. A Case of a Ghanaian Basic School - Asare, Samuel; Leticia, Agyemang (Innovation The European Journal of Social Science Research, 2020)
The study came about as a result of poor performance showed by Bosofour R\C primary 6 learners' during practical sessions. The general objective of the study is to examine the causes of learner's poor mouse skills and provide an immediate solution to it. The research was conducted at Bosofour R\C primary school from the month of December, 2019 to June, 2020. The study was critically analyzed, though ICT is a core subject offered by all learners' in the school, but due to time constraint, nature of the research and inadequate financial support, all the classes could not be covered but few were sampled to represent the whole school. The study adopted a random sampling technique for its appropriateness in reaching out to a large representative sample and generalization of the findings. The target population included five hundred and twenty (520) learners, comprising of two hundred and forty-eight (248) boys and two hundred and seventy-two (272) girls. Random sampling techniques was used to select twenty (20) learners'. Test, interview and observation were the main instruments used for data collection. The main design for the study was action research. The collected data was analyzed with the help of frequency distribution table, using pre-test and post-test as a method of obtaining data. The challenges of the study include; insufficient time for practical activity lessons, abstract methods of teaching, inadequate teaching\ learning resources and teachers' pedagogical knowledge about the course. The results of the study showed that learners' mouse skills may be improved by the use of optical mouse, self-instructional software and giving students enough time during practical sessions. It is therefore recommended that, Ghana Education Service should equip all Basic schools across the country with several types of educational software's, in addition in-service training on ICT should be provided for all teachers, and finally, much time should be allotted for ICT practical activity lessons.
Keywords: ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Learning through Assistive Devices: A Case of Students with Hearing Impairment - Farooq, Muhammad Shahid; Aasma; Iftikhar, Umaira (Bulletin of Education and Research, 2015)
Present era has introduced persons with disabilities with a range of assistive devices that have rapidly increased their educational, vocational, and frivolous activities. Current descriptive study attempted to explore the effects of assistive devices on the learning of hearing impaired students. A sample of 200 hearing impaired students was selected to identify the assistive devices that are more in use by hearing impaired students. All of the assistive devices commonly used for hearing impairment were included in the study to explore the effects of each on the learning of students with hearing impairment. The mean difference in the learning of students suggested that assistive technologies are overall assistance for the students with hearing impairment and there is no substitute to these devices that could assist them in such a quite differentiated manner. The role of high tech assistive devices as well as low tech devices has been highlighted prominently. The parents of hearing impaired students were also the part of study and found satisfied with the use of assistive devices for their children. It is divulged that there is a need to reduce the cost of assistive devices to be used by the students with hearing impairment.
Keywords: Assistive Technology; Costs; Elementary School Students; Foreign Countries; Grade 4; Hearing Impairments; Interpersonal Communication; Parent Attitudes; Program Effectiveness; Quality of Life; Student Needs; ___working_potential_duplicate; ⛔ No DOI found

Methodologies for mapping Ministry of Education EdTech interventions: Lessons from Ghana - Radford, Kate; Ampofo, Rudolph (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _comingsoon; _r:AddedByZotZen

Assessing the scale-up of a technology-supported, government-led teacher professional development programme in Tanzania: Considering issues of equity, agency, and adaptation, Round 2 Policy Brief - Chachage, Kristeen; Swai, Calvin; Hennessy, Sara; Adam, Taskeen; Koomar, Saalim; Hegwa Paskali, Jonathan; Massam, Winston; Mtenzi, Fredrick; Komba, Anneth; Jacob Mrpoe, Winfrida; Anthony, Gervace; Malibiche, Mustapha; et al. (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Assessment of the effectiveness of ICT on Teacher Trainees in Colleges of education. A Case of St. Monica's College of Education - Osei Frimpong, Kojo; Asare, Samuel; Caroline, Owusu-Mintah (Asian Journal of Computer Science and Information Technology, 2019)
The use of ICT in teacher training colleges has relatively improve teaching and learning. The effective use of various ICT tools such the computer, smart phones and PDAs has brought innovative ideas in teacher trainees. This study aimed at finding out the factors influencing the use of ICT tools in enhancing teaching and learning process in the various teacher training institutions in Ghana. A survey was used in order to investigate the study. It was revealed from the findings of the study that students and tutors in the various colleges of education have now accepted the use of ICT in teaching and learning process. However some students still see ICT as difficult due to various factors such as inadequate computers in the various colleges for practical tution and poor access to the internet for learning.
Keywords: ⛔ No DOI found

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Teacher professional development and coaching in low-income countries: An evidence-informed conversation - Haßler, Björn; Moss, Caitlin (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This first paper offers a broad overview.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:m; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Teacher professional development and coaching in low-income countries: Overarching considerations for the use of technology - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This second paper offers a wider perspective with some overarching considerations.
Keywords: C:Low-income countries; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Design-Based Implementation Research Baseline Data Collection: Technical report - Koomar, Saalim; Adam, Taskeen; Massam, Winston Edward; Anthony, Gervace; Mrope, Winifrida Jacob; Mtenzi, Fredrick; Mwakabungu, Fika; Komba, Aneth; Hennessy, Sara; Barretto, Johnpaul (EdTech Hub, 2022)
This research study aims to investigate the effectiveness, cost-effectiveness, and sustainability of a tech-supported, decentralised, and school-based teacher continuous professional development (TCPD) model, to improve learning outcomes in rural Tanzanian primary schools. The research will test and iteratively improve the national TCPD model and roll-out (including the semi-structured Communities of Learning), as outlined in the Tanzanian National TCPD Implementation Plan (2021). We seek to understand the model’s effectiveness and the role that technology can play. The research team includes researchers from EdTech Hub, Aga Khan University, and the Tanzania Institute of Education. The study employs a Design-Based Implementation Research (DBIR) approach in the first phase and an experimental study in the second phase. Keywords: teacher professional development; EdTech; design-based implementation research; Tanzania; Community of Learning; school-based An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The discourse on ICT teacher professional development needs: The case of a South African teachers’ union - Dlamini, Reuben; Mbatha, Khanyisile (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2018)
The prevalence and adoption of Information and Communication Technology (ICT) tools in education has often been guided by utopian perspectives without proper research to understand the schooling context and teachers’ ICT development needs. This paper reports on the findings from a study of in-service teachers who are members of a teachers’ union in South Africa. These teachers were surveyed using a questionnaire based on Second Information Technology in Education Study (SITES), which is an analytic framework that includes teacher characteristics, pedagogical practices and ICT use, school factors and system, and other external factors. This exploratory study was conducted within the framework of a teachers’ union to understand members’ preparedness to integrate ICT tools in their teaching practices. Findings indicate the need for in-service professional development activities in the use of ICT for teaching, in teaching in multicultural environments, and in classroom management. Equally important is the role of school management and administration in the adoption and integration of ICT tools in education. In addition, the research provided clear evidence that despite the huge investments into ICT infrastructure by government, inequalities in ICT competencies among teachers remain. The most important conclusion is that the investments being made are politically motivated and that teachers are being side-lined in the decision-making processes and preference given to political visions.
Keywords: ⛔ No DOI found

Secondary school mathematics teachers' views on e-learning implementation barriers during the COVID-19 pandemic: The case of Indonesia - Mailizar; Almanthari, Abdulsalam; Maulina, Suci; Bruce, Sandra (Eurasia Journal of Mathematics, Science and Technology Education, 2020)
School closures in Indonesia during the COVID-19 pandemic have left 45.5 million school students and 3.1 million teachers dependent on online teaching and learning. Online teaching and learning are an unprecedented experience for most teachers and students; consequently, they have a limited experience with it. This paper examines the views of secondary school mathematics teachers on E-learning implementation barriers during the COVID-19 pandemic at four barrier levels, namely teacher, school, curriculum and student. Furthermore, it assesses the relationship between barrier levels with teachers' demographic background. Data was collected through an online questionnaire, involving 159 participants from lower and upper secondary schools in Indonesia. The findings of this study suggest that student level barrier had the highest impact on e-learning use. In addition, the student level barrier showed strong positive correlation with the school level barrier and curriculum level barrier. The study showed that teachers' backgrounds had no impact on the level of barriers. This study stimulates further discussion on the way to overcome e-learning barriers whilst simultaneously maximizing benefits of E-learning during this pandemic and beyond it by highlighting the importance of students' voices.
Keywords: Barrier to e-Learning; E-Learning in mathematics education; E-learning during COVID-19; E-learning in Indonesia

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Determinants of Implementation of Public Sector Projects in Kenya: A Case of Laptop Project in Public Primary Schools in Kangundo Sub-County, Machakos County - Muinde, Samuel Mutisya; Mbataru, Patrick (2019)
In One-to-one laptop programs are becoming popular across the globe. However available evidence suggests that their implementations in schools are often faced with challenges. For example, even though the government of Kenya began supplying laptops to public primary schools in 2016; reports indicate that the gadgets have not fully been put into use in many schools. Most of the empirical studies done in this area have majorly focused on the level of success and factors influencing implementation of the project and not the extent to which specific variables determine implementation of the project, thus resulting to a research gap. In order to fill this gap, study focused on the determinants of implementation of the laptop project in public primary schools in Kangundo Sub-county. The study was guided by 4 research objectives: i.) To assess the extent to which teachers’ perception determine implementation of the laptop project; ii) To establish the extent to which teachers’ capacity in ICT determine implementation of the laptop project; iii) To establish the extent to which availability of facilities determine the implementation of the laptop project; and iv) To establish the extent to which availability of digital subject content determine implementation of the laptop project. The study was premised on three (3) theories; Technology Acceptance Model, Constructivist Learning Theory and Resource Based Theory. The study adopted descriptive survey design. It targeted all the public primary schools, all teachers in lower primary and all the Ministry of Education officials heading the four zones that constitute Kangundo Sub-county. The study targeted all the 74 public primary schools which have 222 lower primary teachers, 74 head teachers and 4 MOEST officials making a total target population of 300. It adopted stratified random sampling in stratifying the schools into four zones and randomly selected 22 schools. All 22 school heads and all 66 lower primary school teachers of the participating schools were purposively sampled. Additionally, the 4 MOEST officials heading the four zones were included, making a sample of 92 participants. Tools of data collection included questionnaires for teachers and school heads, an interview guide for MOEST officials and an observation checklist. The data analysis was conducted using SPSS. Content analysis was adopted in analyzing qualitative data whereas descriptive statistics such as frequencies and percentages were used in analyzing quantitative data. Tables and figures were used to present the study results. The inferential analysis conducted shows that there was a significant relationship between independent and dependent variables. Both teachers’ capacity on ICT and availability of facilities were found to have significant effect on implementation of the laptop project while teachers’ perception and availability of digital subject content were found to have insignificant effect on the project in public primary schools in Kangundo Sub-County.
Keywords: ___working_potential_duplicate; ⛔ No DOI found

E-learning in secondary Schools in Kenya: A Case of the NEPAD E-schools - Ayere, Mildred; Odera, F; Agak, John (Educational Research and Reviews, 2010)
The New Partnership for Africa's Development (NEPAD) schools were set up as centres of excellence in Information and Communication Technology (ICT) integration, so that other schools could copy their model in e-learning. It was for this reason that they were provided with computers, e-materials, internet appliances and trained personnel. But to gauge their levels of success as e-learning centres there was need to compare them to other schools offering ICT education in Kenya. It was for this reason that this study compared the application of the e-learning in NEPAD and non-NEPAD schools in Kenya. Specifically, the study: Identified significant differences in levels of integration of ICT in curriculum subjects; surveyed the differences in use of e-materials in education research; examined availability of e-libraries; identified significant differences in academic performance of NEPAD and non-NEPAD schools attributed to e-learning. The study used a combination of an exploratory approach using descriptive survey and ex-post-facto design. It was carried out in six of the eight provinces in Kenya, where the NEPAD schools are located. It targeted 1600 form four students from 35 secondary schools involved in ICT education (NEPAD schools included). Saturated sampling was used for the six NEPAD schools while six non-NEPAD schools were selected through simple random sampling. The sample consisted of three officials from the ministry of education, twelve principals and twelve heads of ICT department (HODs), and 570 of the form four students. The main data collection instrument was the questionnaire; administered to the students, the principals, and the HODs. The interview schedule was administered to the ministry of education personnel while an observation checklist was used as a confirmatory tool. Analysis was done using both descriptive and inferential statistics. The study found that, there was a significant difference in the application of e-learning in NEPAD and non-NEPAD schools. Based on these findings, it was recommended that schools involved in ICT education should intensify teacher facilitation and support teacher roles that are required in e-learning Key words: E-Learning, ICT integration, ICT education, new partnership for Africa's development (NEPAD).
Keywords: ⛔ No DOI found

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Factors That Influence Teachers' Pedagogical Use of ICT in Secondary Schools: A Case of Ghana - Buabeng-Andoh, Charles (Contemporary Educational Technology, 2019)
Technology is perceived as a vital driving force for contemporary education. The Government of Ghana acknowledges the relevance of Information and Communication Technology (ICT) in education, and it is financing ICT in secondary schools. However, most instructors are unwilling to integrate ICT into their teaching. Therefore, the purpose of this study was to investigate the factors that influence secondary school teachers' ICT usage in schools. The participants were 376 teachers randomly selected from 24 public and private schools. The data collected from the participants were analyzed by using descriptive statistics and analysis of variance. The results showed that teachers' use of ICT was still confined to basic and traditional activities such as search for information, class presentation etc. Internal and external factors were found to influence teachers' ICT usage. Also, female teachers reported that they use ICT more than male teachers. In general, this study has contributed to the literature regarding teachers' pedagogical use of ICT in secondary schools and also their gender differences in the use of ICT.
Keywords: Access to Computers; Competence; Computer Uses in Education; Foreign Countries; Gender Differences; Influence of Technology; Information Technology; Instructional Leadership; Pedagogical Content Knowledge; Private Schools; Public Schools; Rural Schools; Secondary School Teachers; Secondary Schools; Self Efficacy; Teacher Attitudes; Technological Literacy; Technology Integration; Training; Urban Schools; ⛔ No DOI found

Distance learning during COVID-19 crisis: Primary and secondary school parents experiences in Kenya - Mabeya, Mary Theodorah (East African Journal of Education Studies, 2020)
The COVID-19 disease outbreak in 2020 was declared by the World Health Organization as a Public Health Emergency (PHEIC). Human symptoms of the Coronaviruses among others are commonly spread through droplets (coughing) and close personal unprotected contact with an infected person through toughing. Based on the speed at which the disease spreads, learning institutions were distinguished as high-risk areas with prospective of exposing both learners and instructors the spreading the virus. This had a serious effect on the academic programs in all learning institutions worldwide where learning was abruptly discontinued and all students and instructors send home. The Government of Kenya (GOK) through the President’s directives suspended all learning institutions as one of the measures taken by the Ministry of Health to mitigate the spread of COVID-19. This affected the learning since most of the schools had not even started their syllabus that academic year. Alternative measures to ensure that curriculum implementation progressed well; various mechanisms were suggested including remote learning which was actualised in some instances. Virtual lessons and Open and Distance e-learning (ODeL) has mainly been adopted by institutions of higher learning (colleges and universities) globally in offering online classes. However, this was not the case in many public primary and secondary institutions where the common form of learning involves a very interactive physical relationship between teachers and their learners in classrooms. In Kenya, since all institutions of learning were closed as a result of the breakout of the COVID-19 pandemic, the Ministry of Education (MOE) opted for remote learning across the country. Research results from Rangwe Sub-county have shown that most learners have not benefited much from the online classes due to the network and other related challenges reported in this paper. This has created education inequity since parents who have children in private schools and those from well of backgrounds are the ones enjoying distance learning programmes offered. The research has also found out that parents did no proper supervision to ensure that their children were committed in their studies in remote settings. Lack of supportive infrastructure (electricity and internet network access) limited children participation in distance learning programmes in Rangwe Sub-county. The paper recommends that government to properly educate parents, teachers and learners on modalities of distance and remote learning programmes. There is need for government to provide children from disadvantaged families with technological appliances to enable them to participate in distance education.

Using School Performance Data to Drive School and Education District Office Accountability and Improvement: The Case of Ghana - Prew, Martin; Quaigrain, Kenneth (Educational Management Administration & Leadership, 2010)
Distance-education delivery through interactive television (ITV) is an effective means of providing instruction to learners. There are many advantages, such as the ability to provide immediate feedback and personal participation. To be effective, however, ITV requires structured planning and development, making the use of instructional design principles imperative. The following recommendations are made for training teachers about ITV: (1) provide an overview of the technology and how it works; (2) provide hands-on guided practice; (3) incorporate effective elements of instruction; (4) conduct periodic follow-up inservice training; (5) train with teachers who volunteer; (6) establish the amount of time needed to prepare and teach ITV courses; (7) provide experiences with other faculty members; (8) incorporate strategies for adding visual components to audio courses; and (9) use strategies that encourage group cohesion and student motivation. Teachers must adapt instruction to meet the varied needs of students, as both teachers and students adjust to the demands of the medium. (SLD)
Keywords: Delivery Systems; Distance Education; Educational Planning; Educational Technology; Educational Television; Feedback; Graduate Study; Higher Education; Information Transfer; Instructional Design; Instructional Effectiveness; Interactive Television; Student Motivation; Teacher Attitudes; Teacher Education; Teaching Methods; Technological Advancement; Telecourses; Training; search_string_27b

Government–donor relations in Sierra Leone: Who is in the driving seat? - Harris, David; Conteh, Felix Marco (The Journal of Modern African Studies, 2020)
Since the cessation of conflict in 2002, Sierra Leone has experienced extraordinary levels of involvement from Western donors. Paradoxically, while relationships are often portrayed on the ground as strong with significant donor influence, our research shows considerable fluidity in individual and institutional relationships. The article disaggregates donor–government relations at various levels over a short but crucial period, 2010–16, asking in each case who occupies the driving seat. In so doing, the article interrogates the concept of ‘extraversion’, investigating to what extent government – and indeed donors – has space in which to manoeuvre and how and why government and donors act as they do in this space. The period 2010–16 is of particular interest due to extreme iron ore price volatility and the Ebola epidemic of 2014–15. The article adds much-needed critique and empirical evidence to the debate on donor influence and ‘extraversion’.

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech for Contexts of Forced Displacement: A Rapid Evidence Review - Barnes, Katrina; Katrin, L (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices for learners in contexts of forced displacement. The main aim of the review is to provide education decision-makers, funders, and implementers (among others), with a clear picture of which interventions may be the most effective in these contexts and, crucially, which implementation decisions facilitate or hinder this effectiveness. We reviewed evidence generated between 2019 and 2024 on EdTech implementations in different contexts of forced displacement. We focused on implementations aimed at primary- and secondary-age learners, as well as their teachers and caregivers. Keywords: forced displacement, refugee education, education in emergencies An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Massive Open Online Courses (MOOCs) for Professional Teacher and Teacher Educator Development: A Case of TESSA MOOC in Kenya - Wambugu, Patriciah W. (Universal Journal of Educational Research, 2018)
This study intends to present a bespoke teacher professional development MOOC designed by Teacher Education for Sub-Saharan Africa (TESSA) team that allows MOOCs to become a viable means offering cost-effective, quality professional teacher development. TESSA is a network of teachers and teacher educators, working to improve classroom teaching in Africa. TESSA MOOC is an innovative approach to capacity building for teacher educators and teachers across Africa. The study presents outputs of an evaluation of TESSA MOOC course undertaken by Kenyan teachers and teacher educators. The experiences of the participants were that the TESSA MOOC was a new but interesting, appealing and flexible course. In addition, the participants were able to learn from one another and what they learnt may impact on their pedagogical skills. Key challenges identified include difficulties in downloading of materials due to lack of internet connectivity and use of ICT phobia for learning. MOOCs represent an untapped potential for teacher professional development that can be a cost and resource effective means to deliver quality education to teachers and teacher educators. Therefore, the teachers and teacher educators may need to exploit this learner based TESSA MOOC to build capacity for teaching.
Keywords: Educational Quality; Faculty Development; Foreign Countries; Information Technology; Online Courses; Teacher Education; Teacher Educators; Teacher Effectiveness

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology Use for Teacher Professional Development in Low- and Middle-Income Countries: Recommendations for policy from a systematic review - D'Angelo, Sophia; Hennessy, Sara; Kreimeia, Adam; Koomar, Saalim; Cao, Lydia; McIntyre, Nora; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Read; Teacher education and training; _r:AddedByZotZen

Mapping and Analysing Digital Learning Platforms in Latin America and the Caribbean - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF Latin America and Caribbean Regional Office (LACRO) submitted to the EdTech Hub Helpdesk in October 2021. The UNICEF team requested a curated list of digital learning platforms in the Latin America and Caribbean (LAC) region and an analysis of a shortlisted series of platforms intending to explore their potential for at-scale implementation and impact. This report does not aim to cover every leading and innovative digital learning platform in the LAC region. Rather, it presents a list of promising platforms and discusses their design and implementation to explore their relevance and potential for at-scale impact. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Deconstructing EdTech frameworks based on their creators, features, and usefulness - Cherner, Todd; Mitchell, Chyrstine (Learning, Media and Technology, 2020)
Several theoretical frameworks have been released in recent years to inform how educational technology (edtech) can be used in the classroom. These frameworks range from providing a holistic view of the role edtech plays in education at a macrolevel to analyzing how edtech is used by students and teachers. With a growing number of them now available, researchers have yet to systemically collect and analyze a set of these frameworks, which can result in edtech not being used effectively by practitioners and researchers alike. In response, this study employed a content analysis methodology to analyze nine frameworks designed for using edtech. This study will report its findings regarding the creators of these frameworks, features used to draw attention to the frameworks, and which frameworks key stakeholders may find most useful. To conclude, implications for contextualizing these frameworks within the EdTech Ecosystem will be offered along with critical considerations for practitioners and researchers to use when selecting edtech frameworks for their work.
Keywords: Critical Media Literacy; EdTech; Frameworks

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Designing OLPC learning environments: A case on 1:1 pedagogy in rural Tanzania - Pakarinen, S.; Apiola, M.; Moisseinen, N.; Tedre, M. (2013 Africon, 2013)
In the past two decades computers have become a standard educational tool in the industrialized countries. Recently, equipping each student with a personal device (one-to-one computing, OLPC) has been enthusiastically advocated for developing countries, too. However, despite a number of pioneering research studies, broader analyses of pedagogical, technical, and organizational aspects of one-to-one computing in developing countries are largely missing. In this participatory action research in a rural Tanzanian primary school, we identified a number of pedagogical elements that were beneficial for teaching and utilizing ICT in the classroom. We pinpointed exploratory and self-regulated learning, group problem solving, and constructive principles as facilitators of learning within the one-to-one computing paradigm in this context. Our results show that the introduction of children's computers also triggered a number of changes in dynamics both within the school but also outside the school.
Keywords: Context; Educational institutions; ICT utilization; Interviews; Materials; OLPC learning environment; Portable computers; Tanzania; computer aided instruction; constructive principles; educational institutions; educational tool; exploratory learning; group problem solving; information and communications technology; learning facilitators; one-to-one computing; organizational aspect; participatory action research; pedagogical aspect; pedagogical elements; pedagogy; rural primary school; self-regulated learning; teaching; technical aspect

A Cascade Teacher Training Model in Disaster Education: A Case of Turkey - Gökmenoğlu, Tuba; Sönmez, Elif Daşçı; Yavuz, İbrahim (2021)
Individuals' reluctance to take precautions before the disasters happen is one of the most critical concerns of the disaster management area. The disaster education given through schools is a critical process in addressing this problem. The purpose of this paper is to introduce the teacher training program model and the implementation practices of Turkey's School-Based Disaster Education Project. In Turkey, there are few studies regarding the planning, development, implementation, and evaluation stages of Disaster Risk Reduction education for teachers. The project has been carried out within the framework of the Ministry of National Education and Japan International Cooperation Agency. An at-scale cascade teacher professional development model was implemented. The model reached 135,375 teachers in 67 provinces by the 567 trainer teachers in a relatively short time with the cascade training system. This project has brought a significant nationwide disaster risk reduction training experience for Turkey with its economic and sustainable structure.

Digital literacy through Let’s Read app to improve the reading interest of elementary school students - Samsudin, Dea Fariska Ardiana; Rahmawati, Fitri Puji (International Conference on Learning and Advanced Education (ICOLAE 2022), 2023)
This study aimed to determined digital literacy through Let's Read application (app) as an innovation to increase students’ reading interest and to find out the results of using the let's read app in reading activities in elementary schools. The method used in this study was descriptive qualitative with a case study design. The authors collected...

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech for Out-of-School Children and Youth: A Rapid Evidence Review for the Southeast Asian Region - Barnes, Katrina; Mazari, Haani; Mitchell, Joel; Hayat, Amal; Zhao, Annette; Ullah, Noor; Emerusenge, Aime Parfait; D'Rozario, Jonny; Hinks, Jessica; Thinley, Sangay (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) by and for out-of-school children and youth (OOSCY) in Southeast Asia. The review summarises how EdTech is currently being used with OOSCY learners in these contexts, explores how effective these implementations are, and highlights the benefits and challenges of using EdTech with different out-of-school learners. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The review’s scope includes the following countries: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education for OOSCY, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for OOSCY. Key words: out-of-school children; rapid evidence review; RER; Southeast Asia; ASEAN; education technology; marginalised learners An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Blogging as critical praxis: becoming a critical teacher educator in the age of participatory culture - Pascarella, John (McGill University, 2009)
This self-study of becoming a critical teacher educator extends the research on blogs as a vehicle of critical self-reflection in teaching and teacher education. While the primary focus of this thesis is a self-study of the process of becoming a teacher educator, the author presents findings based on discursive data collected from blogs produced by teacher candidates in two case studies, which inform this process of becoming. The case studies are represented as two “strands”: one carried out in Montréal, Quebec, Canada, at McGill University, and the other carried out near Durban, KwaZulu-Natal, South Africa, at the University of KwaZulu-Natal. Like prior studies involving the use of blogs in teacher preparation, this study examines pre-service teachers’ critical engagement with topics and issues endemic to their current field experiences and future careers in K-12 classrooms. The instructional techniques deployed in the case studies adhered to principles of modeling technology integration in order to transform teaching and learning activities by facilitating a learning environment for pre-service teacher candidates informed by the tenets of critical pedagogy. In this vein, this study examines the implementation of a particular instructional strategy, problem-posing pedagogy, as a practice that integrates the use of blogs to aid the achievement of pre-service teacher candidates’ “critical self-engagement” as well as contribute to the author’s development as a critical teacher educator.
Keywords: 0530:Teacher education; 0710:Educational technology; Blogging; Critical praxis; Culture; Education; Educational technology; Participatory culture; Teacher education; Teacher educator; __:import:01; __:match:final; __:matched; __:study_id:2097704; __finaldtb

Factors Affecting Technology Uses in Schools: An Ecological Perspective - Zhao, Yong; Frank, Kenneth A. (American Educational Research Journal, 2003)
Why is technology not used more in schools? Many researchers have tried to solve this persistent puzzle. The authors of this article report on their study of technology uses in 19 schools. They suggest an ecological metaphor, using the example of the introduction of the zebra mussel into the Great Lakes, to integrate and organize sets of factors that affect implementation of computer uses. Their findings suggest that an ecological perspective can provide a powerful analytical framework for understanding technology uses in schools. That perspective points out new directions for research and has significant policy and practical implications for implementing innovations in schools.
Keywords: computers in schools; diffusion of innovation; educational technology; school ecology; teacher development

Summary: EdTech for Learners With Cognitive and Learning Disabilities - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Nimra, Afzal (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Cognitive and Learning Disabilities produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Negotiating problems of practice in research–practice design partnerships - Penuel, William R.; Coburn, Cynthia E.; Gallagher, Daniel J. (Teachers College Record, 2013)
This chapter focuses on how researchers and practitioners negotiate the focus of their joint work within design-based implementation research (DBIR). Studying and facilitating successful negotiation of the problems that become the focus of work and the search for solutions is important for developing DBIR, because of its commitment to focusing on persistent problems of practice from multiple stakeholders’ perspectives. Case studies of two different research–practice partnerships provide a context for exploring two different perspectives on negotiation. In one case study, the notion of partnerships as forms of cultural exchange across institutional boundaries that differ with respect to goals, norms, and practices is used to analyze a design partnership focused on repurposing curriculum units in elementary science. In the second case study, the concept of framing as developed in social movement theory is used to illuminate issues of status and authority within a partnership between a district and researchers. The chapter concludes by describing the contributions of each perspective to an understanding of how teams jointly negotiate the focus of their work and by providing some recommendations for how teams can do so successfully.

Literature Reviews of Educational Technology Research in Low- and Middle-Income Countries: An audit of the field - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
Keywords: LP: English; R:Literature review, systematic review; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:g; _zenodoETH:submitted; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode; educational technology, EdTech, low-income countries, literature review

Summary: EdTech for Learners With Hearing and Visual Impairments - A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny (EdTech Hub, 2024)
This document is a summary of a rapid evidence review on EdTech for Learners With Hearing and Visual Impairments produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/.An output of the EdTech Hub, https://edtechhub.org/ An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Online Examinations in Emergency Contexts: Can Proctoring and Other Technologies Be Feasible Alternatives for Facilitating Inclusive School Exams for All in Emergency Contexts? - AlSheikh Theeb, Thaer; Sahin, AynurGul; Abdelrahman, Salma; Chuang, Rachel; Affolter, Friedrich; Al Mekdad, Bayan; Sabboura, Rani; Shequem, Yazeed (EdTech Hub, 2022)
The purpose of this document is to serve as a guide that education practitioners working in emergency contexts can use to assess the feasibility of implementing online examinations and using proctoring technologies. The implementation of online high-stakes examinations in Syria and other emergency contexts will require significant investments in achieving the prerequisites needed for feasibility and credibility. Prerequisites include electricity, internet, and devices, as well as the development of the digital skills necessary for students to participate in online exams and for teachers and administrators to facilitate online exams. Further efforts are needed to prevent leakage of information on exam questions and content, and promote cultural change around online examinations. Key words: online examinations; proctoring technologies; emergency contexts; Syria An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

STEM Skills Initiatives for Adolescent Girls in the LAC Region - Villavicencio, Xuzel; Myers, Christina; Coflan, Caitlin Moss (EdTech Hub, 2022)
This report was produced in response to a request from the UNICEF country office of Argentina and presents a curated list of science, technology, engineering, and mathematics (STEM) skills initiatives for adolescent girls in the Latin American and Caribbean (LAC) region. It also provides an introduction to gender equality and background on the participation of women in STEM fields in the LAC region — as well as cross-cutting recommendations based on an analysis of a series of initiatives. Key words: STEM; Gender; Girls; LAC; Argentina; technology; Science An output of the EdTech Hub, https://edtechhub.org
Keywords: F: Helpdesk response; _r:AddedByZotZen

Small-group problem-based learning as a complex adaptive system - Mennin, Stewart (Teaching and Teacher Education, 2007)
Small-group problem-based learning (PBL) is widely embraced as a method of study in health professions schools and at many different levels of education. Complexity science provides a different lens with which to view and understand the application of this method. It presents new concepts and vocabulary that may be unfamiliar to practitioners of small-group PBL and other educational methods. This article looks at small-group PBL from the perspective of complex adaptive systems (CAS). It begins with a brief review of the current understanding and practice of PBL. Next some of the characteristics of CAS are reviewed using examples from small-group PBL to illustrate how these characteristics are expressed in that context. The principles and the educational theory in which small-group PBL are embedded are related to CAS. Implications for health professions education are discussed.

Scaling up successfully: Lessons from Kenya’s Tusome national literacy program - Piper, Benjamin; Destefano, Joseph; Kinyanjui, Esther M.; Ong’ele, Salome (Journal of Educational Change, 2018)
Many successful piloted programs fail when scaled up to a national level. In Kenya, which has a long history of particularly ineffective implementation after successful pilot programs, the Tusome national literacy program—which receives funding from the United States Agency for International Development—is a national-level scale-up of previous literacy and numeracy programs. We applied a scaling framework (Crouch and DeStefano in Doing reform differently: combining rigor and practicality in implementation and evaluation of system reforms. International development group working paper no. 2017-01, RTI International, Research Triangle Park, NC, 2017. https://www.rti.org/publication/doing-reform-differently-combining-rigor-and-practicality-implementation-and-evaluation) to examine whether Tusome’s implementation was rolled out in ways that would enable government structures and officers to respond effectively to the new program. We found that Tusome was able to clarify expectations for implementation and outcomes nationally using benchmarks for Kiswahili and English learning outcomes, and that these expectations were communicated all the way down to the school level. We noted that the essential program inputs were provided fairly consistently, across the nation. In addition, our analyses showed that Kenya developed functional, if simple, accountability and feedback mechanisms to track performance against benchmark expectations. We also established that the Tusome feedback data were utilized to encourage greater levels of instructional support within Kenya’s county level structures for education quality support. The results indicated that several of the key elements for successful scale-up were therefore put in place. However, we also discovered that Tusome failed to fully exploit the available classroom observational data to better target instructional support. In the context of this scaling framework, the Tusome literacy program’s external evaluation results showed program impacts of 0.6–1.0 standard deviations on English and Kiswahili learning outcomes. The program implemented a functional classroom observational feedback system through existing government systems, although usage of those systems varied widely across Kenya. Classroom visits, even if still falling short of the desired rate, were far more frequent, were focused on instructional quality, and included basic feedback and advice to teachers. These findings are promising with respect to the ability of countries facing quality problems to implement a coherent instructional reform through government systems at scale.
Keywords: ___working_potential_duplicate

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

Transition to online education in schools during a SARS-CoV-2 Coronavirus (COVID-19) pandemic in Georgia - Basilaia, Giorgi; Kvavadze, David (Pedagogical Research, 2020)
The situation in general education in Georgia has changed in the spring semester of 2020, when the first case of coronavirus COVID-19 infection was detected rising to 211 local and more than 1,5 million infection cases worldwide by the Apr. 8. 2020. Georgia became one of 188 countries worldwide that has suspended the education process. The paper studies the capacities ofthe country and its population to continue the education process atthe schools in the online form of distance learning, study reviews the different available platforms and indicates the ones that were used by the support of the government, such as online portal, TV School and Microsoft teams for public schools and the alternatives like Zoom, Slack and Google Meet, EduPage platform that can be used for online education and live communication and gives examples of their usage. Authors made a case study, where the Google Meet platform was implemented for online education in a private school with 950 students, shows the usage statistics generated by the system for the first week of the online education process. Results confirm that the quick transition to the online form of education went successful and gained experience can be used in the future. The experience and studies can be useful for other countries that have not found the ways of transition yet. The lesson learned from the pandemic of 2020 will force a generation of new laws, regulations, platforms and solutions for future cases, when the countries, government and population will be more prepared than today.

Integrating technology into K-12 teaching and learning: current knowledge gaps and recommendations for future research - Hew, Khe Foon; Brush, Thomas (Educational Technology Research and Development, 2007)
Although research studies in education show that use of technology can help student learning, its use is generally affected by certain barriers. In this paper, we first identify the general barriers typically faced by K-12 schools, both in the United States as well as other countries, when integrating technology into the curriculum for instructional purposes, namely: (a) resources, (b) institution, (c) subject culture, (d) attitudes and beliefs, (e) knowledge and skills, and (f) assessment. We then describe the strategies to overcome such barriers: (a) having a shared vision and technology integration plan, (b) overcoming the scarcity of resources, (c) changing attitudes and beliefs, (d) conducting professional development, and (e) reconsidering assessments. Finally, we identify several current knowledge gaps pertaining to the barriers and strategies of technology integration, and offer pertinent recommendations for future research.

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Overview of emerging country-level response to providing educational continuity under COVID-19: What’s working? What isn’t? - Joynes, Chris; Gibbs, Emma; Sims, Kate (2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Qualitative Research: A Guide to Design and Implementation - Merriam, Sharan B. (John Wiley & Sons, 2009)
Praise for the Third Edition of Qualitative Research: "Sharan B. Merriam synthesizes twenty years of developments in qualitative research with clarity and acumen." ?Michael Quinn Patton, author, Qualitative Research and Evaluation Methods "Here is a qualitative research methods book that reinforces the connection between professional experience and qualitative inquiry." ?Robert Stake, author, The Art of Case Study Research and Multiple Case Study Analysis "In this new edition, Sharan Merriam once again presents the world of qualitative research in language engaging and accessible?for new and experienced readers alike. If you can have only one book about qualitative research, this is it!" ?Patricia M. Reeves, associate professor, School of Social Work, University of Georgia "Mystified by qualitative research? You couldn't ask for a better guide than Sharan Merriam, who introduces you to the fundamental concepts of this research method, explains its complex forms, and then shows you exactly how to do a high-quality qualitative study." ?M. Carolyn Clark, coeditor, The International Journal of Qualitative Studies in Education
Keywords: Education / General

Summary: EdTech for Girls’ Education - A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Hinks, Jessica; D'Rozario, Jonny; Thinley, Sangay (EdTech Hub, 2024)
This document is a summary of a Rapid Evidence Review on EdTech for Girls' Education produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK’s Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.
Keywords: Research methodology; ___working_potential_duplicate; education systems; mixed-methods research

Not just for special occasions: supporting the professional learning of teachers through critical reflection with audio-visual information - Saito, Eisuke; Khong, Thi Diem Hang (Reflective Practice, 2017)
Despite increased use of professional learning communities in the teacher education field, they do not necessarily guarantee change in teachers’ daily practice. This study is a multiple case study of three school leaders in Vietnam to connect their teachers’ learning and practice by utilising visual records. In the cases studied, we see a progression of models of joint reflection based on visual information, from only occasional reflection to daily critical reflection, the latter of which the authors call ‘vide-flection’ referring to a process for people to consider their actions, thoughts, or experiences by utilising video-recorded images. For joint vide-flection, school leaders visit every classroom for several minutes every day to observe the wellbeing and learning of pupils and video-record struggles or breakthroughs in children’s learning; they share those images with teachers to jointly reflect on the situations. Through this vide-flection, teachers develop more detailed awareness of pupils needs.
Keywords: Reflective practice; Vietnam; critical reflection; professional learning; teacher professional development; vide-flection

Motivating students to offer their best: evidence based effective course design - Stearns, Susan A. (College Teaching, 2013)
Sometimes we question whether students are incapable or capable and/or willing or unwilling in regards to their academics. This study determined where students lie in regards to these concepts and showed one example of motivating students to do their best via course design, in this particular case by the use of a writing process model.
Keywords: course design; effective teaching; higher education; process writing; student motivation

Blended learning and Syrian refugees' empowerment through a capability approach lens - Abdelfattah Ahmed Younes, Mona (Lancaster University, 2020)
This study analyses the learning experiences of three Syrian refugee youth who enrolled in and completed blended learning (BL) programmes in Jordan, in order to explicate how BL has/or has not empowered those refugees. To achieve this objective, the following research questions framed this study: Does blended learning empower Syrian refugee youth living in Jordan? 1. Is blended learning, in the case of Syrian refugee youth, an empowering capability? 2. Does blended learning help Syrian refugee youth to overcome their restrictive ‘rules of the game’? 3. Does blended learning improve Syrian refugee youth’s resource portfolio? This study followed a case study approach. Three Syrian youth, each of whom attended a different BL programme, were interviewed between December 2018 and March 2019. While all three cases expressed aspirations that are education-bound, this study shows some difference in the aspirations of males and females and of urban refugees versus those residing in the camps. BL has been for all three cases a feasible learning opportunity. Programme providers designed the courses in a manner that accommodated to refugees’ locations, time, and economic status. Social media disseminated information about educational opportunities and possessing smartphones made following up with lectures and assignments possible and easy. The investigated BL programmes proved also to be enjoyable due to their constructive, learner-centred and collaborative approach, and competent facilitators. However, this finding does not indicate that those programmes were “empowering”. Restrictive legislations that constrain refugees’ work, movement, and lives, as well as patriarchal traditions that hampered females’ choices of education, were “rules of the game” that hindered students’ ability to fully benefit from the provided programmes. Despite the development of oral and public speaking, employability, and English language skills and despite the enhancement of self-esteem, confidence, and respect towards others, those programmes did not lead to refugees’ full empowerment.
Keywords: Google Scholar/ "mobile learning" "refugee education"; RER theme_pedagogies and modalities

Education and International Development: An Introduction - McCowan, Tristan; Unterhalter, Elaine (Bloomsbury Publishing, 2015)
'Honorable Mention' 2016 PROSE Award - Education PracticeEducation is fundamental to every aspect of development and there is widespread support across the world for policies that affirm that all children, regardless of their circumstances, have a right to quality schooling. Yet despite concerted efforts from national governments, multilateral organisations and NGOs over many decades we are still far from achieving education for all. In addition, while education can enhance human development, it is also associated with persistent inequalities. Education and International Development provides a comprehensive introduction to the field, giving an overview of the history, influential theories, important concepts and areas of achievement, and presenting a critical reflection on emerging trends in policy, practice and research. With chapters that review key challenges and inspiring initiatives in countries around the globe - focusing on critical issues such as language, conflict and teachers - this book serves both as a companion to graduate studies in international education and a concise reference book for practitioners and educators in the field.
Keywords: Education / Comparative; Education / Multicultural Education

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
Keywords: _r:AddedByZotZen

Use of Assistive Education Technologies to Support Children with Visual and Hearing Difficulties in the East Asia and Pacific Region - Yarrow, Noah; Pynnonen, Lauri; Song, Chuyu; Bhardwaj, Riaz; Spiezio, Mario (World Bank, 2023)
Evidence on the uptake, use, and impact of EdTech at scale on participation and learning among students with disabilities in low- and middle-income countries remains very limited. This report presents findings on access to EdTech for children with difficulties in hearing and vision in middle-income countries (MICs) in the East Asia and Pacific (EAP) region using three approaches: (i) a systematic regional literature review; (ii) interviews with 17 actors from the education technology private sector across the EAP region; and (iii) case studies from four countries: Vietnam, the Philippines, China, and Tonga. The main findings from the literature review are that most EdTech solutions in EAP MICs were applied at very small scale, with a focus on the tech testing stage, and only two of the 13 identified studies from a sample of 1,661 studies measured changes in student learning outcomes. The private sector interviews indicate qualitatively that most actors in this space are unaware of the needs of children with vision and hearing disabilities, and that other challenges such as profitability and general inequalities related to access to devices and high-speed internet receive the most attention. The case studies report no examples of national deployment of any assistive education technology, though there are multiple examples of small-scale digital approaches developed by individual schools or NGOs and shared locally or, in two cases, regionally. In looking at country contexts for the case studies, we found a lack of publicly available data on spending for assistive EdTech in EAP, a lack of data on (a) prevalence of disabilities among the student population, (b) student learning, and (c) student persistence in higher grades. We examine new data on policy-maker estimates of access and inclusion of children with disabilities, and find that despite support for inclusion, there is large scope for improving data collection, service delivery and access to assistive EdTech in MICs in the EAP region.

The Views of University Students About the Achievements and Motivations of the Distance Education Process During the Pandemic Period - Güldal Kan, Şebnem; Çaltıkuşu, Çilem; Şensoy, Şeniz (Propósitos y Representaciones, 2021)
The aim of this study is to examine the views of students about the achievements and motivations of thedistance education processes in universities during the pandemic period. The working group consists of 68 prospective teachers who continue their undergraduate programs in different departments of a private university in Northern Cyprus in the 2019-2020 spring academic year. All these participantsarestudying at thevariousdepartments of theFaculty of Education as 17 are in Pre-school Education, 28 in PrimaryEducationMathematics, 6 in PrimaryEducation, 1 in HistoryTeaching, 12 in Special Needs Education, 4 of them arestudying in Guidance and Psychological Counseling. The study is a qualitative study and the design of the study is determined as a case study. 42 female and 26 male teacher candidates participated in the study group. The majority of the participants are prospective teachers studying in their final year at university. While choosing the participants, easily accessible case sampling from purposeful sampling type was used. A Semi-structured interview form was used as a toolfordata collection. Later, the opinions of the experts were obtained and the interview questions were re-arranged accordingly and applied to the participants. As a result of the research, it was concluded that the psychological trauma experienced by teacher candidates during distance education at thepandemicperiodaffects both the success and motivation of their lessons.

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Systems Research in Education: Designs and methods - Magrath, Bronwen; Aslam, Monazza; Johnson, David (Research in Comparative and International Education, 2019)
This exploratory paper seeks to shed light on the methodological challenges of education systems research. There is growing consensus that interventions to improve learning outcomes must be designed and studied as part of a broader system of education, and that learning outcomes are affected by a complex web of dynamics involving different inputs, actors, processes and socio-political contexts. How should researchers in comparative and international education respond to this call for complexity? To begin to answer this question, we draw on recent and ongoing research within the Raising Learning Outcomes in Education Systems research programme – a programme of 30 projects funded by the UK’s Department for International Development (DFID) and Economic and Social Research Council (ESRC). The paper explores critical ways in which the methods used by individual research projects, and across the programme as a whole, offer opportunities and raise challenges for advancing systems thinking in education research.
Keywords: Research methodology; ___working_potential_duplicate; education systems; mixed-methods research

Interaction in a discussion list: an exploration of cognitive, social, and teaching presence in teachers’ online collaborations - Nami, Fatemeh; Marandi, S Susan; Sotoudehnama, Elaheh (ReCALL: the Journal of EUROCALL, 2018)
Discussion lists have gained a significant popularity in professional development research over the past few decades for the opportunity they provide for asynchronous interaction. This article presents findings from a small-scale case study that aimed at exploring the nature of teachers’ asynchronous exchanges in a discussion list. The data comprised the archived log of the messages in a Yahoo Group discussion list by five in-service English as a foreign language (EFL) teachers who volunteered to take part in a hybrid computer-assisted language learning (CALL) teacher education course in a state university in Iran. The discussion list was incorporated into the course to engage participants in professional dialogue on topics related to technology/CALL. During the initial data analysis, participants’ asynchronous exchanges were grouped as suggestions, questions, unclassified, answers, and delivery, drawing upon Oriogun and Cave’s (2008) SQUAD categorization, following the constant comparative method of analysis. Through a follow-up computer-mediated discourse analysis, cognitive, social, and teaching presence functional moves were identified in the data. Participants used the space not only for socializing and peer instruction but also for constructing knowledge. Despite an uneven pattern of contribution, asynchronous exchanges provided opportunities for knowledge construction at different levels of cognitive presence on topics ranging from technology tools and their affordances/constraints to computer-assisted language testing, materials development, and classroom management. The findings provide CALL teacher education researchers and course designers insights into the potential of asynchronous interaction for online and blended language teacher education.
Keywords: Asynchronous Communication; Blended Learning; CALL teacher education; CASE studies; COMPUTER assisted language instruction; Cognitive processes; Collaborative learning; Colleges & universities; Computer Mediated Communication; Computer assisted instruction--CAI; Computer assisted language learning; Critical thinking; Curriculum development; Data analysis; Discourse Analysis; Distance learning; ERIC, Current Index to Journals in Education (CIJE); Educational Technology; Educational technology; English (Second Language); English as a second language instruction; Faculty Development; Foreign Countries; Foreign languages; Group Discussion; Higher Education; Higher education; Hybrid computers; Interactive learning; Iran; LANGUAGE & languages; Language Teachers; Linguistics--Computer Applications; PROFESSIONAL education; Professional development; School environment; Second Language Instruction; Second language teachers; Social factors; TEACHERS; Teacher Education Programs; Teacher education; Teachers; Teaching; Technology Uses in Education; __:import:01; __:match:final; __:matched; __:study_id:2095858; __finaldtb; asynchronous interaction; cognitive presence; online collaboration; social presence; teaching presence

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance on Facilitation of E-Learning - Dzinotyiweyi, Monica; Chuang, Rachel; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
Keywords: F: Helpdesk response; _r:AddedByZotZen

Pathways to Impact: Insights from Research Partnerships in Uganda and India - Hinton, Rachel; Bronwin, Rona; Savage, Laura (IDS Bulletin, 2019)
This article sets out a perspective from the United Kingdom’s Department for International Development (DFID) on the challenges of achieving research uptake. Two country case studies are presented from India and Uganda, which explore research projects under the Economic and Social Research Council ESRC-DFID-funded Raising Learning Outcomes programme. These case studies focus on relationships between the key stakeholders that enable policy debate relevant to the funded research. They are not a direct assessment of the impact that this research has had. Rather, this article explores the messy and iterative processes that DFID advisers are engaged in within the networks that they are embedded (and those that they are not), the way that they use partnerships to access evidence and promote it into policy debate, and the other drivers that matter. This article is important as a contribution to ongoing efforts to improve the quality and usage of education evidence in low-income contexts.
Keywords: Impact; Policy Engagement; Research Partnership; Research Uptake

AI in education: Enhancing learning experiences and student outcomes - Xu, Zhiyi (Applied and Computational Engineering, 2024)
This research article makes an attempt to investigate the potential of Artificial Intelligence (AI) in enhancing the learning experiences, as well as student outcomes. As a result, it has developed a study that will be able to understand how the different AI tools, including machine learning, data learning, virtual reality (VR) and augmented reality (AR), automation, and so forth can be used to develop learning experiences and outcomes. Subsequently, a case study involving a mathematics classroom was used to collect data and confirm whether indeed AI led to improved learning experiences and study outcomes. The study confirms that AI resulted in positive outcome with positive performance measure sin academic performance, motivation and engagement, learning progression, and so forth.

Teachers’ Perception About Integration of ICT in Teaching and Learning of Kiswahili Language in Secondary Schools in Kenya. - Miima, Florence; Ondigi, Dr Samson; Mavisi, Rose (2013)
This article discusses the results of exploratory study of integration of ICT in teaching and learning of Kiswahili language in Kenyan secondary schools taking the case of Kakamega county in western part of Kenya. A survey design technique was adopted. Forty five teachers were selected to act as sample size for the study. Questionnaires and interview protocols were used to collect the data. The data collected was analyzed through descriptive statistical techniques. The results are summarized and presented through tables and graphs. The findings established that most Kiswahili teachers understand the benefit of integrating ICT in teaching and learning of Kiswahili language but they are not willing to adopt it due to various challenges. The paper examines how Kiswahili language teachers integrate ICT into everyday classroom practice, their perceptions, constrains, and their reservations. It also considers use of ICT along with the influences of established curriculum practice and policy upon Kiswahili language teacher’s willingness to develop new forms of activity and pedagogy. The case study provides some information on integration of ICT at all level of language teaching and learning in education.

A cognitive assessment tool designed for data collection in the field in low-and middle-income countries - Ford, Cassie B.; Kim, Ha Yeon; Brown, Lindsay; Aber, J. Lawrence; Sheridan, Margaret A. (Research in Comparative and International Education, 2019)
The Rapid Assessment of Cognitive and Emotional Regulation (RACER) is a tablet-based assessment tool for children that measures executive function (EF) skills. Instructions that are brief and visually presented; game-like tasks are designed to easily engage children regardless of literacy level and variable test administration settings. RACER measures inhibitory control and working memory. This study presents the theoretical rationale and empirical evidence for tablet-based assessments of EF, the process of administering the RACER assessments. The current sample consists of students in Lebanon (N=1900) and Niger (N=850). The results indicate that individual differences in EF can be assessed by the RACER tablet tasks. Specifically, we demonstrate that EF scores are associated in expected ways with age and that tasks function similarly to what has been observed in high-income countries. The feasibility and utility for researchers, practitioners, and clinicians, of this cognitive assessment tool is discussed.

Videos as a Tool in Teacher Professional Learning: How Do Videos Scaffold Teachers’ Understanding of the Behaviours of Students with ASD? - Lam, Cici Sze-ching (Promoting Collaborative Learning Cultures to Help Teachers Support Students with Autism Spectrum Disorder, 2022)
Videos are often used in teacher training. However, when considering professional learning for teachers in supporting students with autism spectrum disorder (ASD), the manner by which teacher educators can make use of videos in professional learning has rarely been documented. On the basis of a model called ‘Fostering a Community of Learners’ (FCL), this chapter aims to show a case study on how a professional learning course for in-service teachers uses videos as a tool to train teachers in understanding pedagogies and handling students with ASD, thus providing a platform for teachers to discuss their common points of interest. Individual interviews were conducted to understand the process of video learning. Hopefully, this article will inform practitioners or teacher educators on the use of videos and case studies in assisting teachers to understand the needs of students with ASD. Implications focus on how scaffolding of knowledge of the behaviours of students was supported with the use of videos in an FCL cycle.
Keywords: Scaffolding; Teaching self-efficacy; Video learning

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

TCPD in Tanzania: Phase 2 Round 1 Recommendations - Swai, Calvin; Chachage, Kristeen; Koomar, Saalim; Hennessy, Sara; Massam, Winston; Komba, Aneth; Mwakabungu, Fika; Paskali, Jonathan Hegwa; Anthony, Gervace; Mrope, Winifrida Jacob; Malibichi, Mustapha; Mutura, Emmanuel; et al. (EdTech Hub, 2024)
The study reported here is for Phase 2 of the research project known as ‘The Impact of a Tech-Supported, School-Based Teacher Continuous Professional Development Model on Learning Outcomes in Tanzania’ and part of the global Empowering Teachers Initiative (ETI), which comprises 10 country projects. It is closely aligned with the implementation of ‘MEWAKA’ (Mafunzo Endelevu kwa Walimu Kazini) or Teacher continuous professional development (TCPD), and the Tanzania National TCPD implementation plan. MEWAKA is an innovative, school-based, technology-supported programme currently being implemented by the Government of Tanzania in schools nationwide. The research was co-developed and designed collaboratively between EdTech Hub, the Tanzania Institute of Education (TIE), and Aga Khan University, with consultation from key stakeholders at the ministry level. The work’s current (second) phase focuses on issues of equity, agency, and adaptation in scaling MEWAKA. This policy brief summarises the key findings and recommendations from the first round of data collection for Phase 2 of the research project, conducted in March 2024. Keywords: teachers; teacher professional development; Tanzania; MEWAKA; participatory research An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Guidance Note 3 Digital technologies and girls’ education From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Blended learning for academic resilience in times of disaster or crisis - Mackey, Julie; Gilmore, Fiona; Dabner, Nicki (Journal of Online Learning and Teaching, 2012)
Blended learning can provide academic resilience in times of natural disaster, civil emergency, and crisis. While blended pedagogies are widely used in tertiary settings, very little has been written about the role of blended learning in times of crisis, or the pedagogical challenges of rapid course redesign to mitigate disruptive circumstances. This case study describes the immediate post-earthquake challenges of redesigning courses using different blends of face-to-face and online activities to meet the needs of on-campus, regional campus, and distance pre-service teacher education students. The research question asked, "What can be learned from the experiences of academic staff directly involved in the adaptation and redesign of blended courses in a time of disaster?" This descriptive case study employed quick-response research strategies to gather time-sensitive data while it was fresh in the minds of the participants. This article discusses key findings and concludes with recommendations to assist program and course leaders to prepare in advance for resilient blended learning in times of natural disaster, crisis, and emergency.

Computer literacy and e-learning perception in Cameroon: the case of Yaounde Faculty of Medicine and Biomedical Sciences - Bediang, Georges; Stoll, Beat; Geissbuhler, Antoine; Klohn, Axel M; Stuckelberger, Astrid; Nko’o, Samuel; Chastonay, Philippe (BMC Medical Education, 2013)
Background: Health science education faces numerous challenges: assimilation of knowledge, management of increasing numbers of learners or changes in educational models and methodologies. With the emergence of e-learning, the use of information and communication technologies (ICT) and Internet to improve teaching and learning in health science training institutions has become a crucial issue for low and middle income countries, including sub-Saharan Africa. In this perspective, the Faculty of Medicine and Biomedical Sciences (FMBS) of Yaoundé has played a pioneering role in Cameroon in making significant efforts to improve students’ and lecturers’ access to computers and to Internet on its campus. The objective is to investigate how computer literacy and the perception towards e-learning and its potential could contribute to the learning and teaching process within the FMBS academic community. Method: A cross-sectional survey was carried out among students, residents and lecturers. The data was gathered through a written questionnaire distributed at FMBS campus and analysed with routine statistical software. Results: 307 participants answered the questionnaire: 218 students, 57 residents and 32 lecturers. Results show that most students, residents and lecturers have access to computers and Internet, although students’ access is mainly at home for computers and at cyber cafés for Internet. Most of the participants have a fairly good mastery of ICT. However, some basic rules of good practices concerning the use of ICT in the health domain were still not well known. Google is the most frequently used engine to retrieve health literature for all participants; only 7% of students and 16% of residents have heard about Medical Subject Headings (MeSH). The potential of e-learning in the improvement of teaching and learning still remains insufficiently exploited. About two thirds of the students are not familiar with the concept of e-leaning. 84% of students and 58% of residents had never had access to e-learning resources. However, most of the participants perceive the potential of e-learning for learning and teaching, and are in favour of its development at the FMBS. Conclusion: The strong interest revealed by the study participants to adopt and follow-up the development of elearning, opens new perspectives to a faculty like the FMBS, located in a country with limited resources. However, the success of its development will depend on different factors: the definition of an e-learning strategy, the implementation of concrete measures and the adoption of a more active and participative pedagogy.

What have we learned after ten years of systematic reviews in international development? - Waddington, Hugh; Masset, Edoardo; Jimenez, Emmanuel (Journal of Development Effectiveness, 2018)
The paper discusses the role of systematic evidence in helping make better decisions to reach global development targets. Coming at the end of the ﬁrst decade of serious funding and support for systematic evidence generation in development economics and development studies, the paper presents opportunities and challenges for the continued development of systematic review methodologies. It concludes by introducing the papers collected in the issue, which make and demonstrate the case for theory-based approaches to evidence synthesis.
Keywords: Reviewed

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

How Can Decision-Makers Assess EdTech Interventions for Cost-Effectiveness to Enable Better Investments? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how decision-makers should consider cost-effectiveness when contemplating investing in EdTech programmes. Cost-effectiveness is a critically important consideration for anyone planning investments in EdTech, but it is also a complex one, which requires understanding the total cost of an intervention and comparing it against the likely impact on education. We draw on work from EdTech Hub and other prominent researchers to distil key practical insights for decision-makers on how to apply cost-effectiveness analysis to their decision-making. Practical considerations include recommendations on gathering the right data for analysis; ensuring cost calculations are holistic; leveraging existing frameworks and tools for cost and impact calculations; and ensuring that comparisons are made against non-tech interventions as well as the broader resource envelope available for education to determine affordability in a given context. Finally, we explore areas where additional work is needed, including an increased understanding of the challenges faced by decision-makers in considering cost-effectiveness and the need for greater transparency and accountability in cost-effectiveness analysis in the sector. Keywords Cost-effectiveness; EdTech; education policy; total cost of implementation; affordability; Learning-Adjusted Years of Schooling An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Dual Systems theory to conceptualise challenges to routine when transforming pedagogy with digital technologies - Blundell, Christopher; Lee, Kar-Tin; Nykvist, Shaun (Teachers and Teaching, 2019)
(2019). Using Dual Systems theory to conceptualise challenges to routine when transforming pedagogy with digital technologies. Teachers and Teaching: Vol. 25, No. 8, pp. 937-954.
Keywords: Barriers; Case Studies; Classroom Techniques; Correlation; Educational Change; Information Technology; Learning Theories; Student Behavior; Systems Approach; Teacher Attitudes; Teacher Role; Teacher Student Relationship; Teaching Methods; Technology Integration; ⛔ No DOI found

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Innovative finance reshaping cyclone resilience and child-responsive disaster management in Madagascar - UNICEF Climate, Environment, Energy and Disaster Risk Reduction (2024)
In Madagascar, severe cyclones have become an integral part of children’s lives. Between 2000 and 2024, more than 50 tropical storms and cyclones have impacted over six million boys, girls and adults. Given that nearly 60 percent of Madagascar’s population (31 million) is under the age of 25, children and young people bear a disproportionate burden.*This case study shows how UNICEF, the Government of Madagascar and civil society are working together to pilot a ground-breaking, innovative finance solution that includes a child-responsive, parametric risk transfer product for tropical cyclones. The Today & Tomorrow approach aims to reduce child exposure and vulnerability to future shocks and hazards, engage children and young people in solutions and strengthen the essential social systems and services they rely on most. In Madagascar, Cyclones Cheneso, Freddy and Gamane and Tropical Storm Alvaro affected nearly 200,000 students. The case study highlights UNICEF Madagascar and government efforts in the education sector to support these students and build disaster resilience in affected communities.*ACAPS, Madagascar, Cyclone Exposure and Vulnerabilities and UNICEF, Child Climate Risk Index (CCRI).

Learning without Schools? Education, Relief, and Government Partnerships during COVID-19 - Skoll Foundation (2020)
Join to hear about how two large school systems, in Pakistan and West Africa, are partnering with governments and NGOs to educate children at home without internet access. This is a case study on how local leaders, including a Skoll Awardee, see the challenge of education, relief, and partnerships during COVID-19. Panel: - Susannah Hares, Center for Global Development - Mushtaq Chhapra, TCF Co-Founder - Riaz Kamlani, TCF EVP - Paul Skidmore, Rising Academy Network Moderator: Shashi Buluswar, UC Berkeley, Institute for Transformative Technologies

Forum Guide to Data Governance - National Forum on Education Statistics (National Center for Education Statistics, 2020)
The Forum Guide to Data Governance highlights the multiple ways that data governance programs can benefit education agencies. It addresses the management, collection, use, and communication of education data; the development of effective and clearly defined data systems and policies to handle the complexity and necessary protection of data; and the continuous monitoring and decisionmaking needed in a regularly shifting data landscape. The Guide also features 12 case studies from state and local education agencies that have implemented effective data governance programs.

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Role of Intergovernmental Fiscal Transfers in Improving Education Outcomes - Al-Samarrai, Samer; Lewis, Blane (World Bank, 2021)
The majority of the world’s children live in countries where local governments are responsible for the provision of basic education services. Although subnational governments manage their own education systems, they often rely on transfers from the central government for funding. The main purpose of this study is to assess how these fiscal transfers affect public funding for education and how they ultimately affect student schooling and learning outcomes. Through a careful analysis of how fiscal transfers have affected education systems in different contexts, the investigation develops a set of principles to support improvements in the design and implementation of transfer systems with a specific focus on the provision of education services. The study is centered on seven country case studies that aim to answer a set of common research questions using a similar approach. Country case studies were conducted in Brazil, Bulgaria, China, Colombia, Indonesia, Sudan, and Uganda. The analysis shows that fiscal transfer mechanisms can improve the adequacy of public education spending, reduce spending inequalities between regions, and improve spending efficiency. Moreover, the study highlights that carefully designed and implemented transfer systems can help raise overall education outcomes and reduce education inequality. This publication was funded by a grant from the Results in Education for All Children (REACH) trust fund at the World Bank. REACH is supported by the government of Germany through the Federal Ministry for Economic Cooperation and Development, the government of Norway through NORAD, and the government of the United States of America through the U.S. Agency for International Development.
Keywords: Education; Education Equity; Education Finance; Education Outcomes; Education Spending; Fiscal Decentralization; Fiscal Transfers; Public Expenditure

Five starting points on innovation for the EdTech Hub – The EdTech Hub - Simpson, Lea (EdTech Hub, 2019)
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Pakistan Digital Learning Landscape Analysis - Zubairi, Asma; Khalayleh, Abdullah; Baloch, Imdad; Mazari, Haani; Kaye, Tom; Groeneveld, Caspar (EdTech Hub, 2022)
The Covid-19 pandemic has resulted in a dramatic increase in the role educational technology (EdTech) plays in education delivery. As schools have closed worldwide, EdTech has played a critical role in keeping children learning. However, as the pandemic has persisted, the optimism around EdTech has plateaued. It has given way to fears that children who are using EdTech are not learning, and that the most marginalised children are falling further behind due to the emergence of a digital divide. On average, only 34% of households across Pakistan have digital access and only 14% have access to laptops or computers. The access challenge is further intensified by demographics including gender, locality, and socio-economic status. This divide must be addressed if EdTech is to support effective learning for all children across all contexts in Pakistan. If left unaddressed, EdTech interventions can exacerbate a digital divide that further compounds the disadvantage of marginalised groups. Across the world, UNICEF has supported governments globally to deploy EdTech tools in response to the Covid-19 pandemic. To support this endeavour in Pakistan, UNICEF Pakistan is building evidence on digital learning to support the EdTech ecosystem in Pakistan. Evidence in this landscape review will support stakeholders including the Ministry of Federal Education and Professional Training (MoFEPT) and UNICEF Pakistan to develop long-term strategies to fortify Pakistan’s EdTech ecosystem. The purpose of this landscape review is to identify the challenges, emerging trends, and opportunities for engagement within Pakistan’s EdTech ecosystem. To do this, the landscape analysis collected and analysed data (both primary and secondary, and quantitative and qualitative) relating to technology-facilitated learning in Pakistan. In this way, this landscape analysis can both inform MoFEPT and UNICEF’s strategies and provide a resource for stakeholder (e.g., federal, provincial, and regional government agencies, development partners, and the private sector) engagement in technology-facilitated learning in Pakistan. Keywords: marginalised learners; out-of-school children; EdTech tools; Pakistan; foundational skills; infrastructure; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Helpdesk Response; _r:AddedByZotZen

A Theory of Change for Parents and Caregivers Towards a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Ahmed, Shakil; Mazari, Haani; Kaye, Tom; Radford, Kate; Otieno, Jennifer (EdTech Hub, 2022)
The third of a trilogy of Theories of Change (TOCs) that focuses on parents and caregivers as key agents of change in the development of an increasingly technology-enhanced education system in Bangladesh. The TOC was created following a period of desk research and in-country stakeholder workshops. It offers a theory for how parents’ and caregivers’ experiences in diverse programmes and initiatives will enable them to support children to improved educational outcomes, and take advantage of available technology. It offers a tool for programme designers, implementers, and evaluators to think critically about how their initiative(s) will impact parents and caregivers for the longer-term benefits of their children. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; parents and caregivers; parenting; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Impact of Education on Labour Market Outcomes in Rural and Urban India - Pradhan, K. C.; Parida, P. C.; Sarangi, Tapas (Reflecting on India’s Development: Employment, Skill and Health, 2018)
This paper examines the returns to education with respect to three labour market outcomes namely wages, employment and occupation using the National Sample Survey Office (NSSO) 68th round (2011–12) data. Wage equation (without selection bias) results point to the fact that returns to education increase at an increasing rate as the level of education increases and the impact of education is found relatively higher in the case of urban than rural areas. In case of employment, the study finds that compared to illiterates, the chances of higher educated people going to agriculture sector is less. This is true even in the case of rural areas whereas the interactive variable (education with rural dummy) is found negatively associated with employment in agriculture sector. Occupation results suggest that there is a strong association between higher education (under graduate and graduate and above) with professional occupations and less with agriculture and fishery and unskilled occupations, suggesting the need for improving education and creating quality employment opportunities in the rural areas that may help in arresting the growing urban burden.
Keywords: Education; Employment; India; Occupation; Urban-rural gap; Wages

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

EdTech for Education in Emergencies: A review of existing guidance and minimum standards - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Hayat, Amal; Emerusenge, Aime Parfait; Zazai, Rozina (EdTech Hub, 2024)
EdTech Hub is seeking to work with the education in emergencies (EiE) sector to develop quality standards and guidance relating to the effective implementation of educational technology (EdTech) in crisis contexts. To ensure that this work is genuinely meaningful and helpful, it is important to understand what guidance is already available in this space, and what effective guidance could look like. To do this, we reviewed existing guidance documents relating to the design and implementation of EdTech in emergency contexts, along with materials from adjacent disciplines such as humanitarian work and technology design and development. By identifying key commonalities and persistent gaps across these documents, we were able to suggest what future guidance relating to EdTech in emergencies should include, and how this guidance should be developed. Keywords: EdTech; education in emergencies; guidance; minimum standards An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Application of EdTech in Tanzania: Effectiveness of radio and television in teaching and learning amid COVID-19 pandemic - Feruzi, Sadiki M.; Li, Yang (International Journal of Advanced Engineering Research and Science, 2020)
On March 2020 school and university going students experienced termination of classes. The statement declared by the Tanzania prime minister honourable Kassim Majaliwa required all primary and secondary schools to postpone learning for a month and one day later universities were also asked to suspend studies and other activities. It was necessary to do so because of the novel coronavirus disease 2019 named by World Health Organisation as COVID-19 a pandemic that had spread and hit more than 150 countries. This paper intended to attain two major objectives, one was to explore the effectiveness of radio and television in handling teaching and learning process as an alternative adopted to ensure that students continue to be engaged in learning. Second, to examine the capabilities of the country through the Ministry of Education, Science and Technology to continue teaching and learning during the time of classroom disruption. The authors made a case study where radio and television platforms were adopted for teaching and learning. The results show that the transition from classroom teaching and learning to teaching and learning through radio and television stations platform was not effective. Similarly, the study shows that the government has demonstrated incompetence in running and monitoring the programme mostly in terms of programme preparation and implementation. However, this experience has built a solid foundation for the future cases, when the country, facilitators, students and parents will be more arranged than now.

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

School-based teachers' professional development through technology-enhanced learning in Bangladesh - Mahruf C Shohel, M; Banks, Frank (Teacher Development, 2012)
To promote significant pedagogical change, the most successful teacher education programmes for the global south happen in the school context. This paper is based on a pre-pilot intervention study of an international education development programme in Bangladesh. Technology-enhanced learning, in this case the use of the Apple® iPod® (iPod touch®), was used to support teachers' teaching and learning in their school contexts. This paper presents evidence to demonstrate how such school-based technology-enhanced support systems impact on classroom practice and help teachers' professional development. Using the case of a pre-pilot intervention in the Underprivileged Children's Educational Programs schools, it explores the teachers' professional development by analysing interviews with the teachers who were participating in the pre-pilot intervention programme, and draws the conclusion from the collected data that school-based teachers' professional development through technology-enhanced learning is contributing significantly to in-service training in a resource-constrained context.
Keywords: Bangladesh; Education--Teaching Methods And Curriculum; Educational technology; Learning; Professional development; Teacher education; UCEP-Bangladesh; ___working_potential_duplicate; hand-held device; school-based; teachers' professional development; technology-enhanced learning

Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

The Covid-19 epidemic: Teachers’ responses to school closure in developing countries - Khlaif, Zuheir N.; Salha, Soheil; Affouneh, Saida; Rashed, Hadi; ElKimishy, Lotfia Ali (Technology, Pedagogy and Education, 2020)
There is little research which explores middle school teachers’ response to school closures in developing countries in times of crisis. This article presents a case study of Afghanistan, Libya and Palestine as developing countries which have suffered from violence for many years prior to the Covid-19 crisis. It focuses on how teachers in middle school responded to school closure to fight the spread of Covid-19. Twenty-two teachers from these countries participated in the study. Semi-structured interviews and three diverse focus group sessions were used to collect data and evidence. The study found that teachers developed their skills to use emerging technologies and design suitable digital content. Moreover, they built strong relationships with the local community to assume their responsibility in emergency remote learning (ERL) by establishing community centres for students from poor families. Assessing and engaging students were crucial issues in ERL which need more research in different contexts.
Keywords: Covid-19; Emergency remote learning; developing countries; online learning; school closure

Prospective teachers' online learning mathematics activities in the age of COVID-19: A cluster analysis approach - Mulenga, Eddie M; Marbán, José M (Eurasia Journal of Mathematics, Science and Technology Education, 2020)
The learning situation in the Zambian education sector has changed in the age of COVID-19 when the first two cases of COVID-19 infection were detected in the country rising to 45 local and at least 1.8 million infections globally by 13th April, 2020. Zambia became one of the many countries globally that has prematurely closed all schools. This study examines prospective teachers' online learning mathematics activities in the age of COVID-19 pandemic. Cluster analysis results revealed that online learning mathematics activities have significant mean differences in clustering. Cluster 2 recorded the best performance, implying that students in this cluster exhibited excellent online learning skills for mathematics in technology-rich environments in which they will be forced to study and work in the future. The study reviews various available online platforms and indicates the one that will be opened by the government which is the Educational Channel on TV.
Keywords: COVID-19; Mathematics education; Online learning; Prospective teachers; Virtual teaching; Zambia

Deliverology 101: A Field Guide For Educational Leaders - Barber, Michael; Moffit, Andy; Kihn, Paul (Corwin Press, 2011)
'Michael Barber's pioneering work as head of my Delivery Unit helped ensure real progress, not just with our education reforms, but with healthcare and policing too. It attracted worldwide attention. This guide distils the wisdom he gained at that time and has refined since. I strongly recommend it.' - Tony Blair, Former UK Prime Minister 1997-2007A step-by-step approach to delivering resultsMichael Barber, former chief advisor on delivery to British Prime Minister Tony Blair, and his colleagues Andy Moffit and Paul Kihn thoroughly describe Barber's proven reform delivery processes in this practical field guide. The timing is ideal, as Barack Obama's administration prioritizes education reform. Citing education reform case studies from more than 20 countries, the authors assert that most previous reforms were unsuccessful due to failed implementation. This book focuses on how to accomplish meaningful results, including:- Significant and ongoing education reform- Excellence and equity across public educationThe authors illustrate a field-tested program that ensures reform is achieved in the most profound sense, with students able to see, feel, and reap the benefits of a high-quality education. It is based not only on the experience of the Blair administration but also on case studies of successful implementation of reform in the U.S. and elsewhere.Listen as Barber describes the importance of the book:
Keywords: Education / Decision-Making & Problem Solving; Education / Leadership

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Educational Television: A Rapid Evidence Review - Watson, Joe; McIntyre, Nora (EdTech Hub, 2020)
This Rapid Evidence Review (RER) gives an overview of the recent literature concerning how the use of educational television might support children’s learning in low- and middle-income countries (LMICs). In this review, educational television is defined as television designed with research-based knowledge of how children use and understand television that systematically incorporates academic or social curricula into its content. In low-income contexts, educational television material could be delivered through videos played in schools that are supported by corresponding teacher guidance (e.g. the Mexican school-based T elesecundaria programme), or broadcast on public channels (e.g. the Tanzanian animation, Ubongo Kids). As such, certain educational television projects are capable of functioning even in circumstances where access to formal schooling facilities is restricted. This review therefore provides information that is particularly valuable in the context of the COVID-19 pandemic.
Keywords: L:English UXZJW5DR; P:Evidence review VCMFM9ZD; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:P:Girls ED5GMBNU; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _P:Evidence review VCMFM9ZD; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:P:Girls ED5GMBNU; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Challenges and strategies of working with learners with low vision: Implications for teacher training - Yalo, J. A.; Indoshi, F. C.; Agak, J. O. (Educational Research and Reviews, 2012)
Learners with low vision can be trained to increase their visual functioning through a planned programme of visual experiences. Such a low vision training programme was introduced in Kenya in 1994. However, despite its implementation over the last 15 years, challenges still persist among teachers who work with such learners. The purpose of this study was to document challenges that learners with low vision have on teachers’ performance when teaching learners with low vision in special primary schools for the visually impaired in Kenya. The study was carried out in 6 schools for the visually impaired respondents in the study including 78 teachers survey through questionnaire and observation. The study established challenges faced by teachers as lack of appropriate devices for learners, lack of adequate training of teachers and lack of regular teacher auditing. Strategies suggested to address the challenges were supply of low vision devices, low vision teams based at each school reconstituted to provide co-ordinated learning support and regular case conferencing be mounted to provide teacher support.

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Educational loss at times of crisis: the role of games in students’ learning in Palestine and Iraq - Ali, Kareema; Burgos, Daniel; Affouneh, Saida (Sustainability, 2023)
This study examines the role of educational games in compensating for educational loss and their impact on students’ motivation towards learning during crises in Palestine and Iraq. Additionally, the study considers the challenges facing the employment of this strategy and ways to overcome these challenges. By performing separate open semi-structured interviews with a group of 10 educators from university professors, teachers, and educational supervisors, the study used the qualitative descriptive approach which designs multiple case studies. The results showed the prominent role that educational games play in increasing students’ motivation towards learning and compensating for educational loss through what they add to the fun and suspense in the learning process and how they shorten time and effort and help students to engage and cooperate in acquiring knowledge, skills, and values. The results also reveal common challenges that face the employment of educational games. These challenges are social, economic, technological, challenges related to school environment, and psychological challenges. The study shows the possibility of overcoming these challenges by providing funding sources, preparing plans to employ educational games, and developing teachers’ capabilities to implement them in their teaching practices.
Keywords: crises; educational games; educational loss; motivation

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (International Institute of Social and Economic Sciences, 2019)
All universities in South Africa are encouraged to use a Learning Management System such as Blackboard to facilitate blended learning. Despite, the availability of Blackboard at one university of technology in the country, some lecturers and students prefer utilising WhatsApp for teaching and learning. The purpose of this study is to investigate students and lecturers’ perspectives about learning and teaching using WhatsApp at a university in South Africa. The study was done using a qualitative case study within an intepretivist paradigm. It was guided by Garrison, Anderson and Archer’s Community of Inquiry as a theoretical framework. Sixteen students and two lecturers who heavily use WhatsApp were purposively selected to participate in semi-structured interviews and focus group discussions. The study found that lecturers use WhatsApp not only for communication purposes, but to foster collaborative learning among students. Although students noted some limitations which they experience when using WhatsApp, they preferred the social media to blackboard. The study concludes that although WhatsApp is response to students’ needs, it does not adequately prepare students to graduate with digital literacy skills expected by the Department of Education in the country.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425972; __finaldtb

WhatsApp utilisation at an initial teacher preparation programme at a university of technology in South Africa - Mabaso, Nkosinomusa; Meda, Lawrence (International Institute of Social and Economic Sciences, 2019)
All universities in South Africa are encouraged to use a Learning Management System such as Blackboard to facilitate blended learning. Despite, the availability of Blackboard at one university of technology in the country, some lecturers and students prefer utilising WhatsApp for teaching and learning. The purpose of this study is to investigate students and lecturers’ perspectives about learning and teaching using WhatsApp at a university in South Africa. The study was done using a qualitative case study within an intepretivist paradigm. It was guided by Garrison, Anderson and Archer’s Community of Inquiry as a theoretical framework. Sixteen students and two lecturers who heavily use WhatsApp were purposively selected to participate in semi-structured interviews and focus group discussions. The study found that lecturers use WhatsApp not only for communication purposes, but to foster collaborative learning among students. Although students noted some limitations which they experience when using WhatsApp, they preferred the social media to blackboard. The study concludes that although WhatsApp is response to students’ needs, it does not adequately prepare students to graduate with digital literacy skills expected by the Department of Education in the country.
Keywords: __:import:01; __:match:final; __:matched; __:study_id:2425972; __finaldtb

IDENTIFICAÇÃO DO MODELO DE NEGÓCIO DE UMA START-UP/TIC: ESTUDO DE CASO NA EMPRESA GEEKIE - Lulia Filho, Herivelto; Turri, Silvia Novaes Zilber; Silva, Eduardo Corneto; Santos, Edna de Souza Machado (Investigação Científica nas Ciências Humanas e Sociais Aplicadas 3, 2019)
This study does not only understand the state of the art of the startups, but also understand how a small company of technology-based structure, shape its business model to grow and strengthen their business. For this this article has how objective of research, identify and describe the business model of a Startup/ICT Brazilian that work in the area of the education. It was used the concepts of case study, when analyzing the company Start-up/ICT Geekie, but will be used only secondary data, being this research a documentary research. The results show that the adaptive learning platform Start-up/ICT Geekie offers innovative service, personalizing and customizing education schools where works. The business model creates value for students, teachers and schools. Limitations of this article are in not obtaining primary data direct in the Geekie company and have only one company as study focus which limits the understanding of the business model of firms in the education sector.

Cultivating a personal learning network that leads to professional change - Stewart, Benjamin L. (Northcentral University, 2015)
Teacher professional development opportunities in Mexico are currently lacking. The traditional approaches of professional development such as workshops and conferences are commonplace but do little to bridge the gap between abstract concepts about teaching and learning and the practicalities teachers face in the classroom. The purpose of this qualitative multiple case study was to describe how ideas, materials, and social interactions form a PLN through online, informal pedagogical dialogues among English language educators as it relates to professional learning. The five participants of this study were selected from a total of 10 based on their willingness to complete an informed consent form, complete an initial online survey, interact with other professionals publically online, and participate in a final interview. The online survey contained demographic information about each case and included both open and closed items; a content analysis was done on public interactions that tool place online; and a final in-depth interview used open questions to inquire about how respective PLNs changed over time. All data was coded, categorized, and placed into themes based on the ideational, material, and social aspects of each PLN. The findings show that professional knowledge, skills sets, and overall dispositions emerge in unique ways based on how ideas, technologies, and personal contacts interrelate with each other over time, and that an individual’s PLN provides unanticipated benefits when sharing publicly online.
Keywords: 0444:Foreign language education; 0449:Educational leadership; 0710:Educational technology; Actor-network theory; Complexity; Content analysis; Education; Educational leadership; Educational technology; English; Foreign Language; Learning; Personal learning network; Polls & surveys; Teacher education; __:import:01; __:match:final; __:matched; __:study_id:2096277; __finaldtb

Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1) - Haßler, Björn; Brugha, Meaghan; Muyoya, Chisenga; Mitchell, Joel; Hollow, David; Jackson, Alan (Jigsaw and Open Develoment & Education, 2018)
Donor Organizations & the Principles for Digital Development: A Landscape Assessment and Gap Analysis. (Principles for Digital Development — Resource Development Program Asset No. 1)   Also available at https://digitalprinciples.org/resource/donor-organizations-the-principles-for-digital-development-a-landscape-assessment-and-gap-analysis/, https://digitalprinciples.org/wp-content/uploads/PDD2018_interactive.pdf
Keywords: _DOILIVE; _not_EdTechHub; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Paying Per Diems for ICT4D Project Participation: A Sustainability Challenge - Sanner, Terje Aksel; Sæbø, Johan Ivar (Information Technologies & International Development, 2014)
The article highlights the contradictory role per diem payments play in swiftly attracting local participation in ICT for Development (ICT4D) projects, while undermining long-term capacity building and sustainability with such efforts. We discuss sustainability challenges endemic to ICT4D projects in light of our case study findings from a mobile phone–based intervention in a public health management information system (HMIS) in Malawi. We explore these challenges at multiple levels of analysis by drawing on the neo-institutional notion of “institutional logics.” For practitioners and policy makers, the article offers suggestions on how to counter some of the pitfalls associated with the use of per diems to incentivize ICT4D project participants. The study contributes to the institutional logics perspective by exploring empirically the intricate interdependence between two mutually reinforcing, yet seemingly incongruent institutional logics of development project impact and aid entitlement.
Keywords: ⛔ No DOI found

Guidance Note 8 Resilient and sustainable energy solutions From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Azfal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The Effects of Micro-Reflective Teaching Practices on the Professional Skill Development of Pre-Service Physics Teachers - Batman, Demet; Saka, Ahmet Zeki (The Turkish Online Journal of Educational Technology, 2021)
The aim of this study is to find out the effects of micro-reflective teaching practices on the professional skill development of pre-service physics teachers. It was planned as an experimental study with one group pretestposttest and supported by the case study method. The data were collected by using professional skill scale, observation form and reflective diaries. The sample of the study composed of 13 (6 female, 7 male) pre-service teachers were studying in a Physics Teaching Program in an education faculty in north-eastern Turkey. Each preservice teacher implemented 5 micro-reflective teaching practice within the scope of the research. These practices were recorded by the camera. At the end of each practice pre-service teachers watched themselves and wrote their reflective diaries. The data obtained from the scales and the observation form were analyzed by using the Wilcoxon Signed Rank Test, and the data acquired from the reflective diaries were examined based on interpretive analysis. The findings based on the data obtained from the professional skill scale, observation forms and the reflective diaries indicate that micro-reflective teaching practices help improve pre-service physics teachers’ basic professional skills; subject matter mastery, planning, communication, classroom management, and evaluation.
Keywords: ⛔ No DOI found

Child labour and school dropout in least-developed countries: empirical evidence from Lao PDR - Xayavong, Thidavong; Pholphirul, Piriya (International Journal of Education Economics and Development, 2018)
Even though topics related to child labour and school dropout have been studied worldwide, little attention has focused in the least-developed countries. This paper examines the impact of child labour on school dropout by using national representative data surveyed in the Lao PDR, which serves as a case study of a least-developed country. Using an average wage of children by province as an instrumental variable, findings indicate that child labour, especially with regard to girls, has a strong impact on driving school dropout. Parental educational attainment, particularly mother's education, seems to show a significant effect on reducing the probability of dropping out. Our evidence supports the need to provide free education programs that have not yet been established in least-developed countries such as the Lao PDR. At the very least, given limited government budgets, support can be targeted to help vulnerable groups and poor families.
Keywords: Lao PDR; child labour; least-developed countries; school dropout; ⛔ No INSPIRE recid found

Private engagement in refugee education and the promise of digital humanitarianism - Menashy, Francine; Zakharia, Zeena (Oxford Review of Education, 2019)
This paper examines the prevalence of technological interventions in education in emergencies through a case study of private participation in Syrian refugee education in Jordan, Lebanon, and Turkey. This research is conceptually situated within critiques of ‘digital humanitarianism’, simultaneously interrogating the role of technology in humanitarian responses and the roles of private actors who promote this technology. Our study demonstrates that a pervasive optimism concerning education technology in emergencies accompanies a surge in private actor engagement in Syrian refugee education. Findings indicate that while access to technology in educational settings is important to the Syrian refugee populations, private actors’ disproportionate focus on technology is problematic, particularly when technological interventions are viewed as panaceas for refugee education; designed free from coordination; driven by proﬁt motivations; and developed in a manner decontextualised from the learning context. This study attends to the necessity of countering the overwhelming optimism about technology as a panacea for refugee education, which fails to problematise the implications of interventions developed in the Global North for a distant ‘other’ in the Global South.

Private engagement in refugee education and the promise of digital humanitarianism - Menashy, Francine; Zakharia, Zeena (Oxford Review of Education, 2019)
This paper examines the prevalence of technological interventions in education in emergencies through a case study of private participation in Syrian refugee education in Jordan, Lebanon, and Turkey. This research is conceptually situated within critiques of ‘digital humanitarianism’, simultaneously interrogating the role of technology in humanitarian responses and the roles of private actors who promote this technology. Our study demonstrates that a pervasive optimism concerning education technology in emergencies accompanies a surge in private actor engagement in Syrian refugee education. Findings indicate that while access to technology in educational settings is important to the Syrian refugee populations, private actors’ disproportionate focus on technology is problematic, particularly when technological interventions are viewed as panaceas for refugee education; designed free from coordination; driven by profit motivations; and developed in a manner decontextualised from the learning context. This study attends to the necessity of countering the overwhelming optimism about technology as a panacea for refugee education, which fails to problematise the implications of interventions developed in the Global North for a distant ‘other’ in the Global South.
Keywords: GENERAL - to be categorised; Google Scholar/ "education technology" refugees

Building an online community: student teachers' perceptions on the advantages of using social networking services in a teacher education program - Habibi, Akhmad; Mukinin, Amirul; Riyanto, Yatim; Prasohjo, Lantip Diat; Sulistiyo, Urip; Sofwan, Muhammad; Saudagar, Ferdiaz (Turkish Online Journal of Distance Education, 2018)
This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collecting data involving forty-two student teachers. We organized our analysis and discussion around their perceptions and the contexts in which the advantages they perceived emerge. The analyses of the texts revealed that two salient themes with their sub-themes related to the advantages of using Social Networking Services (SNS) in a teacher education program were social interaction (peer discussion and platform to interact with supervisors or lecturers) and learning motivation and experience supports (self-directed learning, promotes critical thinking, content engagement). Some pedagogical and social implications are also discussed.
Keywords: Case Studies; College Students; Computer Mediated Communication; Critical Thinking; Data Analysis; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Focus Groups; Foreign Countries; Group Discussion; Higher Education; Independent Study; Indonesia; Interpersonal Communication; Learner Engagement; Learning Motivation; Practicums; Preservice Teacher Education; Qualitative Research; Social Networks; Student Teacher Attitudes; Teacher Education Programs; __:import:01; __:match:final; __:matched; __:study_id:2097353; __finaldtb

Building an online community: student teachers' perceptions on the advantages of using social networking services in a teacher education program - Habibi, Akhmad; Mukinin, Amirul; Riyanto, Yatim; Prasohjo, Lantip Diat; Sulistiyo, Urip; Sofwan, Muhammad; Saudagar, Ferdiaz (Turkish Online Journal of Distance Education, 2018)
This inquiry examined student teachers' perceptions on the advantages of using Social Networking Services (SNS) in an English teacher education program at a public university in Jambi, Indonesia to ease the communication, supervision, discussion, and report submissions between supervisors and student teachers. The networking types included in the program are Whatsapp, Telegram, Email, and Google Form. The method of the research was qualitative through using focus group discussions as the technique of collecting data involving forty-two student teachers. We organized our analysis and discussion around their perceptions and the contexts in which the advantages they perceived emerge. The analyses of the texts revealed that two salient themes with their sub-themes related to the advantages of using Social Networking Services (SNS) in a teacher education program were social interaction (peer discussion and platform to interact with supervisors or lecturers) and learning motivation and experience supports (self-directed learning, promotes critical thinking, content engagement). Some pedagogical and social implications are also discussed.
Keywords: Case Studies; College Students; Computer Mediated Communication; Critical Thinking; Data Analysis; ERIC, Current Index to Journals in Education (CIJE); Educational Benefits; Focus Groups; Foreign Countries; Group Discussion; Higher Education; Independent Study; Indonesia; Interpersonal Communication; Learner Engagement; Learning Motivation; Practicums; Preservice Teacher Education; Qualitative Research; Social Networks; Student Teacher Attitudes; Teacher Education Programs; __:import:01; __:match:final; __:matched; __:study_id:2097353; __finaldtb

Does EdTech Substitute for Traditional Learning? Experimental Estimates of the Educational Production Function - Bettinger, Eric; Fairlie, Robert; Kapuza, Anastasia; Kardanova, Elena; Loyalka, Prashant; Zakharov, Andrey (National Bureau of Economic Research, 2020)
Experimental studies rarely consider the shape and nature of the education production function, which is useful for deriving optimal levels of input substitution in increasingly resource constrained environments. Because of the rapid expansion of EdTech as a substitute for traditional learning around the world and against the backdrop of full-scale temporary substitution due to the coronavirus pandemic, we explore the educational production function by using a large randomized controlled trial that varies dosage of computer-assisted learning (CAL) as a substitute for traditional learning. Results show production is concave in CAL. Moving from zero to a low level of CAL, the marginal rate of technical substitution (MRTS) of CAL for traditional learning is greater than one. Moving from a lower to a higher level of CAL, production remains on the same or a lower isoquant and the MRTS is equal to or less than one. The estimates are consistent with the general form of a Cobb-Douglas production function and imply that a blended approach of CAL and traditional learning is optimal. The findings have direct implications for the rapidly expanding use of educational technology worldwide and its continued substitution for traditional learning.

Female teachers in Tanzania: An analysis of gender, poverty and constrained capabilities - Tao, Sharon (Gender and Education, 2019)
Tanzania has made great strides in improving access to education; however, concerns about the quality of this education persist due to reports of teacher absenteeism, distraction and lack of preparation. Given this situation, this study aimed to investigate teachers’ values and contexts to provide nuanced understandings of teacher practice and behaviour, particularly with regard to how gender intersects with these. Ethnographic case studies were conducted at three Tanzanian schools and findings demonstrated that although men and women experienced similar material conditions, there were marked differences between their opportunities and constraints, which female teachers could readily relate to instances of absenteeism and distraction. A feminist interpretation of the capability approach was used to reflect on female teachers’ capabilities, constraints and agency; and socialist feminist theory was used to further elaborate on why male and female teachers differ in their valued capabilities, their levels of constraint and their actions resulting from negotiating constraint.

Assessing user acceptance toward blog technology using the UTAUT model - Pardamean, Bens; Susanto, Mario (International Journal of Mathematics and Computers in Simulation, 2012)
Blogs are among the many commonly used technologies for education and learning. They are also both conversational technologies and constructivist learning tools. Their interactive, collaborative, user-friendly, and instant archival features have transformed blogs into effective tools for enhancing case-based teaching methods in the asynchronous nature of the online environment. This study investigated the student populace’s acceptance of the blog technology through the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. UTAUT integrates eight theories from social psychology and sociology in order to examine the effects of major factors on behavioral intention and actual use of blog to learn e-business course materials and topic discussions. The results showed that both social influence and performance expectancy had a significant relationship with behavioral intention, whereas effort expectancy did not. In this study, behavioral intention did not have a significant relationship with actual usage level of blogs as a learning tool.
Keywords: ⛔ No DOI found

Recontextualization of learner-centred pedagogy in Rwanda: A comparative analysis of primary and secondary schools. - van de Kuilen, Hester; Altinyelken, Hulya Kosar; Voogt, Joke M.; Nzabalirwa, Wenceslas (Compare: A Journal of Comparative and International Education, 2020)
Learner-centred pedagogy (LCP) has become a global pedagogy and has been adopted in sub-Saharan African countries such as Rwanda, despite ample evidence of implementation failure. Most research has examined its implementation at either the primary or the secondary level. However, this qualitative study adopts a comparative approach and seeks to explore how Rwandan primary and secondary school teachers define, perceive and recontextualize LCP. The study is based on interviews and classroom observations of 12 effective primary and 12 effective secondary teachers working in eight well-performing schools; the analysis draws on Schweisfurth’s minimum standards for LCP. This Rwandan case reveals that the majority of primary and secondary teachers stimulated open and respectful classroom interactions. However, recontextualization of constructivism differed substantially between the two groups. Furthermore, the findings highlight the importance of more research into the dynamics between the various standards for LCP, and the interaction of these standards with contextual factors.
Keywords: Learner-centred pedagogy; education reform; recontextualization; rwanda; teachers

Computer-assisted instruction tools: A model to guide use in low-and middle-income countries - Kaye, Thomas; Ehren, Melanie (International Journal of Education and Development using Information and Communication Technology, 2021)
Learning outcomes in low- and lower-middle-income countries (LMICs) require significant improvement. With traditional reform efforts taking many years to realise results, education practitioners in LMICs are searching for innovative ways to rapidly strengthen learning outcomes. One tool showing promise is computer-assisted instruction (CAI). While a growing number of studies document CAI’s positive impacts on learning outcomes, others have found nil or negative effects. Research has yet to identify why these differences occur, and, most importantly, which factors must be in place to ensure that CAI contributes to improving learning outcomes. The aim of our research was to fill this gap in the research by developing a model highlighting those factors influencing the results of CAI interventions. Adopting a realist-informed methodology, we analysed 21 resources shared by 13 experts from around the world. We used the results of this analysis to develop a model that outlines key trends that facilitate and/or impede the deployment of CAI tools in LMICs. We find that key factors that should be considered when designing CAI interventions include the operating environment; stakeholder engagement; infrastructure; technological trust; CAI tool design; content curation/creation; student engagement; classroom integration; teacher capacity; student capacity; and data collection and use. This model highlights both these individual elements as well as noting how these elements interact. The model provides a foundation that can guide future research in this under-examined area.
Keywords: ⛔ No DOI found

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Emerging Technologies: An Overview of Practices in Distance Education - Hussain, Irshad (Journal on School Educational Technology, 2007)
In contemporary society, information technologies and communication technologies (ICTs) are playing crucial role in dissemination of knowledge and information the world over. Universities/ higher education institutions, particularly distance education universities in developed countries are making best use of these technologies for effective and interactive teaching learning process. Developing countries are also trying to adopt the model of developed countries according to their resources and circumstances. Distance education universities in developed countries like United States of America and United Kingdom are using advanced (emerging) technologies such as computers, Internet (World Wide Web) satellite communication, teleconferencing (videoconferencing and audio conferencing) and virtual reality in education and training. In developing countries like India, Pakistan and Thailand, distance education universities are using Radio, Television and Internet for teaching learning purpose and students support services. They are using computers mostly for office work. They are trying to adopt advanced technologies like developed countries but they have some limitations of resources (human & material resources). In future it is hoped that developing countries will also be using emerging technologies for teaching learning purpose.
Keywords: Case Studies; Computer Mediated Communication; Distance Education; Educational Development; Educational Practices; Educational Technology; Educational Television; Foreign Countries; Influence of Technology; Information Networks; Online Systems; Open Universities; Technological Advancement; Technology Integration; Technology Uses in Education; Telecommunications; Virtual Universities

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 3: Skills taxonomy - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the third of five reports on the development of a proof of concept for the Hub and describes our observations during the creation of a skills taxonomy. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Rethinking research partnerships: Evidence and the politics of participation in research partnerships for international development - Fransman, Jude; Newman, Kate (Journal of International Development, 2019)
This article responds to the drive for research partnerships between academics and practitioners, arguing that while potential benefits are clear, these are frequently not actualized resulting in partnerships that are ineffectual or worse, exacerbate damaging or inequitable assumptions and practices. In order to understand/improve partnerships, a systematic analysis of the interrelationship between what counts as evidence and dynamics of participation is proposed. Drawing on data from a seminar series and iterative analysis of seven case studies of partnerships between Higher Education Institutions and International Non-Governmental Organisations, the article concludes by suggesting substantial shifts in the theory and practice of partnerships. © 2019 The Authors Journal of International Development Published by John Wiley & Sons Ltd
Keywords: INGOs; evidence; higher education; knowledge and power; participation; research partnerships

Staying or leaving? Designing for persistence in an online educator training programme in Indonesia - Burns, Mary (Open Learning: The Journal of Open, Distance and e-Learning, 2013)
This case study discusses factors impacting the attrition and persistence rates of 60 Indonesian educators in an online programme in 2010. Course designers developed three variations of a web-based programme – a fully online, hybrid and web-facilitated model – and placed 20 learners, all with similar technology skills, in the three different models. The online cohort experienced a 31% attrition rate while 100% of learners in the hybrid and web-facilitated models completed the programme. Data collection revealed that the greatest factor impacting attrition or persistence was the absence or presence of face-to-face interaction with the instructor and colleagues. This paper outlines programme design elements that learners found most helpful in successfully completing the course.
Keywords: Indonesia; completion; online learning; persistence; readiness

Moving online : Creating effective tasks for analysis of teaching evidence - Schwartz, Jonathan; Mahiko, Joy (2020)
The use of examples of teaching videos becomes more prevalent in teacher education. Despite good teaching examples, a video cannot truly replace the real-life classroom experience. This paper presents the findings of a qualitative case study conducted in two teacher education courses during Spring 2020 semester. Due to the COVID-19 pandemic, field experiences were replaced by assignments administered online where teacher candidates watched and analyzed videos of expert teachers, and also analyzed their own videotaped teaching lessons. Results showed that teacher candidates became better at analyzing the teaching videos and appreciated the diversity of teaching examples. However, they also reported that they did not enjoy substituting real life experiences with online teaching videos.
Keywords: ⛔ No DOI found

Development and evaluation of Ning social network for teaching training online surveillance - Mohd Nawi, Mohd Aliff; Jamsari, Ezad Azraai; Sulaiman, Adibah; Hamzah, Mohd Isa (Turkish Online Journal of Distance Education, 2013)
Supervision of teaching practice is an important aspect of training teachers in improving their teaching skills. Barriers such as distance and time factor are the constraints faced by the lecturers at the National University of Malaysia to communicate with the teacher trainees under their supervision. Therefore, this study aims to develop and evaluate a social-networking site Ning's platform for the supervision of lecturers to teach on-line training. This study used the case design where a total of nine teacher trainees involved in this study. It found that overall, acceptance of the use of the social-networking site Ning mean score at the highest level of 3.91. In addition, all student teachers have positive attitudes towards the use of the social-networking site Ning social-networking site and agree a suitable approach to the supervision of one of the online teaching practices. While the "blog" is the most active facility used by student teachers in which they do self-reflection. In conclusion, the social-networking site Ning has the potential to assist lecturers to carry out supervision on-line teaching practice. (Contains 5 figures and 1 table.)
Keywords: Courseware; ERIC, Current Index to Journals in Education (CIJE); Foreign Countries; Higher Education; Interviews; Malaysia; Observation; Online Courses; Social Networks; Student Teachers; Supervisory Methods; Teacher Education Programs; Teacher Supervision; Teaching Methods; Trainees; Web 2.0 Technologies; __:import:01; __:match:final; __:matched; __:study_id:2098097; __finaldtb; ⛔ No DOI found

An Analysis of COVID-19 Student Learning Loss - Patrinos, Harry Anthony; Vegas, Emiliana; Carter-Rau, Rohan (World Bank, 2022)
COVID-19 caused significant disruption to the global education system. Early reviews of the first wave of lockdowns and school closures suggested significant learning loss in a few countries. A more recent and thorough analysis of recorded learning loss evidence documented since the beginning of the school closures between March 2020 and March 2022 finds even more evidence of learning loss. Most studies observed increases in inequality where certain demographics of students experienced more significant learning losses than others. But there are also outliers, countries that managed to limit the amount of loss. This review aims to consolidate all the available evidence and documents the empirical findings. Thirty-six robust studies were identified, the majority of which find learning losses on average amounting to 0.17 of a standard deviation, equivalent to roughly a one-half year’s worth of learning. These findings confirm that learning loss is real and significant, even compared to the first year of the pandemic. Further work is needed to increase the quantity of studies produced, and to ascertain the reasons for learning loss and in a few cases mitigation of loss.
Keywords: Coronavirus Impact on Learning; Covid-19 Student Learning Loss; Education; Education Disruption; Educational Inequality; Human Capital Accumulation; Learning Inequality; Pandemic Education Impact; Remote Learning Quality; School Lockdowns; Systematic Education Review

Using AI to Automate the Literature Review Process in Education: A Topic Brief - Haßler, Björn; Hassan, Syed Mustafa; Klune, Christopher; Mansour, Hassan; Friese, Laila (EdTech Hub, 2024)
Systematic literature reviews are often conducted manually in many research organisations. This topic brief explores the use of AI to automate the literature review process in the field of EdTech in order to improve the speed and efficiency of creating literature reviews across the sector. The topic brief is guided by the following questions: What tools are available for organisations and projects to use to automate evidence reviews? How appropriate are existing tools? Are they easy to use? Do they have licensing or cost barriers? How advanced are these AI tools? What tools are other organisations using to present the best evidence quickly? Is there value in building a bespoke AI tool to help identify, review, and synthesise evidence for literature reviews on education in low- and middle-income countries (LMICs)? What are the pros and cons of building a bespoke AI tool focusing on education in LMIC versus using an already existing commercial product? What are the cost implications of the two options?
Keywords: _r:AddedByMyEducationEvidence

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Unlocking Educational Opportunities : The Role of EdTech in Enhancing Access to Education for Rohingya Refugee Children - Ehlers, Henning (University of Twente, 2024)
The impact of ICT and especially EdTech within the Rohingya refugee camps remains poorly understood. The study investigates whether EdTech can serve as a scalable solution for mass education in the camps, considering current limitations. The ongoing conflict and the resulting humanitarian crisis have forced hundreds of thousands of Rohingya to flee, resulting in extremely limited educational opportunities for the children affected. Limited infrastructure hinders effective deployment of technological devices, exacerbated by unreliable power and internet access. Due to their stateless status, the Rohingya lack legal rights and protections, exposing them to exploitation, including human trafficking, child labor, child marriage and gender-based violence. The research is based on a combination of content analysis, a comparative case study analysis and an expert interview. Particular attention is paid to the factors that influence the successful use of EdTech, including infrastructure, culture and sustainability of initiatives. The work identifies both the opportunities and challenges associated with the implementation of EdTech in refugee camps. This study contributes to the current debate on innovative education strategies in humanitarian crises and offers recommendations to improving access to education for some of the world's most disadvantaged children.

Teacher Motivation in Sub-Saharan Africa and South Asia - Bennell, Paul; Akyeampong, Kwame (Department for International Development: Educational Papers, 2007)
This is one of a series of Education Papers issued by the Central Research Department of the Department For International Development. Each paper represents a study or piece of commissioned research on some aspect of education and training in developing countries. Most of the studies were undertaken in order to provide informed judgements from which policy decisions could be drawn, but in each case it has become apparent that the material produced would be of interest to a wider audience, particularly those whose work focuses on developing countries.This report synthesises the main findings and recommendations of an international research project on teacher motivation and incentives in sub-Sahara Africa and South Asia. The study has addressed the following four main questions: • To what extent is there a problem of poor motivation among teachers in sub-Saharan Africa and South Asia? Does this amount to a ‘crisis’, as has been suggested by some observers? • If so, what are the main reasons for poor teacher motivation? • How do poor motivation and incentives affect teacher performance and the overall effectiveness of national education systems? • What should be done to ensure that teachers are adequately motivated?
Keywords: C:sub-Saharan Africa and South Asia; ⛔ No DOI found

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Where is the “theory” within the field of educational technology research? - Hew, Khe Foon; Lan, Min; Tang, Ying; Jia, Chengyuan; Lo, Chung Kwan (British Journal of Educational Technology, 2019)
Critics often characterise the study of educational technology as under-theorised. To test this assertion and to determine the extent of this criticism, the present paper reports an in-depth analysis of the 503 most recent empirical articles published in three selected education-technology-related journals (Computers & Education; Learning, Media and Technology; and British Journal of Educational Technology). These journals were selected because they publish studies related to all education settings rather than focusing on only a certain segment such as higher education; they have broad geographical catchment; and they were the most highly ranked journals in terms of their 2017 journal citation impact factor. The present paper examines how explicitly existing theory was identified in previous research, how theories were applied and how often these theories were advanced in education technology research. In the majority of cases, explicit engagement with theory was absent. Many studies either were wholly bereft of theories or made vague use of theory. Where theory was explicit, the articles were more likely to use theory to conceptualise the research, to inform the data collection or analysis process and to discuss the results. Very few articles reported findings that help us to learn something new about a particular theory (ie, little evidence of theory advancement).

Planning and designing educational technology for low-income communities: A participatory and proactive approach - Ezumah, Bellarmine (Disruptive Technologies, Innovation and Global Redesign: Emerging Implications, 2012)
This chapter is an excerpt of a study that addressed the above concern using the One Laptop Per Child (OLPC) projects in Nigeria and Ghana as a case. It also situates the OLPC XO-laptop as a disruptive technology, because it aims at altering the existing pedagogy of the communities in which it was introduced through its constructivist approach. Moreover, as with most disruptive technologies, the XO laptop project is considered revolutionary, dramatically cheaper than regular laptops, convenient, and provides a different kind of learning content. As with the theme of this chapter, the XO laptop, although possessing disruptive technological qualities, was unable to achieve its goal due to lack of thorough planning and implementation of the adoption process. Results from the study informed the author to posit a model for technology adoption in low-income communities that is considered inclusive, participatory, and proactive, involving all stakeholders in setting up a policy. Such policy is expected to serve as benchmark for measuring the congruency of any proposed product whether disruptive or sustainable to the local need before its adoption.
Keywords: ___working_potential_duplicate

Planning and designing educational technology for low-income communities: A participatory and proactive approach - Ezumah, Bellarmine (Disruptive Technologies, Innovation and Global Redesign: Emerging Implications, 2012)
This chapter is an excerpt of a study that addressed the above concern using the One Laptop Per Child (OLPC) projects in Nigeria and Ghana as a case. It also situates the OLPC XO-laptop as a disruptive technology, because it aims at altering the existing pedagogy of the communities in which it was introduced through its constructivist approach. Moreover, as with most disruptive technologies, the XO laptop project is considered revolutionary, dramatically cheaper than regular laptops, convenient, and provides a different kind of learning content. As with the theme of this chapter, the XO laptop, although possessing disruptive technological qualities, was unable to achieve its goal due to lack of thorough planning and implementation of the adoption process. Results from the study informed the author to posit a model for technology adoption in low-income communities that is considered inclusive, participatory, and proactive, involving all stakeholders in setting up a policy. Such policy is expected to serve as benchmark for measuring the congruency of any proposed product whether disruptive or sustainable to the local need before its adoption.
Keywords: ___working_potential_duplicate

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Insights on ESL student teachers reflecting collaboratively online - Suppiah, Shubashini; Wah, Lee Kean, (PhD); Swanto, Suyansah, (PhD); Lajium, Denis Andrew, (PhD) (The English Teacher, 2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.
Keywords: Collaboration; Distance learning; English as a second language--ESL; Linguistics; Malaysia; Problem solving; Professional development; Reflective practice; Researchers; Social research; Student teachers; Teacher education; Teaching; Web 2.0; __:import:01; __:match:final; __:matched; __:study_id:2095770; __finaldtb; ⛔ No DOI found

Insights on ESL Student Teachers Reflecting Collaboratively Online Shubashini Suppiah Institute of Teacher Education Gaya Campus - Lee, S; Swanto, K; Lajium, S; Suppiah, D; Suppiah, Shubashini (2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.

Insights on ESL Student Teachers Reflecting Collaboratively Online Shubashini Suppiah Institute of Teacher Education Gaya Campus - Suppiah, Shubashini; Lee, S; Swanto, K; Lajium, S (2019)
The concept of a collaborative based reflective practice approach is grounded within the theoretical argument that critical reflection can be fostered through the presence of the "knowledgeable other" (Vygotsky, 1978). The present study was a pilot initiative in utilizing EDMODO (a closed educational learning management system) as a platform to explore reflection in a communal approach within a group of pre-service ESL teachers and their teacher educator mentor during a teaching practice placement in the context of the TESL (Teaching English as a Second Language) degree programme in an institute of teacher education (ITE) in Malaysia. The aims of the study are: (1) to examine the nature of the online reflection posts; and (2) to explore the nature of interactions that occurred online and the extent it supported collaborative reflection practices. The study employed a qualitative case study design in which five pre-service teachers (n=5) and their teacher educator mentor used EDMODO to post their reflections and carry out discussions for four weeks (n=4). The sources of data were the online reflection posts, the threaded discussion posts and a semi-structured group interview. Despite initial ambiguities and constraints, the EDMODO learning site as a platform for reflective practice showed positive results in that it allowed collaboration and dialogue to take place. Nevertheless, the facilitation of the reflection process requires further inquiry. The findings of the study suggest the need to establish a more systematic and structured approach when fostering critical reflection practices in a communal setting.

Challenges and opportunities for teacher professional development in interactive use of technology in African schools - Hennessy, Sara; Haßler, Bjoern; Hofmann, Riikka (Technology, Pedagogy and Education, 2015)
This article examines the supporting and constraining factors influencing professional learning about interactive teaching and mobile digital technology use in low-resourced basic schools in sub-Saharan Africa. It draws on a case study of iterative development and refinement of a school-based, peer-facilitated professional learning programme (‘OER4Schools’) that integrated use of mobile technologies, digital open educational resources and interactive pedagogy. The research and development involved teachers in three Zambian primary schools and culminated in an extensive multimedia resource. Using an ecological framework, factors emerging were characterised at three levels: teacher, school, and the wider community and policy context. They include school organisation and leadership, teacher motivation and perceptions of opportunities for professional learning and change, teacher views of pupil capabilities, availability of resources, teacher collaboration, and viewpoints of parents and policymakers. [ABSTRACT FROM PUBLISHER]
Keywords: ADULTS; AFRICA; Article; CAREER development; Digital Technology; EDUCATION; EDUCATIONAL technology research; Interactive Pedagogy; Open Educational Resources; PRIMARY school teachers; Sub-Saharan Africa; Zambia; _THEME: Teacher Professional Development; __:import:01; __:match:final; __:matched; __:study_id:2099892; __finaldtb; digital technology; interactive pedagogy; open educational resources; sub-Saharan Africa; teacher professional development

'Let's learn together': co-creating mental health solutions with adolescents in Tanzania and Viet Nam - Myers, Christina; Samuels, Fiona; Kyungu, Esther; Mbowe, Dayani; Dang, Hoang-Minh; Vu, Van; Le, Ha; Leon-Himmelstine, Carmen; Pellini, Arnaldo (ODI: Think change, 2022)
Co-creation is when participants and key stakeholders themselves are central to the process of designing solutions. This approach challenges the idea that interventions should be designed for individuals, and instead focuses on contextualising interventions through designing solutions by the very individuals who will be using them.This ODI Case study explores the experiences and reflections that emerged from designing and implementing a co-creation process. The project, funded by Fondation Botnar, was aiming to respond to mental health and well-being challenges facing adolescents in Tanzania and Viet Nam by co-creating digital and non-digital solutions. In the context of Covid-19, it also presents insights that can be used to inform what a co-design process should consider in practice, as well as a few lessons learnt and suggestions on how to do things differently in future.

Disrupted classes, undisrupted learning during COVID-19 outbreak in China: Application of open educational practices and resources - Huang, Ronghuai; Tlili, Ahmed; Chang, Ting Wen; Zhang, Xiangling; Nascimbeni, Fabio; Burgos, Daniel (Smart Learning Environments, 2020)
With the coronavirus (COVID-19) outbreak in China, the Chinese government decided to ban any type of face-to-face teaching, disrupting classes and resulting in over 270 million students being unable to return to their universities/schools. Therefore, the Ministry of Education (MoE) launched an initiative titled ‘Ensuring learning undisrupted when classes are disrupted’ by reforming the entire educational system and including an online education component. However, this quick reform in this unexpected critical situation of widespread COVID-19 cases harbours several challenges, such as the lack of time and teacher/student isolation. This paper discusses the possibility of using open educational resources (OER) and open educational practices (OEP) as an effective educational solution to overcome these challenges. Particularly, this study presents a generic OEP framework built on existing open-practice definitions. It then presents, based on this framework and based on the challenges reported by several Chinese education specialists during two national online seminars, a set of guidelines for the effective use of OER and OEP for both teaching and learning. Finally, this study presents some recommendations for the better adoption of OER and OEP in the future. The findings of this study can help researchers and educators apply OER and OEP for better learning experiences and outcomes during the COVID-19 outbreak.
Keywords: Coronavirus (COVID-19); Distance education; Online education; Open education; Open educational practices (OEP); Open educational resources (OER)

Life planning by digital storytelling in a primary school in rural Tanzania - Duveskog, Marcus; Tedre, Matti; Sedano, Carolina Islas; Sutinen, Erkki (Educational Technology & Society, 2012)
Storytelling is one of the earliest forms of knowledge transfer, and parents often use it for teaching their children values and knowledge. Formal schooling, however, is less inclined to use storytelling as a vehicle for knowledge transfer, and even less as a vehicle for modern self-directed, student-centered, and constructionist pedagogy. Research literature reports experiences on student-centered storytelling in schools, but there is little information about such learning environments using modern information technology. Using a case study approach, we collected qualitative data from a workshop that tested a number of constructionist pedagogical approaches and one-to-one computing technology in a hypercontextualized storytelling workshop. In that workshop, which took place in a Tanzanian primary school, pupils used their XO-1 laptops as digital media tools for expressing their dreams and solutions to overcoming challenges in life. Results of this study suggest that digital storytelling offers additional advantages when compared to traditional storytelling. Designers need to follow six principles for a successful digital storytelling workshop: commitment, contextual grounding, previous exposure to the context, involvement of local experts, atmosphere of trust, and realistic flexible planning.
Keywords: ⛔ No DOI found

Blog-based professional development of English teachers in Mumbai: The potential of innovative practice under scrutiny | Australasian Journal of Educational Technology - Khan, Atiya (Australian Journal of Educational Technology, 2017)
The professional development of teachers in India is still, by and large, based on formal and outdated professional learning traditions, often characterised by crash courses and one-off workshops. In education, blogs have proven to be an effective means of establishing and maintaining collaborative learning networks and helping members reflect on their professional practices. Information and communications technology (ICT) enabled practices of teacher professional development is still in its infancy in India. Moreover, there is limited research in India to secure foundational understanding of how and in what ways teachers of English in India use blogs for their professional development. This study explores the use of teacher reflective practice, teacher networking, and teacher collaboration, beyond formal ICT training, through blog-based professional development of English teachers in the Mumbai region of India. Using data collected from 32 teachers from three private schools in Mumbai, through ICT interactive workshop observations, questionnaires, interviews, and blog comments, this action case study explains whether and why blogging, as a learning community, has the potential to add significant value to existing professional development of English teachers in Mumbai.

The effects of a technology-aided learning environment on the improvement of a primary special education school - Karal, Hasan (Educational Research and Reviews, 2015)
The changes demanded by technology are reshaping people’s expectations of education. These changing demands and expectations have introduced certain concepts, such as individuals who have become skilled at learning and the learning organization. Individuals and schools, as the most basic unit of educational organizations, should demonstrate a shift from traditional training toward becoming ‘learning’ or ‘effective’ schools in order to survive in the world today. This requires effective implementation of technology infrastructure in schools and the integration of technology into learning environments. This study aimed to examine the impact of technology-aided learning environments on the improvement of a primary special education school where students with hearing impaired attend. The study adopted qualitative research approach and used case study as a research design. Semi-structured interviews and observations were employed for collecting necessary data. The study sample comprised a school principal, a vice principal, a staff, thirteen teachers and four parents of the students in the school. The data were analyzed qualitatively by using a descriptive analysis through the qualitative analysis software MAXQDA©. It was found that themes such as cooperation and organization for school improvement, innovation and student achievement received the highest level of emphasis. The results of the study suggest that using technology aided learning environments, helped the school to improve, changed the way of teachers’ functioning and contributed to their professional development. Progress in the social and academic performances of the students was also observed. Key words: School development, technology, innovation, hearing impaired.
Keywords: ___working_potential_duplicate

Short message service (SMS)–based remote support and teacher retention of training gains in Malawi - Slade, Timothy S.; Kipp, Scott; Cummings, Stirling; Nyirongo, Kondwani (Cultivating dynamic educators: case studies in teacher behavior change in Africa and Asia, 2018)
This book responds to growing recognition by international education professionals, policy makers, and funding partners of the need for qualified teachers and interest in the subject of teacher professional development (also referred to as "teacher behavior change"). The book responds to important questions that are fundamental to improving teaching quality by influencing teaching practice. These questions include: How do we provide high-quality training at scale? How do we ensure that training transfers to change in practice? What methods are most cost-effective? How do we know what works? The book includes case studies describing different approaches to teacher behavior change and illustrates how specific implementation choices were made for each context. Individual chapters document lessons learned as well as methodologies used for discerning lessons. The key conclusion is that no single effort is enough on its own; teacher behavior change requires a system-wide view and concerted, coordinated inputs from a range of stakeholders. This book contains the following chapters: (1) Understanding and Influencing Teacher Behavior Change: Editorial Introduction (Sarah Pouezevara); (2) Changing Teacher Educators' Conceptions and Practices Around Literacy Instruction: Lessons from Teacher Educators' Professional Development Experiences in Ethiopia (Dawit Mekonnen, Marion Fesmire, Adrienne Barnes, Stephen Backman, and Flavia Ramos-Mattoussi); (3) School Leadership and Early Grade Reading: Examining the Evidence in Zambia (Mitchell Rakusin and Guy Bostock); (4) Making Sense of Teacher In-Service Training in the Philippines (Nancy Clark-Chiarelli and Bonita Cabiles); (5) Short Message Service (SMS)-Based Remote Support and Teacher Retention of Training Gains in Malawi (Timothy S. Slade, Scott Kipp, Stirling Cummings, and Kondwani Nyirongo); (6) Relationships Between Coach Support and Teachers' Adoption of New Instructional Practices: Findings from the Nigeria Reading and Access Research Activity (RARA) (Karon Harden, Alison Pflepsen, and Simon King); (7) Using Activity Theory to Understand Teacher Peer Learning in Indonesia (Sarah Pouezevara, Feiny Sentosa, and Tifa Asrianti); (8) Teacher Motivation and Behavior Change: Results of the Teacher Motivation Diagnostic Tool in Northern India (Molly Hamm-RodrÃguez, Emily Richardson, and Jarret Guajardo); and (9) Once More Up the Mountain: The Promise of High-Quality Teaching Depends on Behavior Change (Lee E. Nordstrum). Contains a section about the contributors and an index. (Individual chapters contain references.) [Erin Newton compiled this volume.]
Keywords: __:import:02; __:match:final; __:matched; __:study_id:3123693; __finaldtb; ⛔ No DOI found

From face-to-face to teaching at a distance: Lessons learned from emergency remote teaching - Corcuera, Lovely; Abel Alvarez, Jr (Asian Journal of Distance Education, 2021)
The Covid-19 disrupts not only the health, economic, and tourism sectors but it paralyzed the education sector as well. Since face-to-face teaching and learning environment is still not possible in the Philippine context, this phenomenon leaves the teachers to use various alternative ways of instructional delivery. The sudden shift of teaching and learning delivery continuously challenges not only the students but also the teachers who are serving as educational front liners at the time of the pandemic crisis. The lack of proper training and experiences of teachers in online teaching and distance education served as educational loopholes in the context of emergency remote education.  Hence, this case study attempts to explore the experiences of K-12 senior high school teachers who have been immersed in emergency remote teaching. In analyzing the data gathered, the descriptive coding process was used. Interestingly, there were three themes reported in this study: getting the right mix of instructional methods, engaging in different open educational resources and information, and highlighting the need for the pedagogy of care and understanding. Although this study does not aim to make any generalities, however, the researchers saw the need to understand and investigate the journey of the K-12 senior high school teachers, which are essential in providing lending ears about their transitioning experiences from the traditional classroom environment to emergency remote education. This study concludes with the implications of the findings that emerged and the direction for further research.
Keywords: Covid-19; K-12 teachers; distance education; emergency remote education; teaching modality; ⛔ No DOI found

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

‘They are visually impaired, not blind … teach them!’: Grade R in-service teachers’ knowledge of teaching pre-reading skills to visually impaired learners - Kao, Matiekase A.; Mzimela, Patience J. (South African Journal of Childhood Education, 2019)
Background: Teaching reading skills is the cornerstone of all learning; therefore, teachers’ adherence to this mandate is important. However, it becomes complicated and challenging if the teacher has to teach pre-reading skills to Grade R learners with visual impairments. In light of this challenge, researchers have endeavoured to determine the Technological Pedagogical and Content Knowledge (TPACK) that teachers should possess for the effective teaching of reading in classrooms with visually impaired learners.Aim: This article explores a small sample of in-service teachers’ knowledge of using Braille to teach pre-reading skills to Grade R learners with visual impairments.Setting: The study was conducted in a School for the Blind in Maseru, Lesotho, where three Grade R in-service teachers teaching learners with visual impairments were purposively sampled.Methods: This study is underpinned by Koehler and Mishra’s theory of TPACK. An interpretivist, qualitative small-scale case study approach was employed, using semi-structured interviews and classroom observations. Document analysis was also used to corroborate findings.Results: Findings reveal that although some of the participants possess a high level of technological knowledge, they tend to teach Braille as a ‘stand-alone’ skill and fail to integrate it with the teaching of other pre-reading skills to Grade R learners.Conclusion: In-service teachers showed limited knowledge of some of the essential skills for teaching pre-reading skills to Grade R learners who are visually impaired. The study calls for supportive in-service teacher education programmes that equip Grade R teachers of learners with visual impairments with the necessary skills to teach pre-reading skills.
Keywords: Braille; Grade R Learners; Pedagogical Knowledge; Pre-Reading Skills; Technological Knowledge; Visual Impairment

Community outreach projects as a sustainable way of introducing information technology in developing countries - Zlotnikova, Irina; van der Weide, Theo (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2015)
The paper describes an approach to the sustainable introduction of IT in developing countries based on international collaboration between students taking the form of a knowledge bridge. The authors consider the challenges for introducing information technologies in developing countries; one of these is lack of reading materials ultimately leading to lack of reading skills in pupils and poor overall performance. A theoretical framework for the sustainable introduction of IT is proposed. It comprises the following components: (1) the model of a knowledge bridge, (2) the managerial model of the interactions between key stakeholders, and (3) the model of impact of a Community Outreach Project (COP) on target schools. The proposed models have been mapped to the widely adopted DPSIR framework used in sustainable development studies. As a case study, the authors discuss the E-readers Project run in two primary schools in Northern Tanzania. The paper also demonstrates how interaction and collaboration between Tanzanian and Dutch students was organized during preparatory stage and project implementation. The paper concludes with general recommendations on how to run a sustainable IT-based COP. These recommendations have been drawn from the analysis of the COP experience in the developing country, namely Tanzania.
Keywords: ⛔ No DOI found

Trialling open educational resources for technology-supported teacher professional development in rural Zimbabwe - Walker, H.; Hennessy, S.; Pimmer, C. (Research Papers in Education, 2022)
This study reports on the adaptation and outcomes of a teacher professional development (TPD) programme in a rural Zimbabwean secondary school. The programme incorporated Open Educational Resources (OER), specifically OER4school materials, that were provided via tablet computers for teachers and students. A mixed-methods case study was employed to explore teachers’ perceptions, knowledge, experiences of interactive learning and teaching in relation to this TPD, as well as their perceptions and experiences of the role and value of using technology to support student learning. Video data from structured lesson observations were triangulated with teacher post-lesson interviews and thematically coded. The interviews indicated that all teachers demonstrated a change in mindset and a clear understanding of interactive teaching methods. However, the structured observations revealed that only half of the teachers were using these interactive methods. Teachers also emphasised the value of OER and tablet technologies in improving lesson planning and making classroom learning more authentic. The use of technology, as both a TPD medium and as a classroom tool, showed potential to enhance the quality of TPD and teacher quality. Yet more specific teacher development to support the interactive use of technology within the classroom would be beneficial.

Goodhart’s Law and the gaming of UK public spending numbers - Hood, Christopher; Piotrowska, Barbara (Public Performance & Management Review, 2021)
Goodhart’s Law, originally inspired by money-supply indicators, predicts high-consequence administrative numbers tend to be gamed out of meaningfulness. This paper argues that, in addition to the well-documented manipulation of aggregate input numbers at the top-levels of decision making and performance indicators used for output control at the lower level, meso-level gaming happens also on the input side of public expenditure planning and control. A key mechanism through which it operates is creative categorization in the classification of units of spending. Based on a UK study, we explore three questions: can we find evidence for the existence of gaming in public expenditure control, how does the creative categorization work and how material or consequential is it? Using case studies of “protected” spending, public-private partnerships and accounting changes, we show that gaming understood as creative categorization is readily observable in UK public expenditure control and Goodhart’s Law effects can indeed be material or consequential, both in scale and in their implications for government accountability. We conclude that creating new spending categories to control public expenditure and limit gaming is a two-edged sword since it itself creates new opportunities for gaming.
Keywords: Goodhart’s Law; creative categorization; fiscal illusions; gaming; public finance management; public spending; rule bending

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Teaching Practices in the 21st Century in Kenya: A Qualitative Approach - Kaume-Mwinzi, Regina K. (International Journal of Educational Excellence, 2018)
Education is an engine for the growth and progress of any society and it is responsible for building human capital which sets technological and economic growth. In the pre-technology education context, the teacher controlled the instructional process, the content was delivered to the entire class and the teacher emphasized factual knowledge. However, the current global demands in education require the use of approaches that are learner-centered and embracing integration of ICT. The purpose of this study is to establish the pedagogy used in Kenya for the 21st century learner. The case study design was used to collect qualitative data from three teachers who were purposively sampled from three education sub-sectors in Kenya: primary, secondary and university. The interview was guided by three research questions: Which teaching practices are used in Kenya? Which are the ‘best’ teaching practices in Kenya in the 21st century? What are the barriers for the ‘best’ teaching practices in Kenya? The findings were that the teaching methods currently in use were mainly teacher-centered although the respondents revealed that the ‘best’ teaching practices for the 21st century learner were student-centered. However, the barriers were large classes, lack of resources and facilities among other factors. The study recommends realignment of education policies to give priority to build pedagogical capabilities of teachers, provide digital tools and other resources. This would enable the 21st century learners’ opportunity to unleash their potential.

eSkwela project - eSchool for out-of-school youths and adults, Philippines - Kamei, M (2010 International Conference on Technology for Education, 2010)
There are 774 million non-literates globally (UNESCO, 2009) and there is the acute problem of illiteracy grave in South Asian region. The paper discusses the implementation of eSkwela project as Alternative Learning System (ALS) in Philippines. The initiative responds directly to a national development priority to bring elearning opportunities and Information Communication Technology (ICT) for learning resources to mobile teachers / instructional managers and out-of-school learners in the Philippines. The paper assesses how the eSkwela project initiatives have provided opportunities for remote and elearning, blended learning and how Alternative Learning System (ALS) has been supported by innovative use of ICT for content development. It presents a macro view, case study of the strategic approach, design, challenges and successes faced by the eSkwela project which is still a work in progress. Rudiments in ICT for Education for citizens to attain the new-age literacy and lifelong learning opportunities are also evaluated.
Keywords: Aging; Alternative Learning System (ALS); Blended Learning; Collaboration; Communications technology; Computer science education; Educational institutions; Educational products; Electronic learning; Learning Management System (LMS); Learning systems; Space technology; Technology management; Virtual Learning Environment (VLE); ⛔ No INSPIRE recid found

Psychological impacts of 'screen time' and 'green time' for children and adolescents: A systematic scoping review - Oswald, Tassia K.; Rumbold, Alice R.; Kedzior, Sophie G. E.; Moore, Vivienne M. (PLOS ONE, 2020)
Technological developments in recent decades have increased young people’s engagement with screen-based technologies (screen time), and a reduction in young people’s contact with nature (green time) has been observed concurrently. This combination of high screen time and low green time may affect mental health and well-being. The aim of this systematic scoping review was to collate evidence assessing associations between screen time, green time, and psychological outcomes (including mental health, cognitive functioning, and academic achievement) for young children (<5 years), schoolchildren (5–11 years), early adolescents (12–14 years), and older adolescents (15–18 years). Original quantitative studies were identified in four databases (PubMed, PsycInfo, Scopus, Embase), resulting in 186 eligible studies. A third of included studies were undertaken in Europe and almost as many in the United States. The majority of studies were cross-sectional (62%). In general, high levels of screen time appeared to be associated with unfavourable psychological outcomes while green time appeared to be associated with favourable psychological outcomes. The ways screen time and green time were conceptualised and measured were highly heterogeneous, limiting the ability to synthesise the literature. The preponderance of cross-sectional studies with broadly similar findings, despite heterogeneous exposure measures, suggested results were not artefacts. However, additional high-quality longitudinal studies and randomised controlled trials are needed to make a compelling case for causal relationships. Different developmental stages appeared to shape which exposures and outcomes were salient. Young people from low socioeconomic backgrounds may be disproportionately affected by high screen time and low green time. Future research should distinguish between passive and interactive screen activities, and incidental versus purposive exposure to nature. Few studies considered screen time and green time together, and possible reciprocal psychological effects. However, there is preliminary evidence that green time could buffer consequences of high screen time, therefore nature may be an under-utilised public health resource for youth psychological well-being in a high-tech era.
Keywords: Adolescents; Attention; Children; Cognitive psychology; Mental health and psychiatry; Psychology; Schools; Social psychology

Short screening scales to monitor population prevalances and trends in non-specific psychological distress - Kessler, Ronald; Andrews, Gavin; Colpe, Lisa; Hiripi, E; Mroczek, Daniel; Normand, Sharon-Lise; Walters, Ellen; Zaslavsky, Alan (Psychological Medicine, 2002)
A 10-question screening scale of psychological distress and a six-question short-form scale embedded within the 10-question scale were developed for the redesigned US National Health Interview Survey (NHIS). Initial pilot questions were administered in a US national mail survey (N = 1401). A reduced set of questions was subsequently administered in a US national telephone survey (N = 1574). The 10-question and six-question scales, which we refer to as the K10 and K6, were constructed from the reduced set of questions based on Item Response Theory models. The scales were subsequently validated in a two-stage clinical reappraisal survey (N = 1000 telephone screening interviews in the first stage followed by N = 153 face-to-face clinical interviews in the second stage that oversampled first-stage respondents who screened positive for emotional problems) in a local convenience sample. The second-stage sample was administered the screening scales along with the Structured Clinical Interview for DSM-IV (SCID). The K6 was subsequently included in the 1997 (N = 36116) and 1998 (N = 32440) US National Health Interview Survey, while the K10 was included in the 1997 (N = 10641) Australian National Survey of Mental Health and Well-Being. Both the K10 and K6 have good precision in the 90th-99th percentile range of the population distribution (standard errors of standardized scores in the range 0.20-0.25) as well as consistent psychometric properties across major sociodemographic subsamples. The scales strongly discriminate between community cases and non-cases of DSM-IV/SCID disorders, with areas under the Receiver Operating Characteristic (ROC) curve of 0.87-0.88 for disorders having Global Assessment of Functioning (GAF) scores of 0-70 and 0.95-0.96 for disorders having GAF scores of 0-50. The brevity, strong psychometric properties, and ability to discriminate DSM-IV cases from non-cases make the K10 and K6 attractive for use in general-purpose health surveys. The scales are already being used in annual government health surveys in the US and Canada as well as in the WHO World Mental Health Surveys. Routine inclusion of either the K10 or K6 in clinical studies would create an important, and heretofore missing, crosswalk between community and clinical epidemiology.

Classroom ICT integration in Tanzania: Opportunities and challenges from the perspectives of TPACK and SAMR models - Kihoza, Patrick; Zlotnikova, Irina; Bada, Joseph; Kalegele, Khamisi (International Journal of Education and Development using Information and Communication Technology (IJEDICT), 2016)
With the education systems demand of contemporary technologies, teacher trainees should be imparted with competencies and skills to integrate information and communication technology (ICT) into their future teaching and learning practices. This study assessed classroom ICTs integration opportunities and the challenges in relation to Technological Pedagogical and Content Knowledge (TPACK) and SAMR (Substitute, Augmentation, Modification, and Redefinition) models. The case study involved tutors and teacher trainees (N=206) from teacher training colleges. Results indicated that, majority of respondents have low pedagogical ICT competencies. However, tutors exhibited good knowledge level in all TPACK and SAMR constructs that we assessed, teacher trainees’ revealed poor skills and inefficient support on the use of basic ICTs (hardware, software, and associated peripherals). The impacts of TPACK and SAMR models characteristics related to the technology use planning and redesign of learning tasks was evident. Most of the challenges identified were associated to the lack of infrastructures, readiness to change and lack of competencies on pedagogical ICTs applications. Among others, we recommend the government to work on a harmonized ICT in education integration framework; that consider the existing opportunities and challenges facing Tanzania teacher training systems. Further work should focus on carrying out an experimental research design to unlock the existing ICT use realities.
Keywords: ⛔ No DOI found

Trends in educational research about e-learning: a systematic literature review (2009–2018) - Valverde-Berrocoso, Jesús; Garrido-Arroyo, María del Carmen; Burgos-Videla, Carmen; Morales-Cevallos, María Belén (Sustainability, 2020)
The concept of e-learning is a technology-mediated learning approach of great potential from the educational perspective and it has been one of the main research lines of Educational Technology in the last decades. The aim of the present systematic literature review (SLR) was to identify (a) the research topics; (b) the most relevant theories; (c) the most researched modalities; and (d) the research methodologies used. To this end, the PRISMA protocol was followed, and diﬀerent tools were used for the bibliographic management and text-mining. The literature selection was carried out in three ﬁrst-quartile journals indexed in JCR-SSCI specialized in Educational Technology. A total of 248 articles composed the ﬁnal sample. The analysis of the texts identiﬁed three main nodes: (a) online students; (b) online teachers; and (c) curriculum-interactive learning environments. It was revealed that MOOC was the most researched e-learning modality. The Community of Inquiry and the Technological Acceptance Model, were the most used theories in the analyzed studies. The most frequent methodology was case study. Finally, the conclusions regarding the objectives of our SRL are presented: Main themes and research sub-themes, most researched e-learning modality, most relevant theoretical frameworks on e-learning, and typologies of research methodologies.

School-based professional development in one Lebanese school: how much is too much? - Nabhani, Mona; Bahous, Rima; Hamdan, Zeina (Professional Development in Education, 2012)
This case study examines the attitudes of the secondary and middle school teachers at one school in Lebanon regarding the effect of the school’s professional development (PD) programs on the quality of their teaching practices and motivation. It also examines teachers’ attitudes regarding PD as well as their recommendations to improve the quality of the PD program provided by their school. Questionnaires, focus group interviews and observations were conducted to collect and triangulate data results. Results show that teachers regard PD in their school as beneficial in general but able to be enhanced further. Although the attitude of novice teachers towards PD is more favorable than that of veteran teachers, findings show that the overall teachers’ attitude towards PD is a negative one. Modifications and suggestions to improve the quality of the PD activities are proposed by the teachers. The school offers a prosperous PD program, but its fruitfulness will remain limited unless an organizational structure is created.
Keywords: Lebanon; professional development; schools; ⛔ No DOI found

Multilingual language policy and mother tongue education in Timor-Leste: a multiscalar approach - Caffery, Jo; Coronado, Gabriela; Hodge, Bob (Language Policy, 2016)
This article looks at multilingual, mother-tongue-based language policies influenced by colonial and postcolonial histories and globalization processes. We use multiscalar analysis to show these policies as creative responses to problems affected by national and international forces. Our study focuses on Timor-Leste, specifically a pilot mother-tongue-based multilingual education program. We analyse the program’s practices and successful outcomes, in the adverse circumstances of this small, impoverished, recently independent nation, as it attempts to manage high levels of linguistic diversity (16 mother tongues and a five-language destination system) through multilingual education. We also identify tensions and problems that impinge on the outcomes for this ambitious program. Despite the obstacles, Timor-Leste’s multiscalar multilingual literacy policy is an important case that reinforces the significance of mother tongue education as a response to global complexity. The pilot program provides valuable lessons for many other parts of the world with similar problems, particularly for nations with comparable colonial histories.

A global outlook to the interruption of education due to COVID-19 pandemic: Navigating in a time of uncertainty and crisis - Bozkurt, Aras; Jung, Insung; Xiao, Junhong; Vladimirschi, Viviane; Schuwer, Robert; Egorov, Gennady; Lambert, Sarah; Al-Freih, Maha; Pete, Judith; Don Olcott, Jr; Rodes, Virginia; Aranciaga, Ignacio; et al. (Asian Journal of Distance Education, 2020)
Uncertain times require prompt reflexes to survive and this study is a collaborative reflex to better understand uncertainty and navigate through it. The Coronavirus (Covid-19) pandemic hit hard and interrupted many dimensions of our lives, particularly education. As a response to interruption of education due to the Covid-19 pandemic, this study is a collaborative reaction that narrates the overall view, reflections from the K12 and higher educational landscape, lessons learned and suggestions from a total of 31 countries across the world with a representation of 62.7% of the whole world population. In addition to the value of each case by country, the synthesis of this research suggests that the current practices can be defined as emergency remote education and this practice is different from planned practices such as distance education, online learning or other derivations. Above all, this study points out how social injustice, inequity and the digital divide have been exacerbated during the pandemic and need unique and targeted measures if they are to be addressed. While there are support communities and mechanisms, parents are overburdened between regular daily/professional duties and emerging educational roles, and all parties are experiencing trauma, psychological pressure and anxiety to various degrees, which necessitates a pedagogy of care, affection and empathy. In terms of educational processes, the interruption of education signifies the importance of openness in education and highlights issues that should be taken into consideration such as using alternative assessment and evaluation methods as well as concerns about surveillance, ethics, and data privacy resulting from nearly exclusive dependency on online solutions.
Keywords: COVID-19; Coronavirus Pandemic; Covid-19.; Emergency remote education; distance education; dode_eth-src-dode; dode_eth-trf2-dode; emergency remote education; online learning; ⛔ No DOI found

Broadening borders to build better schools: virtual professional learning communities - Carpenter, Daniel; Munshower, Paul (The International Journal of Educational Management, 2019)
PurposeThe purpose of this paper is to explore how rural teachers provided a PLC by leveraging virtual technologies to connect educators of like subject disciplines from several schools, foreign and domestic.Design/methodology/approachA phenomenological case study-based approach was leveraged to investigate established vPLCs at schools (Creswell, 2013; Stake, 2010). Qualitative data were collected from multiple sources to obtain rural teacher perceptions on the impact vPLCs had on their practice (Creswell, 2013).FindingsTeacher collaborative teams build relationships comparable to teams that met face to face as part of a similar PLC and PD experience. Participant reflections in this investigation showed that rural educators favored face-to-face meetings; however, vPLCs provided similar teacher experiences to that of the face-to-face PBL model. Results indicated that educators recognized virtual collaboration just as valuable a tool for enabling PLCs than face-to-face collaborations while still offering similarities to improved teacher practice.Research limitations/implicationsThe research was limited to teachers in rural settings in the USA (Texas) and in the Dominican Republic. The research was limited to teacher perceptions of change, and observed changes as part of their participation in a research-based virtual PLC model. The research was limited to the school setting over an academic year.Practical implicationsThe findings from this study have practical implications for rural teachers and school implementation of a professional learning community model.Originality/valueThe promise provided by this study is that vPLCs may provide opportunity for rural schools to provide a job-embedded professional development model (Croft et al., 2010) for otherwise isolated teachers (Barrett et al., 2015).
Keywords: Collaboration; Communities of Practice; Computer Mediated Communication; ERIC, Current Index to Journals in Education (CIJE); Education; Educational technology; Faculty Development; Learning; Meetings; Preferences; Professional development; Professional learning communities; Rural Schools; Rural schools; School districts; Teacher Attitudes; Teacher Collaboration; Teacher collaboration; Teachers; Teaching; Virtual professional learning communities; __:import:01; __:match:final; __:matched; __:study_id:2095794; __finaldtb

Human-AI collaboration to identify literature for evidence synthesis - Spillias, Scott; Tuohy, Paris; Andreotta, Matthew; Annand-Jones, Ruby; Boschetti, Fabio; Cvitanovic, Christopher; Duggan, Joe; Fulton, Elizabeth; Karcher, Denis; Paris, Cecile (2023)
Systematic approaches to evidence synthesis can improve the rigour, transparency, and replicability of a traditional literature review. However, these systematic approaches are time and resource intensive. We evaluate the ability of OpenAI’s ChatGPT to undertake two initial stages of evidence syntheses (searching peer-reviewed literature and screening for relevance) and develop a novel collaborative framework to leverage the best of both human and AI intelligence. Using a scoping review of community-based sheries management as a case study, we nd that with substantial prompting, the AI can provide critical insight into the construction and content of a search string. Thereafter, we evaluate ve strategies for synthesising AI output to screen articles based on prede ned inclusion criteria. We nd low omission rates (< 1%) of relevant literature by the AI are achievable, which is comparable to that of human screeners. These ndings show that generalised AI tools can assist reviewers with evidence synthesis to accelerate the implementation and improve the reliability of a review.
Keywords: _Added-ailr-2024

Paradigm Peace and the Implications for Quality - Bryman, Alan (International Journal of Social Research Methodology, 2006)
In this article it is shown that the paradigm wars that raged concerning the incompatibility of quantitative and qualitative research have largely subsided. In the process, discussions of epistemological and ontological issues have become less prominent. The peace that has broken out has proved to be more favourable to research combining quantitative and qualitative research than was the case during the paradigm wars. Drawing on interviews with social researchers who employ a mixed‐methods approach and on the literature, it is shown that a spirit of pragmatism with regard to combining quantitative and qualitative research prevails which encourages researchers to consider using mixed‐methods research when the research question is suited to it. However, the issue of which quality criteria should be employed in investigations combining quantitative and qualitative research has not been given a great deal of consideration. The author argues for a contingency approach, in which issues to do with quality are decided in relation to the nature of the study.

Roles and student identities in online large course forums: Implications for practice - Baxter, Jacqueline Aundree; Haycock, Jo (The International Review of Research in Open and Distributed Learning, 2014)
The use of large online discussion forums within online and distance learning continues to grow. Recent innovations in online learning such as the MOOC (massive open online course) and concomitant growth in the use of online media for the delivery of courses in traditional campus based universities provide both opportunity and challenge for online tutors and learners alike. The recognition of the role that online tutors and student identity plays in the field of retention and progression of distance learners is also well documented in the field of distance learning. Focusing on a course forum linked to a single Level 2 undergraduate module and open to over 1,000 students, this ideographic case study, set in a large distance learning university, uses qualitative methodology to examine the extent to which participation in a large forum can be considered within community of practice (COP) frameworks and contributes to feelings of efficacy, student identity, and motivation. The paper draws on current theory pertaining to online communities and examines this in relation to the extent to which the forum adds to feelings of academic and social integration. The study concludes that although the large forum environment facilitates a certain degree of academic integration and identity there is evidence that it also presents a number of barriers producing negative effects on student motivation and online identity.
Keywords: C: United Kingdom; e-learning; higher education; online forums; online identities; online learning

Usage level and Attitude of The Secondary Level Teachers' in Bangladesh Towards ICT at Personal and Professional Arena - Kashem, Abul; Haque, Ziaul (2014)
Integration of information and communications technologies (ICTs) in education sectors is one of the prime objectives of Bangladesh from the last decade. This study is conducted to assess the level of using ICT and acceptance of new technology by secondary level teachers in Bangladesh in their professional and personal arena. The study revealed that in Bangladesh most of the secondary level teachers use computer and internet for their personal purpose and use computers 35 times in a day. It revealed that secondary level teachers are interested to spend for ICT purpose. It also revealed that there is a difference in ICT usage between male and female teachers but no difference of the same among the different level of the teachers. It was found that there is no difference in case of perception about ICT between male and female teachers but perception among different level of teachers about ICT is different. Unavailability of high speed and wireless connections, lack of computer knowledge, high cost at start-up and unwillingness of aged teachers are found as hindrance for use of ICT in secondary level teaching arena. The success of information and communications technology (ICT) applications in teaching is profoundly dependent on the level of computer use by secondary level teachers. Majority of the Secondary level teacher were interested to accept the new technology for their professional capability enhancement and serve the nation. This questionnaire-based study assessed the level of computer and internet use by Secondary level teacher in Bangladesh is not satisfactory but perception of secondary level teacher for accepting new technology is positive both in their personal and professional arena.
Keywords: ⛔ No DOI found

The specific skills required of teachers who deliver K–12 distance education courses by synchronous videoconference: implications for training and professional development - Rehn, Nicki; Maor, Dorit; McConney, Andrew (Technology, Pedagogy and Education, 2018)
The purpose of this research is to identify the specific skills required of videoconference teachers who teach K–12 distance education courses. Many schools and educational districts worldwide are using videoconference technology to deliver courses to students as an economic solution when they cannot afford specialised teachers at remote locations. However, teachers are rarely trained to use this instructional technology and must therefore translate their experience in face-to-face and/or online teaching to this alternative medium. The collective case study used observations and interviews of eight teachers across five schools to identify the specific skills required to teach in a way that they perceived as successful in a videoconference class. It was found that teachers are largely under-prepared with strategies to project presence, develop relationships, foster interaction, manage the course and teach content across a distance when the screen is the main tool of connection. The authors offer a path to improvement that involves supporting teacher action research, creating communities of inquiry and developing teaching quality standards specific to videoconference.
Keywords: K–12; Videoconferencing; distance education; instructional technology; teacher roles

Teaching game and simulation based probability - Koparan, Timur (International Journal of Assessment Tools in Education, 2019)
Technology and games are the areas where learners are most interested in today's world. If these two can be brought together within the framework of learning objectives, they can be an advantage for teachers and students. This study aims to investigate the learning environment supported by game and simulation. The games were used to evaluate the basic probability knowledge of the prospective teachers, to demonstrate the role of problem solving in the formation of the mathematical knowledge, and to enable discussing mathematical ideas in a worksheet. Simulations were used for visualization and a large number of experiments. The sampling of the study, by which case study research is adopted, is comprised of 40 prospective teachers at a state university in Turkey. The data were collected by introducing nine open-ended questions by means of games, worksheets and simulation activities. The questions asked relevant to the games include making predictions about the fairness of the games, playing the games in small numbers and in big numbers and the observation of the scores, calculation of the winning probabilities of the gamers both experimentally and theoretically, and their comparisons. The process of finding out the probability information underlying the games by the prospective teachers was analyzed qualitatively by means of worksheets, simulations and in-class observation, and the ways of thinking, intuitions, estimations, strategies, and opinions about the learning situation of the participants were tried to be determined. The results obtained put forward that the learning situation that was set up simultaneously contributed to the knowledge of probability and probability teaching of the prospective teachers; and that the candidates' opinions about the learning situation are positive.
Keywords: Computer Simulation; ERIC, Current Index to Journals in Education (CIJE); Educational Environment; Foreign Countries; Higher Education; Instructional Effectiveness; Knowledge Level; Mathematics Skills; Postsecondary Education; Prediction; Preservice Teacher Education; Preservice Teachers; Probability; Problem Solving; Student Attitudes; Turkey; __:import:01; __:match:final; __:matched; __:study_id:2098269; __finaldtb

Systems Implications for Core Instructional Support Lessons from Sobral (Brazil), Puebla (Mexico), and Kenya - Crouch, Luis (Research on Improving Systems of Education (RISE), 2020)
As this note was being written in April and May 2020, the Coronavirus pandemic was sweeping the world. Children were out of school. Researchers around the world are now estimating a severe learning gap due to loss of school attendance. While the first priority is getting children back to school safely, the discussion in this note regarding foundational learning is all the more relevant, as it is this kind of learning that is likely most affected. Key Points The case studies in this document highlight five tips that may be beneficial to other countries or situations: Focus on just a very few achievable indicators, foregrounding foundational learning, for a country emphasising learning. Use data to drive both initial “wake-up” and stock taking but also to support teaching as the process goes along. Emphasis on the teaching by the teachers who are already in place. Provide strong motivation through support that works. Use tight management so there is some degree of centralism and prescriptiveness as to pedagogy and other inputs, but after having iterated and adapted to context.

Applying the information search process model to analyze aspects in the design of serious games for children with hearing impairment - Cano, Sandra; Alghazzawi, Daniyal M.; Arteaga, Jaime Muñoz; Fardoun, Habib M.; Collazos, César A.; Amador, Viviana Bustos (Universal Access in the Information Society, 2018)
Deaf children traditionally face greater challenges and encounter difficulties particular to their abilities. The Information Search Process model (ISP) is oriented in the context of the present work as a process of searching for information about children with a hearing impairment in the area of literacy, applying the different stages of the ISP model to identify different aspects of hearing impairment. A case study was carried out at the USAER school in Aguascalientes, Mexico, a school that enables children with hearing impairments to be included in regular secondary schooling. The children here are aged 12–15 years and have literacy problems. Eight children from 7 to 11 years of age were also evaluated in the Institute for Deaf and Blind Children in Cali, Colombia. The ISP model can be deemed to have been useful for identifying the relevant needs to support both teachers and deaf children. A need was identified, to construct a game that integrates the activities undertaken following the FitzGerald keys and in turn allow them to assess learning through different activities that help increase the semantic repertoire.

Promoting academic literacy with technology: successful laptop programs in K-12 schools - Warschauer, Mark; Grant, David; Real, Gabriel Del; Rousseau, Michele (System, 2004)
One of the main challenges that US schools face in educating English language learners is developing their academic literacy. This paper presents case studies of two K-12 schools that successfully employ high-technology environments, including laptop computers for each student, toward the development of English language learners’ academic language proficiency and academic literacy. In the first school, Latino fourth-grade students use laptops and other new technologies for a wide variety of pre- and post-reading tasks as part of their effort to transition from learning to read to reading to learn. In the second school, diverse immigrant and refugee students at the middle school level combine technology use with Expeditionary Learning to carry out community projects leading to the development of sophisticated products. In both schools, technology is used to engage students in cognitively demanding activity, motivate independent reading, and provide scaffolding for language development, while the researchers also made use of technology to document learning processes and outcomes. Taken together, the schools offer valuable lessons for utilization of technology to promote academic literacy among culturally and linguistically diverse students.
Keywords: Laptops; Literacy; Technology

Online learning and emergency remote teaching: Opportunities and challenges in emergency situations - Ferri, Fernando; Grifoni, Patrizia; Guzzo, Tiziana (Societies, 2020)
The aim of the study is to analyse the opportunities and challenges of emergency remote teaching based on experiences of the COVID-19 emergency. A qualitative research method was undertaken in two steps. In the first step, a thematic analysis of an online discussion forum with international experts from different sectors and countries was carried out. In the second step (an Italian case study), both the data and the statements of opinion leaders from secondary online sources, including web articles, statistical data and legislation, were analysed. The results reveal several technological, pedagogical and social challenges. The technological challenges are mainly related to the unreliability of Internet connections and many students’ lack of necessary electronic devices. The pedagogical challenges are principally associated with teachers’ and learners’ lack of digital skills, the lack of structured content versus the abundance of online resources, learners’ lack of interactivity and motivation and teachers’ lack of social and cognitive presence (the ability to construct meaning through sustained communication within a community of inquiry). The social challenges are mainly related to the lack of human interaction between teachers and students as well as among the latter, the lack of physical spaces at home to receive lessons and the lack of support of parents who are frequently working remotely in the same spaces. Based on the lessons learned from this worldwide emergency, challenges and proposals for action to face these same challenges, which should be and sometimes have been implemented, are provided.
Keywords: emergency remote teaching; online learning; pedagogical challenges; social challenges; technological challenges

Effect of COVID-19 on the performance of grade 12 students: Implications for STEM education - Sintema, Edgar John (Eurasia Journal of Mathematics, Science and Technology Education, 2020)
With all learning institutions pre-maturely closed on 20 March 2020 and all citizens advised to self-isolate in a bid to control the spread of COVID-19, it was hypothesized that COVID-19 would negatively impact on the performance of students in the 2020 Grade 12 national examinations vis-a-vis mathematics, science and design and technology subjects. An observed steady increase in the number of COVID-19 confirmed cases and the low levels of technology use in secondary schools in Zambia due to limited technology resources signifies a very difficult period in a young country which has just rolled out a nation-wide implementation of STEM education, This study collected data from three teachers at a public secondary school in Chipata District of Eastern Province in the Republic of Zambia. The Head of Department for Mathematics, the Head of Natural Sciences Department and one science teacher were interviewed. Semi-structured interviews via mobile phone were used to collect views of what these specialists thought would be the COVID-19 effects on the general performance of students in their subject areas. Results of this study revealed that there is likely to be a drop in the pass percentage of secondary school students in this year's national examinations if the COVID-19 epidemic is not contained in the shortest possible time considering that the school academic calendar was abruptly disturbed by the early untimely closure of all schools in the country.
Keywords: COVID-19; Mathematics education; STEM subjects; Zambia

PNAE (National School Feeding Program) and its events of expansive learnings at municipal level - da Silva, Eliane Alves; Pedrozo, Eugenio Avila; da Silva, Tania Nunes (World, 2022)
The National School Feeding Program (PNAE for its acronym in Portuguese) is one of the largest food policies in the world, partially covering the daily needs of 44 billion students per year. In 2009, Law No. 11,947 established that at least 30% of the total financial transfer of PNAE was used in the purchase of foodstuff directly from family farming in the left-wing government of Lula. In practice, the rules allow public policy managers to choose between bidding or public call, provision by large agribusiness companies or by family farmers, and this is practiced in idiosyncratic ways by 5568 Brazilian municipalities. Each municipality organizes its own system. Therefore, the aim of this article is to analyze how the evolution of Law No. 11,947 promotes expansive learning in the Brazilian National School Feeding Program (NSFP-PNAE), located in the Western Amazon. As a theoretical framework, the Cultural–Historical Activity Theory (CHAT) and the Theory of Expansive Learning (TEL) were used. Qualitative research in an abductive reasoning was carried out, using a single and incorporated case study as its strategy. The study included 21 interviews, later analyzed by Content Analysis. The main contribution is the advance in solutions for societal needs, in terms of continuous collective collaboration, creating expansive learning, transformative or not, in both sides of productive systems and consumption, integrating family farmers and students by a healthy nutrition and feeding in the same system since 2009.
Keywords: NSFP-PNAE; expansive learning; nutritional and feeding program

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 1: Inception Report - Groeneveld, Caspar; Michels, Guillaume; Kaye, Tom (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the first of five reports on the development of a proof of concept for the Hub. It provides a background and overview of the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Toward a Successful Plan for Educational Technology for Low-income Communities: A Formative Evaluation of One Laptop Per Child (OLPC) Projects in Nigeria and Ghana - Ezumah, Bellarmine Anthonia (Howard University, 2010)
Copious educational technology projects have been implemented in several low-income communities by multilateral institutions, individuals, and governmental agencies. Statistics show that the majority of these initiatives fail to accomplish their objectives, thereby wasting colossal amounts of money, talent, and resources. Scholars aver that poor planning and implementation are the major deterrents to a successful technology project (Flagg, 1990; Osin, 1998; Warschauer, 2006). Responding to this problem, the current work seeks to provide a model for an effective plan for introducing educational technology that will yield a better result for elementary education. Using as a case the One Laptop Per Child (OLPC), a computer program initiated by MIT professor Nicholas Negroponte to enhance education in low-income communities, this study specifically evaluates the planning and implementation strategies employed in the OLPC pilot projects in Abuja, Nigeria and Accra, Ghana. A participatory research approach was employed and qualitative data were collected in situ using in-depth interviews and questionnaires with parents, school leaders, students, public educational officials, community leaders, subject-matter experts, and OLPC personnel involved in the OLPC projects at LEA Galadima Primary School, Abuja, Nigeria and Kanda Primary School, Accra, Ghana. The project under study is a Western initiative; thus, the dominant paradigm of development communication theory and its alternative, the participatory action research, were employed as the theoretical framework. Results from the study allowed the researcher to posit a model toward a better plan for educational technology adoption in low-income communities. Some highlights include the need for every country to establish a standardized educational technology objective, ability to raise funds enough to keep it going, the need to incorporate local materials as major content, and acknowledging input of local experts, and the teachers' role in the entire process.
Keywords: Applied sciences; Communication and the arts; Constructivist pedagogy; Education; Educational technology; Formative evaluation; Ghana; Low-income; Nigeria; One Laptop Per Child; ___working_potential_duplicate

What drives successful economic diversification in resource-rich countries? - Lashitew, Addisu A; Ross, Michael L; Werker, Eric (The World Bank Research Observer, 2021)
The “resource curse” is often understood to imply poor growth in the non-resource sectors of the economy, but research into the diversification performance of resource-rich countries is limited. This paper surveys recent evidence and identifies empirical patterns in the economic diversification of resource-rich countries. Diversification is measured using the growth of per capita non-resource (manufacturing and services) sectors in domestic and export markets, which has a cleaner interpretation than competing measures. This measure is used to evaluate the long-term diversification of countries that started off as resource-dependent, and to rank countries according to their performance. We then identify policy-relevant correlates of diversification at the national level, including the acquisition of human capital, public and intellectual capital, and firm dynamism. More resource-dependent countries appear to perform worse on measures of human capital and intellectual capital, but more resource-abundant countries perform better on public capital and human capital accumulation. We examine the mechanisms behind diversification performance through in-depth case studies of Oman, Laos, and Indonesia, and conclude by identifying policy lessons and future research directions.
Keywords: ⛔ No INSPIRE recid found

Decolonisation in Universities: The politics of knowledge - Jansen, Jonathan (Wits University Press, 2019)
Shortly after the giant bronze statue of Cecil John Rhodes came down at the University of Cape Town, student protestors called for the decolonisation of universities. It was a word hardly heard in South Africa’s struggle lexicon and many asked: What exactly is decolonisation? This book brings together some of the most innovative thinking on curriculum theory to address this important question. In the process, several critical questions are raised: Is decolonisation simply a slogan for addressing other pressing concerns on campuses and in society? What is the colonial legacy with respect to curricula and can it be undone? How is the project of curricula decolonisation similar to or different from the quest for post-colonial knowledge, indigenous knowledge or a critical theory of knowledge? What does decolonisation mean in a digital age where relationships between knowledge and power are shifting? Strong conceptual analyses are combined with case studies of attempts to ‘do decolonisation’ in settings as diverse as South Africa, Uganda, Tanzania and Mauritius. This comparative perspective enables reasonable judgments to be made about the prospects for institutional take-up within the curriculum of century-old universities. Decolonisation in Universities is essential reading for undergraduate teaching, postgraduate research and advanced scholarship in the field of curriculum studies.Shortly after the giant bronze statue of Cecil John Rhodes came down at the University of Cape Town, student protestors called for the decolonisation of universities. It was a word hardly heard in South Africa’s struggle lexicon and many asked: What exactly is decolonisation? This edited volume brings together the most innovative thinking on curriculum theory to address this important question. In the process, several critical questions are raised: Is decolonisation simply a slogan for addressing other pressing concerns on campuses and in society? What is the colonial legacy with respect to curriculum and can it be undone? How is the project of curriculum decolonisation similar to or different from the quest for postcolonial knowledge, indigenous knowledge or a critical theory of knowledge? What does decolonisation mean in a digital age where relationships between knowledge and power are shifting? The book combines strong conceptual analyses with novel case studies of attempts to ‘do decolonisation’ in settings as diverse as South Africa, Uganda, Tanzania and Mauritius. Such a comparative perspective enables reasonable judgements to be made about the prospects for institutional take-up within the curriculum of century-old universities.

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Viewpoints to ICT practices and hindrances from in Tanzanian secondary schools and teacher training colleges: Focus on classroom teachers - Muhoza, O. U.; Tedre, M.; Aghaee, N.; Hansson, H. (2014 International Conference on Teaching and Learning in Computing and Engineering, 2014)
On the policy level, Tanzania has strongly committed to Information and Communication Technology (ICT) supported education on all levels of education. National policy documents give ICT a high priority in development of the country's educational system. Curricula have been revamped to accommodate for increased role of ICT in the society and education. Also educational institutions have explicated high expectations of ICT in the process of "massification of education." Several research studies, however, have showed little change in the classrooms. Surveys and case studies have showed that on the way from policy documents to strategy level and implementation level, something gets missing. The lack of ICT in education is clear in primary and secondary school, which is unsurprising, given that majority of schools also lack electricity and basic facilities, including proper classrooms, tables, and books. This study sets out to investigate, using thematic interviews of secondary school teachers in Tanzania, what processes and support structures do teachers consider to be lacking in terms of ICT supported education. Informants from teacher training colleges were also involved in order to bring out viewpoints from teacher training. The results confirmed a large number of earlier results, divided to six categories: school policy, implementation and administration on the school level, access to ICT, leadership and management, school culture, and teacher training. A number of new factors were also pinpointed: teachers' lack of awareness of government policies and documentation on several levels, lack of pedagogical readiness for e-learning and blended learning, and cultural concerns. Concerning what should come first, there was a chicken-and-egg-problem: it makes little sense to invest in rapidly aging ICT infrastructure and facilities if there is no human capacity to make use of those investments, and it makes little sense to invest in human capacity if there is no technological infrastructure to put quickly aging technical know-how into immediate use.
Keywords: Classroom Activities; Computers; Culture; Educational Technology; Educational institutions; Government; ICT management; ICT supported education; Information and Communication Technology (ICT); Internet; Interviews; Tanzania; Tanzanian secondary schools; Teacher education; Teachers' expectations; Teachers' experiences; Training; blended learning; classroom teachers; computer aided instruction; cultural concerns; e-learning; educational courses; educational curricula; educational institutions; educational system development; government policies; information and communication technology; information technology; national policy documents; pedagogical readiness; teacher training; teacher training colleges

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Investing in disaster preparedness and effective recovery of school physical infrastructure - Opabola, Eyitayo A.; Galasso, Carmine; Rossetto, Tiziana; Meilianda, Ella; Idris, Yunita; Nurdin, Sukiman (International Journal of Disaster Risk Reduction, 2023)
The importance of functioning education infrastructure for the post-disaster recovery of communities is well-acknowledged. Yet, recent natural-hazard events worldwide have highlighted that school facilities still face many post-disaster recovery-impeding challenges. A significant investment in resilience enhancement through appropriate disaster preparedness and post-disaster recovery management is needed to tackle such global challenges. This paper summarises a series of stakeholder engagements (through interviews and focus group discussions) aimed at providing evidence-based recommendations to foster a more rapid and effective post-disaster recovery of school physical infrastructure in disaster-prone marginalised communities. The case-study community is in Central Sulawesi, Indonesia – a region still recovering from the 2018 Central Sulawesi earthquake, tsunami, and liquefaction, which caused damage to over 1200 schools. The considered stakeholders have significant experience in post-disaster recovery management in Central Sulawesi. This paper identifies early-response funding mechanisms, genuine collaborations between stakeholders, and improved capacity for self-organisation as critical elements for an inclusive, sustainable, safer, and more resilient school physical infrastructure. Although the discussion in this paper focuses on Central Sulawesi, the project's outcomes are scalable to other regions in Indonesia, South-East Asia, and other disaster-prone developing nations.
Keywords: Disaster risk reduction; Preparedness; Resilient recovery; School physical infrastructure; Stakeholder engagement

Thematic Analysis: Striving to Meet the Trustworthiness Criteria - Nowell, Lorelli S.; Norris, Jill M.; White, Deborah E.; Moules, Nancy J. (International Journal of Qualitative Methods, 2017)
As qualitative research becomes increasingly recognized and valued, it is imperative that it is conducted in a rigorous and methodical manner to yield meaningful and useful results. To be accepted as trustworthy, qualitative researchers must demonstrate that data analysis has been conducted in a precise, consistent, and exhaustive manner through recording, systematizing, and disclosing the methods of analysis with enough detail to enable the reader to determine whether the process is credible. Although there are numerous examples of how to conduct qualitative research, few sophisticated tools are available to researchers for conducting a rigorous and relevant thematic analysis. The purpose of this article is to guide researchers using thematic analysis as a research method. We offer personal insights and practical examples, while exploring issues of rigor and trustworthiness. The process of conducting a thematic analysis is illustrated through the presentation of an auditable decision trail, guiding interpreting and representing textual data. We detail our step-by-step approach to exploring the effectiveness of strategic clinical networks in Alberta, Canada, in our mixed methods case study. This article contributes a purposeful approach to thematic analysis in order to systematize and increase the traceability and verification of the analysis.

Responding to the COVID-19 pandemic in Trinidad and Tobago: Challenges and opportunities for teacher education - Kalloo, Rowena Constance; Mitchell, Beular; Kamalodeen, Vimala Judy (Journal of Education for Teaching, 2020)
Trinidad and Tobago responded decisively to the COVID 19 pandemic and was successful in containing community spread of the virus. By mid-march 2020, there was closure of key business and educational institutions. To minimise the loss of learning time, emergency remote learning became the modus-operandi, a response which challenged the most socially vulnerable students. At the University of the West Indies (UWI) the 500 participants enrolled in the Early Childhood, and Primary education programmes, and the in-service post-graduate diploma in Secondary education were struggling to adjust to online teaching, the existential anxiety of coping with a dangerous disease, and programme completion. The UWI instituted a COVID-19 policy that facilitated a structured response to programme completion and assessment across all faculties.The paper analysed the decisions taken by the UWI School of Education that supported its teachers through the practicum and pedagogy courses. Using a qualitative case study methodology, data were collected through observations, documents, and informal discussions with faculty. Thematic analyses allowed the emergence of three key constructs that facilitated effective learning during the crisis period : Community as an empathetic connection to stakeholders, Creativity as the ability for agile and imaginative responses, and Connectivity through technological readiness.
Keywords: COVID-19; Teacher education; inequities; online education

Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

Leaving no-one behind: Improving climate change and entrepreneurship education in sub-Saharan Africa through E-learning and innovative governance systems - Chirambo, Dumisani (Climate Literacy and Innovations in Climate Change Education: Distance Learning for Sustainable Development, 2018)
Poverty and climate change vulnerability is increasing in Sub-Saharan Africa (SSA) because the region lacks education and skills development facilities, and sustainable governance systems. Arguably, mainstreaming climate literacy in secondary schools through Information and Communications Technology (ICT) modalities can promote sustainable development and climate change resilience by providing early opportunities for the youth to gain knowledge and awareness of the behavioral and cultural changes that may foster improved climate change resilience. Through an inductive analysis based on research articles, case studies, policy briefs, and academic literature reviews, this chapter sought to highlight emerging ICT learning contexts in SSA as a means to determine the extent to which ICT may be used to promote climate change and sustainable development education in secondary schools. The chapter showed that climate literacy at secondary schools was being constrained by a lack of climate change education material and content on existing ICT learning platforms; and a lack of innovative governance systems to support governments in delivering climate literacy content to secondary schools and the youth. Consequently, to “leave no-one behind” requires non-state actors to develop and utilise innovative governance systems and digital climate literacy material that can complement government efforts to mainstream climate literacy at secondary schools.

Pakistan Landscape Analysis Inception Report: UNICEF Inception Report - EdTech Hub Team (EdTech Hub, 2022)
Based on the growing access to technology, and the lessons learned from the experiences during the Covid-19 school closures, the Ministry of Federal Education and Professional Training (MoEFPT) has identified the formalisation of a strategy to develop and implement technology-based learning approaches as an immediate national priority. UNICEF Pakistan is developing a strategy to guide its engagement in the technology-facilitated learning space in Pakistan. This strategy will identify how both low- and high-tech learning modalities can be scaled to improve access to and the quality of learning for all Pakistan’s children and adolescents, including the most marginalised. This strategy will be underpinned by a rigorous review of the technology-enhanced learning landscape in Pakistan. EdTech Hub has supported governments and development partners globally to research, design, implement, and evaluate EdTech-related programmes to support education service delivery both during school closures and since reopenings have commenced. EdTech Hub will support UNICEF to undertake the aforementioned landscape review, focused specifically on EdTech tools that are being used for student learning in Pakistan. EdTech Hub will then collaborate with UNICEF to develop a strategy for UNICEF’s engagement in the technology-facilitated learning arena. This inception report sets out the scope of work for this partnership. The remainder of the report contains the following sections. Keywords:marginalised learners; EdTech tools; Pakistan; UNICEF; inception report; MoFEPT An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Exploring the backgrounds and shaping of beginning student teachers in Ghana: toward greater contextualisation of teacher education - Akyeampong, Kwame; Stephens, David (International Journal of Educational Development, 2002)
Teacher education programmes are often quite similar in their framework and content but often lack sufficient reflection on the personal background and the socio-political forces that shape teachers’ roles and identity within the systems in which they operate. This paper explores this issue by using Ghana as a case study and discusses implications for its teacher education programmes and policies. Key characteristics of beginning student teachers found were: weak qualifying grades in two fundamental school subjects, mathematics and English, a waiting period of 2–5 years prior to entering teachers’ college, and apparently sharp differentials in trainees’ socio-economic background as compared to typical Ghanaian communities. They come to training with rich and varied images of teachers, teaching and the profession, but, in addition, many beginning trainees also express little desire to teach at primary school level, mainly for reasons of status and insufficient fringe benefits. These factors, we argue, should be taken into more account in the design of college programmes and the development of teacher education policies. The paper concludes with a call to teacher education systems, especially in Africa, to look more closely at, and learn from, who comes for training, what they bring with them, and how they perceive themselves in relation to teaching, training and future aspirations.
Keywords: Beginning student teachers; Ghana; Teacher education; Teacher identity; Teacher images

Timor-Leste education: Supporting sustainable system-wide reform and school leader capacity-building through collaborative foreign aid - Owen, Susanne; Wong, Debbie (Journal of Educational Change, 2021)
Effective school leadership and ongoing teacher capacity-building are essential aspects of school reform and improving educational outcomes for students in developing countries. This paper examines a Timor-Leste curriculum reform and associated school leader capacity-building and the implementation processes for building sustainability, within the context of research literature regarding effective professional development and successful foreign aid principles. The Timor-Leste leadership program was developed using an interpretivist paradigm and action research, with the authors being program designers and managers embedded in the context. School leader interviews and surveys, meeting notes and monitoring and evaluation reports, also teacher skills and student achievement data, were continuously examined to analyse issues and plan actions and solutions. Findings outline early impacts in relation to changing school leader behaviours, improved teacher skills and increased student literacy and numeracy, while also presenting implementation processes and actions taken to overcome challenges in relation to research-informed foreign aid principles.Given the importance of foreign aid for supporting significant educational improvement in developing countries, this Timor-Leste leadership capacity-building case study provides an example relevant to an under-researched area. While the focus is on one particular country and reform involving curriculum and professional development, the paper has value for other education contexts and system change initiatives which involve collaborations with foreign aid donors.
Keywords: Foreign aid; International development; School leadership capacity-building; School reform; School-based professional development; ⛔ No INSPIRE recid found

Snapshots of student-teachers' experiences of DVDs in a learner support programme in a developing ODL context - Kok, Illasha; Blignaut, A. Seugnet (Africa Education Review, 2014)
The School of Continuing Teacher Education (SCTE) in South Africa delivers an Advanced Certificate in Education (ACE) Learner Support Programme to Open Distance Learning (ODL) students in Namibia, a developing sub-Saharan African country. This paper examines the experiences of student-teachers using DVDs included in the tutorial package. Fifteen participants from rural and remote areas of Namibia took part in a semi-structured focus group and individual interviews. A first phase analysis identified a set of codes and categories that guided the researchers to two themes to using DVDs: frustration and attitude. Student-teachers' frustration and attitude towards DVDs are linked to sufficient appropriate information, also available as a paper-based tutorial package. Although electronic learning material can assist in achieving curriculum goals and enrich students' learning experiences, students' expectations are paramount in the design and development of instructional DVDs.
Keywords: Adult Education; Case Studies; College Students; Computer Uses in Education; Continuing Education; Developing Nations; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Electronic Learning; Focus Groups; Foreign Countries; Higher Education; Inservice Teacher Education; Namibia; Open Education; Postsecondary Education; Qualitative Research; Semi Structured Interviews; South Africa; Student Attitudes; Student Experience; Teachers; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096343; __finaldtb

Snapshots of student-teachers' experiences of DVDs in a learner support programme in a developing ODL context - Kok, Illasha; Blignaut, A. Seugnet (Africa Education Review, 2014)
The School of Continuing Teacher Education (SCTE) in South Africa delivers an Advanced Certificate in Education (ACE) Learner Support Programme to Open Distance Learning (ODL) students in Namibia, a developing sub-Saharan African country. This paper examines the experiences of student-teachers using DVDs included in the tutorial package. Fifteen participants from rural and remote areas of Namibia took part in a semi-structured focus group and individual interviews. A first phase analysis identified a set of codes and categories that guided the researchers to two themes to using DVDs: frustration and attitude. Student-teachers' frustration and attitude towards DVDs are linked to sufficient appropriate information, also available as a paper-based tutorial package. Although electronic learning material can assist in achieving curriculum goals and enrich students' learning experiences, students' expectations are paramount in the design and development of instructional DVDs.
Keywords: Adult Education; Case Studies; College Students; Computer Uses in Education; Continuing Education; Developing Nations; Distance Education; ERIC, Current Index to Journals in Education (CIJE); Electronic Learning; Focus Groups; Foreign Countries; Higher Education; Inservice Teacher Education; Namibia; Open Education; Postsecondary Education; Qualitative Research; Semi Structured Interviews; South Africa; Student Attitudes; Student Experience; Teachers; Video Technology; __:import:01; __:match:final; __:matched; __:study_id:2096343; __finaldtb

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 2: Insights from user research - Rahman, Asad; Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the second of five reports on the development of a proof of concept for the Hub. It provides a summary of user research undertaken for the project. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest. Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Cost-Effective EdTech Paper 2: Good practice - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Investigating Thai teachers attitudes toward students with autism - Little, Cathy; Vibulpatanavong, Kanokporn; Evans, David (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2014)
Greater numbers of students with Autism are being educated in mainstream settings, enrolled in regular classes, placed with ‘regular’ students, and with teachers who often have limited experience or knowledge about their specific disability. Teachers, with limited knowledge of disability, struggle to successfully include these students into their classes. However, a powerful predictor of successful inclusion of students with a disability into mainstream classrooms is the attitude of the general education teacher (Ainscow, 2007). A plethora of research abounds to empirically support what is known about quality teaching practice for students with Autism, yet this same research highlights teachers concerns of lack of knowledge, lack of support systems and overriding legislative policy as primary obstacles to the inclusion process. Research suggests that teachers of students with Autism have limited knowledge about the specific traits and idiosyncrasies that define these students learning styles and behaviours.This research investigated the attitudes of Thai teachers toward their students with Autism. Attitudes were defined by four constructs: attitude toward inclusion, teacher effectiveness, academic climate, and social inclusion. A key premise of this research was that positive teacher attitude was strongly related to more successful outcomes for students. This research utilised a mixed methods design over two phases, using both survey data and qualitative case studies. The following paper reports only on phase one of the research, the responses to the Teacher Attitudes Survey. Participants of the study were 404 teachers from seven schools in Bangkok. Results showed an ongoing need to assist teachers in building their confidence and knowledge in catering for students with Autism in the regular classroom. Teacher confidence (effectiveness) in meeting the education needs of students with Autism was reported as limited, yet teachers reported their understanding about the social inclusion of students with Autism in the regular school setting to be positive. Keywords : Attitudes, Autism, Education, Inclusion, Social Inclusio
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

“Thinking Outside the Camp”: Education Solutions for Syrian Refugees in Jordan - Baeyer, Sarah Lebaron Von (Ethnographic Praxis in Industry Conference Proceedings, 2017)
This paper presents a case study of a project on education solutions for Syrian refugees in Jordan conducted between 2015–2017. First, it describes how ReD's methodological approach provided a unique perspective to studies on refugees. By immersing a team in the day-to-day lives and settings that most Syrian refugees experience in Jordan—i.e., outside of camps and in people's actual homes—ReD led its client to “think outside the camp,” something that relief agencies and companies often fail to do due to the refugee camp model of humanitarian assistance that, ever since WWII, has dominated the approach to refugees. Second, as a result of its unique methodological approach, ReD uncovered important findings about social networks and technology use and access in Syrian refugees’ homes and communities that ultimately shaped the client's perspective on solution development. For example, ReD's team of ethnographers found that nearly all out-of-camp Syrian households had at least one Smartphone in their possession, if not two or more, and that digital devices served as important tools of communication and community-building among people displaced by conflict. Consequently, ReD advised its client to tap into these pre-existing social networks and mobile technologies in order to develop an education solution that best fit refugees’ “real-life” practices. Ultimately, both ReD's methods and its findings led to a significant impact in how the client strategized on and developed their education solution, and can serve as a broader model for how to approach building services and/or products for displaced populations with access to basic mobile technologies. “The Jordanian educational/policy response to refugees is broken and will not easily be fixed or tinkered with. Solutions must work around this system.” (Education expert and activist working with vulnerable youth and school dropouts in Jordan)
Keywords: Google Scholar/ refugee education technology; RER theme_durable solutions

Parents’ New Role and Needs During the COVID-19 Educational Emergency - Rousoulioti, Thomais; Tsagari, Dina; Giannikas, Christina Nicole (Interchange, 2022)
This article contributes to the on-going discussion of parental involvement in the education of children, with emphasis on new and unfamiliar roles of parents during the COVID-19 pandemic. The case study undertaken focuses on parents of first graders who belong to non-vulnerable and vulnerable social groups, and the first-grade teachers of a public primary school in the north of Greece. Research questions address the experience of ‘parents–teachers’, the need for technological tools and the required digital literacy, as well as the impact of homeschooling on the wellbeing of the family unit. Data were collected using semi-structured individual interviews. The data analysis shows that parents of both social groups took on the role of the teacher to accommodate the learning challenges of first graders. Mothers from vulnerable groups, in particular, encountered various challenges when attempting to support their children mainly in language lessons. Regarding the use of new technologies, the pandemic found parents of both groups unprepared and unfamiliar with the process of distance education. Stress and worry were the dominant emotions from the very start of homeschooling during the early stages of the pandemic while towards the end of the first lockdown, exhaustion overwhelmed parents and pupils. The article concludes with emphasizing the importance of active parental involvement and coaching that enables parents to contribute substantially to their children’s education in emergency situations.

Investigating educational change: The Aga Khan University Institute for educational development teacher education for school improvement model - Khamis, Anil; Sammons, Pamela (International Journal of Educational Development, 2007)
This article continues the analyses of the impact of an innovative teacher education programme aimed at school improvement in a developing country context (A. Khamis, P. Sammons, 2004. The development of a cadre of teacher educators: some lessons from Pakistan. International Journal of Educational Development, 24(3), 255–268). Building on recent publications that have analysed outcomes of the teacher education programme and how the cadre of teacher educators has worked to initiate improvement in schools in Pakistan. The article considers the ‘teacher education for school improvement model’ based on findings from the case studies of nine co-operating school. Lessons are presented to further inform the development of teacher education programmes and the measurement of effectiveness of such programmes in developing country contexts. The article further considers relevant international research on educational change and reform to draw further lessons. These lessons include the need to pay greater attention to the cultural contexts and milieu in Pakistan, and the need to create models of school improvement and teacher education that originate within developing country contexts rather than the adaptation of European/North American models that are based on sources of data in those contexts. The article concludes by arguing for the need to develop better theoretical understandings from the current innovations underway and placing the onus on intervening agencies to better inform educational change strategies promoted in developing country contexts.
Keywords: Developing countries; Educational change; Innovation; Pakistan; School improvement; Teacher education

A Global Mapping of Delivery Approaches - Mansoor, Zahra; Qarout, Dana; Anderson, Kate; Carano, Celeste; Dvorakova, Veronika; Williams, Martin J (2021)
The past 25 years has seen numerous governments worldwide adopting new institutional forms, such as delivery units and reform labs, to try to improve service delivery. We conduct a systematic global search and mapping of these delivery approaches. We identify 152 instances of delivery approach (DA) adoption from 80 diﬀerent countries, ranging from the center of government down to provincial and local levels, with an accelerating trend of adoption since 2010. The majority of these include education as a focus sector. The main ﬁnding that emerges from our analysis is that there is no single model that characterizes the design of such approaches or the purposes for which they are adopted. However, we do identify a number of patterns, including that DAs in lower-income countries are more likely to focus mainly on output-type goals (as opposed to outcomes), use external consultants, and utilize accountability- and incentive-driven mechanisms relatively more heavily than their counterparts in middle- and high-income countries. While our ﬁndings are purely descriptive and cannot be used to infer whether DAs are eﬀective, they give an indication to policymakers about the menu of potential options available to them in designing DAs. This global mapping can also provide useful context for existing and future country-level case studies that investigate the eﬀectiveness of DAs and seek to explore which designs might be more eﬀective in diﬀerent contexts and for diﬀerent purposes.
Keywords: ⛔ No DOI found

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Learning Inequality During the Covid-19 Pandemic - Engzell, Per; Frey, Arun; Verhagen, Mark D. (SocArXiv, 2020)
Suspension of face-to-face instruction in schools during the COVID-19 pandemic has led to concerns about consequences for student learning. So far, data to study this question have been limited. Here we evaluate the effect of school closures on primary school performance using exceptionally rich data from the Netherlands (n≈350,000). The Netherlands represents a best-case scenario with a relatively short lockdown (8 weeks) and a high degree of technological preparedness. We use the fact that national exams took place before and after lockdown, and compare progress during this period to the same period in the three previous years using a difference-in-differences design. Our results reveal a learning loss of about 3 percentile points or 0.08 standard deviations. These results remain robust when balancing on the estimated propensity of treatment and using maximum entropy weights, or with fixed-effects specifications that compare students within the same school and family. Losses are up to 55% larger among students from less-educated homes. Investigating mechanisms, we find that most of the effect reflects the cumulative impact of knowledge learned rather than transitory influences on the day of testing. The average learning loss is equivalent to a fifth of a school year, nearly exactly the same period that schools remained closed. These results imply that students made little or no progress whilst learning from home, and suggest much larger losses in countries less prepared for remote learning.
Keywords: Economics; Education; Educational Assessment; Evaluation; Public Affairs; Public Policy and Public Administration; Social Statistics; Social and Behavioral Sciences; Sociology; and Research

Decentralisation policy and practice in Ghana: the promise and reality of community participation in education in rural communities - Essuman, Ato; Akyeampong, Kwame (Journal of Education Policy, 2011)
In 1987, the government of Ghana embarked on a process to decentralise education management to districts as part of wider social and democratic governance reforms. A central part of this reform was the prescription of active community participation in the affairs of schools within their locality. This paper explores the different meanings community participation had for school community stakeholders. It examines the multiple understandings of how community and school relations work and the factors which influence this relationship. Drawing on case study data, it argues that much of the theoretical and policy expectations on representation and participation in education by community members are only evident in form, but not as intended in practice. In poor rural contexts, it is often the local elite and relatively more educated members of the community, who become the new brokers of decision-making and, through their actions, close up the spaces for representation and participation by community members in the affairs of schools. Furthermore, the extent of community participation appears to be shaped by a ‘social contract’ based on the principle of reciprocity of roles between the community and schools, and that increasingly teachers feel accountable to the traditional hierarchical educational structure, and not to the community. The paper argues that the realisation of decentralisation policy in education has to contend with the realities of local politics of influence in the community, and tap into the positive side of this influence to improve education service delivery.
Keywords: Ghana; Parent Teacher Associations (PTA); School Management Committees (SMC); ___working_potential_duplicate; community participation; decentralisation policy

Social distancing meet social media: Digital tools for connecting students, teachers, and citizens in an emergency - Greenhow, Christine; Chapman, Amy (Information and Learning Science, 2020)
Purpose: In a public health crisis where social distancing, or physical distancing while in public spaces, is the new normal, social media offer respite from being alone. Recent statistics show spikes in social media usage worldwide during the Covid-19 pandemic. More than just easing loneliness, such freely available digital tools offer affordances for education in an emergency. Design/methodology/approach: This paper summarizes insights from literature reviews of over a decade of research and recent case studies on the benefits of teaching with social media in K-12 education. Findings: The authors highlight three affordances of social media for fostering active learning, community building and civic participation and describe how social media can be used in conjunction with conventional learning management systems. Furthermore, the authors argue that the unprecedented health crisis that is faced today requires the participation of responsible citizens of all ages; K-12 public education is on the front lines of preparing informed and active citizens and the integration of social media as part of remote education plans can help. Practical implications: The paper includes instructional guidelines for K-12 teachers and instructional designers in various settings who seek to integrate social media as part of their strategy for teaching students at a distance and facilitating their civic participation. Originality/value: This paper fulfills an identified need for evidence-based and pragmatic approaches to K-12 online teaching and learning using technologies already widely in use (i.e. social media).
Keywords: Active learning; COVID-19 pandemic; Civic participation; Community building; Distance education; K-12 education; Social media

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Effect of Covid-19 Pandemic on the Education System in Kenya - Kathula, Domeniter Naomi (Journal of Education, 2020)
Education is an integral part of human society, its importance in life cannot be ignored as lack of education gives birth to numerous social problems like poor health, internal conflict, poor living standards and many more, education helps people to find a better solution to their problems. Education lets people realize the true value of contribution and help become the backbone of the society. Innovation and creativity can only occur when people are skilled enough to know how to operate with different technologies. Since the first case of the novel coronavirus (COVID-19) was announced in Kenya, many aspects of society and the education sector have been dramatically affected. On March 15th 2020, the Kenyan government closed all learning institutions countrywide to contain the spread of the virus. As the numbers of those infected by coronavirus rose to over 8,000, the ministry of education announced on July 7th that, the 2020 school calendar year will be considered lost due to COVID-19 restrictions. The purpose of this study was therefore to determine the effect of Covid-19 pandemic on the education systems in Kenya. The study was anchored on Classical Liberal Theory of Equal Opportunities. Mixed method design which involved a combination of both quantitative and qualitative approaches was adopted. In?quantitative the study used a survey research design, specifically the study adopted a cross-sectional survey research design. Cross-sectional survey design involves collecting data from a large group of people of different stages of growth at one point in time. The target population for this study included teachers, students and parents. The sample size for the study comprised of 100 teachers, 25 parents and 100 students who were purposively selected across the country. This study used both questionnaire and interview guide to collect primary data. The questionnaires were served to teachers and students online using Google forms while interview guide was administered to the parents using online Google forms as well. The quantitative data collected was analyzed using SPSS. Quantitative analysis involved the use of descriptive analysis, while qualitative data was analyzed using content analysis. The results were presented on tables. The findings revealed that Covid-19 had seriously affected learning among students in Kenya. The study found that the effects of Covid-19 were so severe that some teachers and parents lost their jobs or source of livelihoods. Most of the students were not able to access online learning due to lack of electricity, lack of learning materials and some were forced to relocate to the country side. The study hence concluded that as a result of the challenges presented by the coronavirus and the likely impact of future pandemics the government’s ability to ensure continuation of learning will depend on the ability to swiftly harness available technology, provide adequate infrastructure and mobilize stakeholders to prepare alternative learning programmes. The study concludes that as a result of the emergence of Covid-19 pandemic, teaching and learning activities in all learning institutions in Kenya just like other parts of the world have severely been disrupted. The worst hit learners are the primary and secondary school candidates who should sit for their national examinations at the end of 2020. Based on the conclusion the study recommended that there is need for the government through the ministry of education together with all the stakeholders in education sector in Kenya to navigate through challenges presented by Covid-19 to ensure continued access to provision of quality, equitable and inclusive education during and after the pandemic. Effective implementation of the proposed interventions by education managers and stakeholders will ensure uninterrupted learning in educational institutions in future. This study in addition recommends that it is important to ensure that the Ministry of Education, parents and teachers support vulnerable students to ensure they are not exploited and that no learning loss occurs even as schools delay re-full opening until January 2021 despite grades 4, class 8 and form 4s being back in schools already. Keywords: Covid-19, Pandemic, Education system, Students, teachers, Parents, Kenya.
Keywords: Covid-19; Education system; Kenya; Pandemic; Parents; Students; teachers; ⛔ No DOI found

Designing Teacher Learning Circles for Improved Foundational Numeracy Outcomes: Findings from the National Numeracy Programme in Malawi - Correa de Oliveira, André; Plaut, Daniel; Kanyoza, Charity; Boilo, Violet; Chidothi, Emmanuel; Kadzamira, Esme; Mpoola, Dorothy; McBurnie, Chris; Phiri, Magret; Haßler, Björn (EdTech Hub, 2024)
The Malawi National Numeracy Programme (NNP) was designed in 2020 in partnership with the Malawi Ministry of Education and Cambridge Education (Mott McDonald), funded by the UK Foreign, Commonwealth and Development Office (FCDO). Building on findings from a prior qualitative review of the NNP's programme components, EdTech Hub proposed a new phase of design-based implementation research (DBIR) to be undertaken in Term 2 of the 2022–2023 school year to refine the school-based teacher continuous professional development (TCPD) model of the NNP. As part of the research, EdTech Hub developed a new TLC guide to be tested in schools. Through observations, focus group discussions, and interviews, the Hub gathered teacher feedback and used it to co-design and iterate on this guide alongside teachers. This report summarises the principal findings from the study. It also outlines the research background, methodology, findings, and recommendations for the programme moving forward. Keywords: teacher continuous professional development, teacher learning circles, National Numeracy Programme (NNP), Malawi, design-based implementation research An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Combining school-catchment area models with geostatistical models for analysing school survey data from low-resource settings: Inferential benefits and limitations - Macharia, Peter M.; Ray, Nicolas; Gitonga, Caroline W.; Snow, Robert W.; Giorgi, Emanuele (Spatial Statistics, 2022)
School-based sampling has been used to inform targeted responses for malaria and neglected tropical diseases. Standard geostatistical methods for mapping disease prevalence use the school location to model spatial correlation, which is questionable since exposure to the disease is more likely to occur in the residential location. In this paper, we propose to overcome the limitations of standard geostatistical methods by introducing a modelling framework that accounts for the uncertainty in the location of the residence of the students. By using cost distance and cost allocation models to define spatial accessibility and in absence of any information on the travel mode of students to school, we consider three school catchment area models that assume walking only, walking and bicycling and, walking and motorized transport. We illustrate the use of this approach using two case studies of malaria in Kenya and compare it with the standard approach that uses the school locations to build geostatistical models. We argue that the proposed modelling framework presents several inferential benefits, such as the ability to combine data from multiple surveys some of which may also record the residence location, and to deal with ecological bias when estimating the effects of malaria risk factors. However, our results show that invalid assumptions on the modes of travel to school can worsen the predictive performance of geostatistical models. Future research in this area should focus on collecting information on the modes of transportation to school which can then be used to better parametrize the catchment area models.
Keywords: Catchment area models; Disease mapping; Missing locations; Model-based geostatistics; Prevalence; School survey

Between Social Justice and Decolonisation: Exploring South African MOOC Designers’ Conceptualisations and Approaches to Addressing Injustices - Adam, Taskeen (Journal of Interactive Media in Education, 2020)
As social justice and decolonisation discussions fill the physical and virtual corridors of universities in South Africa, educators, and in this case, MOOC designers, are inevitably influenced by them. They are prompted to reflect on such topics, whether in agreement or with scepticism. Provoked by one interviewee’s comment that ‘you could decolonise and still have an enormous amount of injustice’, this paper investigates how South African MOOC designers conceptualise (in)justice, and how they attempt to address these injustices in and through their MOOCs. As notions such as ‘social justice’ and ‘decolonisation’ have multiple meanings and connotations, a framework was created to unpack the ‘Dimensions of Human Injustice’ namely, material, cultural-epistemic, and political/geopolitical injustices. These dimensions of injustice were used to analyse semi-structured interviews with 27 South African MOOC designers. MOOC designers who stressed cultural-epistemic injustices, focused on relevance, inclusive processes and the geopolitics of knowledge production. Those who stressed material injustices, focused on socio-economic disparities, infrastructural inequalities and the need to tackle these systemic problems at a societal level. Through illustrating that MOOC designers attempt to address injustices based on their different conceptualisations of (in)justice, this study argues that a multi-pronged approach to tackling the various dimensions of injustice perpetuated in and through MOOCs can lead to more holistic justice-oriented MOOCs that better enable learners. Additionally, justice-oriented efforts by South African MOOC designers, highlighted in this paper, can be seen as a guide for the MOOC space in general to take greater strides in creating MOOCs in more justice-oriented ways.
Keywords: MOOC designers; cultural-epistemic injustice; decolonisation; dode_eth-src-dode; dode_eth-trf2-dode; geopolitical injustice; material injustice; social justice

Blended and Hybrid Learning Initiatives: A curated list for El Salvador - Villavicencio, Xuzel; Coflan, Caitlin Moss (EdTech Hub, 2022)
This document was produced in response to a request from the UNICEF country office and Ministry of Education team of El Salvador that was submitted to the EdTech Hub Helpdesk in November 2021. The UNICEF team requested a curated list of global blended and hybrid initiatives with a focus on initiatives that have used a multimodal strategy, highlighting effective and ineffective practices. This report does not aim to cover every leading and innovative blended / hybrid initiative with relevance to the Salvadoran context. Rather, it presents a list of curated resources with examples of challenges, lessons learned, and teacher training approaches that can be used as a guide when designing a multimodal strategy for the education sector. Keywords: hybrid; blended; El Salvador; multimodal; teacher training; remote learning An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

A Framework to Democratise the Design of Educational Games on Social Issues during Game Jams - Myers, Christina (The Open University, 2021)
Game Jams are events organised to create computer games, usually taking place during weekends. These events have become a popular way to enable participants to experience processes and practices of game development as well as to offer multidisciplinary learning opportunities, accessed through the variety of skills involved in game design. However, these events tend to be attended predominantly by male game developers and present barriers to participation for more diverse groups. This thesis investigates how to support diverse group participation in Game Jams, including people from different ethnicities, genders, ages, sexual orientations and who do not have any prior experience of designing games; and explores Game Jam participation as an opportunity to discuss social issues. To this end, a framework to democratise the design of educational games on social issues in Game Jams is proposed. The framework consists of a process with structured resources and activities to enhance learning by supporting egalitarian participation and agency. It offers collaborative learning opportunities for groups to engage with a social issue, relying on storytelling and on the exchange of perspectives and experiences. It also provides support and access to research-based principles to design games for education, and egalitarian opportunities to acquire game development skills, considered relevant opportunities given the wide-spread use of games and increasing interest in games as engaging tools for online education. The development of the framework is grounded in Critical Pedagogy, an educational approach providing principles and processes to democratise learning initiatives based on egalitarian participation and agency. Following a Design-Based Research methodology, the framework is developed through a case study on creating educational games on everyday sexism. A set of formative design studies are undertaken to co-design resources and activities that enable participants to elaborate solutions to the social issue and create educational games themselves. An evaluative study is then presented with the realisation of two Game Jams to assess and validate the proposed framework. The theoretical contributions of this work validate two new applications of Critical Pedagogy. The first one is to apply Critical Pedagogy to shape Game Jams to enhance learning through the active involvement of participants as equal learners and agents of social change. The second one applies Critical Pedagogy to democratise knowledge of design principles to create educational games on social issues. Lastly, access to a co-created tool for raising awareness of everyday sexism and insights on how to enable broad audiences to acquire games development skills are some of the practical contributions of this thesis.

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, E.; Laurillard, D. (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.

The potential of MOOCs for large-scale teacher professional development in contexts of mass displacement - Kennedy, Eileen; Laurillard, Diana (London Review of Education, 2019)
The mass displacement of people across the world, currently estimated at 65 million, creates a massive demand for new forms of education for children, young people and adults. However, this cannot be addressed without attending to what this means for teachers and other professionals involved in education and training. Clearly, there is a need for large-scale teacher professional development (TPD). Digital technology has the potential to meet this demand, but challenges are presented by the poor digital infrastructure in contexts of mass displacement. Data from two projects are analysed to explore the viability of scaling up TPD in the form of co-designed massive open online courses (MOOCs). The first data set is from a co-designed TPD MOOC project Blended Learning Essentials, to show that digital technology can be effective for scaling up TPD, but that a sustainability plan must be in place from the outset. The second data set is from a project that built on the first to run stakeholder co-design workshops in Lebanon, as a way of developing large-scale TPD in this most challenging context. Lebanon has the highest proportion of refugee to host communities in the world. This case study indicates that MOOCs could be viable in such a context, but also highlights the need to balance the generic principles being offered with a focus on localized practice. A theory of change is presented to outline a method of meeting these challenges by employing a co-design methodology to create self-sustaining digital TPD in the context of Lebanon, and to test this model with the contexts of mass displacement experienced by other participants in the MOOC.
Keywords: BLENDED learning; CO DESIGN MOOCS REFUGEES TEACHERS THEORY OF CHANGE; DIGITAL technology; Design; Digital technology; Education; Google Scholar/ "blended learning" refugee education; Lebanon; MASSIVE open online courses; MOOCs; Online instruction; PROFESSIONAL education; Professional development; RER theme_supporting educators; TEACHER development; __:import:01; __:match:final; __:matched; __:study_id:2095772; ___working_potential_duplicate; __finaldtb; co-design; refugees; teachers; theory of change

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

Using learning design as a framework for supporting the design and reuse of OER - Conole, Gráinne; Weller, Martin (Journal of Interactive Media in Education, 2008)
The paper will argue that adopting a learning design methodology may provide a vehicle for enabling better design and reuse of Open Educational Resources (OERs). It will describe a learning design methodology, which is being developed and implemented at the Open University in the UK. The aim is to develop a 'pick and mix' learning design toolbox of different resources and tools to help designers/teachers make informed decisions about creating new or adapting existing learning activities. The methodology is applicable for designers/teachers designing in a traditional context – such as creation of materials as part of a formal curriculum, but also has value for those wanting to create OERs or adapt and repurpose existing OERs. With the increasing range of OERs now available through initiatives as part of the Open Courseware movement, we believe that methodologies, such as the one we describe in this paper, which can help guide reuse and adaptation will become increasingly important and arguably are an important aspect of ensuring longer term sustainability and uptake of OERs. Our approach adopts an empirically based approach to understanding and representing the design process. This includes a range of evaluation studies (capturing of case studies, interviews with designers/teachers, in-depth course evaluation and focus groups/workshops), which are helping to develop our understanding of how designers/teachers go about creating new learning activities. Alongside this we are collating an extensive set of tools and resources to support the design process, as well as developing a new Learning Design tool that helps teachers articulate and represent their design ideas. The paper will describe how we have adapted a mind mapping and argumentation tool, Compendium, for this purpose and how it is being used to help designers and teachers create and share learning activities. It will consider how initial evaluation of the use of the tool for learning design has been positive; users report that the tool is easy to use and helps them organise and articulate their learning designs. Importantly the tool also enables them to share and discuss their thinking about the design process. However it is also clear that visualising the design process is only one aspect of design, which is complex and multi-faceted. Editors: Alexandra Okada (Open University, UK). Reviewers: Teresa Conolly (Open University, UK), Rose Luckin (Institute of Education, UK), and Alexandra Okada (Open University, UK)
Keywords: IMS learning design; Learning Design; e-learning; mind mapping

High-quality education for better sustainability and resiliency - Prazian, Michael V; Prykhodko, Viktoria M (IOP Conference Series: Earth and Environmental Science, 2023)
The world meets poly crises in climate, pandemic, energy, food, human rights, and migration; hot and cold wars have come in Europe and other regions. The scope of the tasks becomes unprecedented, and their complexity demands high-level skill sets and teaching culture. Education moves into epicentres of the fight for better sustainability and resilience. The United National Sustainable Development Goals Four (SDG4) supposes allocating and diligently using several trillion US dollars for the next decades. The ambitious goals drive the educational system to be at a decent level regarding outcome and process. Saving gratitude to functions of a fundamental human right, a public good, gender equality, and an absolute right to education for all, the author urges that high-quality education is the priority because it will help society to cope with a new level of challenges and even existential threats the climate-like. The article describes the methodology and the importance of soft-hard skills for teaching and learning. The secondary-based sources research illustrates practical results regarding the educational process. The Triple Bottom Line principle (Planet, Profit, People) encompasses many disciplines engaging the main aspects of sustainability and resiliency and climate change for the university curricula in a coherent way. The article considers future trends in high education and case studies connected with the European Green Deal, environmental, social, and governance (ESG) reporting and practical aspects of Green Growth and De-Growth Theory. The Quality of Education reflects the regulator’s requirements and social and personal expectations. Life-long learning becomes a norm. The authors consider university products, processes and platforms through the lens of future trends, threats and opportunities. In times of turbulence, the results obtained through students’ upskilling and reskilling programs should fit the demands of new jobs, technologies, and financial mechanisms.

EdTech for Ugandan girls: Affordances of different technologies for girls' secondary education during the Covid-19 pandemic - Damani, Kalifa; Daltry, Rebecca; Jordan, Katy; Hills, Libby; Evans, Laura (Development Policy Review, 2022)
Motivation This article discusses the use of educational technology (EdTech) in girls' education at PEAS (Promoting Education in African Schools) schools in rural Uganda during the Covid-19-related school closures. Purpose This article addresses a research gap surrounding the potential use of EdTech to support girls' education, focusing on the barriers to girls' EdTech use and how technology might be used to enhance girls' education in disadvantaged rural areas—specifically their academic learning and their social and emotional learning. Methods and approach A sequential, explanatory mixed-methods case-study approach was used. Quantitative exploration of a dataset of 483 Ugandan students, from 28 PEAS schools, was first conducted, followed by interviews with PEAS staff to elucidate the reasons and context behind the findings. Findings Findings show that female students are less likely than male students to have access to their caregivers' phones for learning. The form of EdTech that appeared to be most beneficial for girls' academic learning was radio; girls also had significantly more interest in tuning into radio broadcasts than boys did. Also, poorer boys were more likely to be influenced by SMS messages than wealthier boys. Apart from gender-based differences, students with more highly educated parents found SMS messages more helpful, and phone calls from teachers appeared to help boost younger students' self-confidence. Policy implications The findings suggest that policy-makers need to: carefully consider provision of education through multiple modes of EdTech in order to ensure that it reaches all students; ensure that caregivers are involved in the strategies developed for girls' education; make EdTech interventions interactive; and consider language in EdTech interventions. Given the gender differences which emerged, the findings are of relevance both to supporting the continuation of educational provision during periods of school closure, and also in terms of finding additional ways to support girls' education alongside formal schooling.
Keywords: Covid-19; EdTech; education; gender; rural Uganda

“Being on the wrong side of the digital divide”: seeking technological interventions for education in Northeast Nigeria - Martens, Marianne; Hajibayova, Lala; Campana, Kathleen; Rinnert, Gretchen Caldwell; Caniglia, Joanne; Bakori, Isa Garba; Kamiyama, Tsukuru; Mohammed, Liman Audu; Mupinga, Davison M.; Oh, Olivia Jeonghwa (Aslib Journal of Information Management, 2020)
Purpose This paper aims to report the initial findings of a project aiming to re-establish basic education in conflict-ravaged states in Northeastern Nigeria and to improve education providers' ability to plan and deliver basic educational services. The authors present a preliminary analysis of Nigerian teachers' access to information communication technology (ICT), their technology skills, as well associated national ICT policies. Design/methodology/approach This case study uses results from two co-designed tools, administered using KoboToolbox to Education Managers in the first instance, and teachers in the second. The data from the tools form the basis for analysis. Findings In the first instance, educational managers reported a lack of access to technology, the internet and to training and professional development. In the second instance, teachers reported issues present in the classroom environment, including poor infrastructure, a lack of resources and over-crowded classrooms. Very few teachers had access to computers or to the internet. Research limitations/implications The 33 educational managers represent a small sample size and may not be fully representative of the region covered. The ICT Capacity Audit tool listed Excel in two different areas – basic Excel skills and using Excel for data analysis – which could have caused confusion for participants. The data collection should be repeated, expanded and compared for consistency. For the team, changes to the proposed (SENSE) box content meant that we were not able to deliver low-tech tools, such as Boogie Boards, or high-tech tools, such as tablets, to schools. Originality/value Despite seemingly insurmountable challenges, the research team identified low-tech tools as a feasible resource in the classroom. Existing tools, such as teachers' smartphones and use of the WhatsApp application, can be used for sharing educational resources and providing teacher training. This paper argues that Nigeria needs up-to-date national ICT policies to guide in-country efforts to develop implementation of information technology initiatives for education.

Unlocking data to tell the story of education in Africa: webinar summary & synthesis - Adam, Taskeen; Agyapong, Samuel; Asare, Samuel; Heady, Lucy; Wairimu, Wacharia; Mjomba, Renaldah; Mugo, John; Mukiria, Faith; Munday, Gemma (Zenodo, 2020)
[No description available.]
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Higher education reforms: Latin America in comparative perspective - Bernasconi, Andrés; Celis, Sergio (Education Policy Analysis Archives, 2017)
This article introduces a special issue of EPAA/AAPE devoted to recent higher education reforms in Latin America. The last two decades have seen much policy development in higher education in the region, examined and discussed by scholars in each country, but dialog with the international literature on higher education reform, or an explicit comparative focus, have been mostly absent from these works. By way of presentation of the papers included in this issue, we first provide an overview of major policy changes in higher education in the Latin American region since the 1990s. We then turn to the six works in this special issue to describe the theories and methods supporting them. Next, we illustrate how general analytic categories can be derived from single or multi country case studies to illuminate themes capable of cutting across the particulars of national contexts, with their unique traditions, policy paths, and politics. Our three common threads are, first, the types of drivers for reform, that is, how policy change originates, either bottom-up from the institutions, or top-down from the government, and various possibilities in between. Second, understanding challenges to institutional autonomy in a continuum of intensity of state intended intervention in higher education. Third, explaining different levels of strain between public and private sectors in higher education based on conditions of competition for economic resources. While the papers in this special issue do not cover all countries, nor all issues on which policy has been crafted in the last two decades across the region, the collection of articles herein account for topics of enduring importance: faculty work in Ecuador, financial aid in Colombia, public policy decentralization in Argentina, quality assurance models in Colombia and Uruguay, the emerge of new institutions and universities in Argentina and Uruguay, and social justice, access, and inclusion in higher education, in Argentina, Bolivia, Brazil, Chile, Colombia, and Ecuador. The articles presented in this special issue provide much insight onto higher education policy in Latin America and, additionally, offer ample opportunity to develop social science knowledge on the basis of strong comparative work.
Keywords: Change in universities

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Universal Design for Learning: Is It for Everyone? - Rose, D; Meyer, A (2006)
Universal Design for Learning (UDL) stands at the forefront of contemporary efforts to create universal access to educational curricula for all students, including those with disabilities. The "universal" in UDL does not mean there is a single optimal solution for everyone. Instead, it underscores the need for flexible approaches to teaching and learning that meet the needs of different kinds of learners. In this first UDL Reader, Anne Meyer and David H. Rose, cofounders of CAST, the educational nonprofit that developed the UDL framework, bring together a collection of articles on the practical, classroom dimensions of the UDL revolution in education. The authors offer insights on learner differences, the capacities of new media in the classroom, and effective teaching and assessment practices. The volume also includes lessons from teacher professional development workshops, classroom-based research, and UDL practitioners themselves. A highly readable volume aimed particularly at school teachers and administrators, this book is also an uncommonly accessible introduction to UDL for all readers committed to creating improved and universal access to educational materials for all students. Following a preface (Anne Meyer and David H. Rose), this book contains the following chapters: (1) Applying Universal Design for Learning in the Classroom (Peggy Coyne, Patricia Ganley, Tracey Hall, Grace Meo, Elizabeth Murray, and David Gordon); (2) A UDL Case Story and Model Lesson: Reading Challenges in Geography and Social Studies (The Staff at CAST); (3) Frequent Questions about Universal Design for Learning (Grace Meo); (4) A Level Playing Field: UDL in the Classroom (Lani Harac); (5) Teacher Perspectives: UDL in the Elementary Classroom (Kirsten Lee Howard); (6) Teacher Perspectives: Strategy Instruction Goes Digital (Nicole Strangman); (7) Implications of Universal Design for Learning for Classroom Assessment (David H. Rose and Robert P. Dolan); (8) The Promise of New Learning Environments for Students with Disabilities (Bart Pisha and Skip Stahl); (9) Transforming the Textbook to Improve Learning (Skip Stahl); (10) Engaging the Text: Brain Research and the Universal Design of Reading Strategy Supports (David H. Rose and Bridget Dalton); and (11) Teaching Internet Literacy Strategies: The Hero Inquiry Project (Maya B. Eagleton, Kathleen Guinee, and Karen Langlais). An index is also included.

What does the research suggest is best practice in pedagogy for remote teaching? - McAleavy, Tony; Gorgen, Kristine (2020)
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)

“Matching Person & Technology (MPT) Model” for Technology Selection as Well as Determination of Usability and Benefit from Use - Martinez, A. P.; Scherer, M. J. (Living in the State of Stuck, 2018)
Technologies have become smarter, smaller, more portable or wearable, and more adaptable. This has led to more choice and, in many cases, complexity in decision-making about selecting the best device and features for a given user. A good match of person and technology requires attention to (a) aspects of and resources in the environments in which the technology will be used, (b) the needs, expectations and preferences of the user, and (c) the functions and features of the technology and service delivery process. If the match is not a quality one from the standpoint of the end user, and the user experience (UX) is not satisfactory, then the technology may go unused, or may not be used optimally. There is a need for an improved person-AT matching and outcomes assessment process because studies and reports show in general that there is a high level of dissatisfaction and nonuse or discard of technology by consumers. Psychologists are uniquely qualified to partner with technology developers in implementing an assessment process that inquires into the potential technology user's predisposition to use a particular technology by addressing, subjective view of current capabilities, view of achievements as well as needs in key life domains of activities and participation, and ratings of fundamental personal factors such as mood status, support from others, engagement in therapy activities and desire to use technology. Utilization of the MPT model and accompanying assessment process has been proven to result in enhanced technology use and goal achievement. Research increasingly highlights the fact that consumers are less likely to use recommended devices when their needs are neither fully addressed nor understood during the technology selection process. A user's perspective of their needs and preferences may be obtained by having them identify and prioritize their desired outcomes and then rate progress in achieving them. This approach was used in developing the Matching Person and Technology measures and has also been used in developing Such a person-centered approach allows outcomes to be measured in reference to changes in a person's satisfaction in achieving desired goals, not merely their functional ability to achieve them. An idiographic evaluation is used (i.e., the person is the unit of analysis and serves as his or her own control), not a normative one (i.e., the person is compared to his or her peers). An idiographic evaluation best captures a consumer-directed and social model perspective of outcomes assessment. Many studies have examined the psychometric qualities and usefulness of the Matching Person and Technology measures. Below is the most recent data on one MPT measure, the Assistive Technology Device Predisposition Assessment (ATD PA), from a study done in the country Greece (Koumpouros et al. 2017; n=115).  Excellent interrater reliability (ICC=0.981, ranging from 0.973-0.987)  Adequate internal consistency (Cronbach's alpha =0.701, ranging from 0.605-0.701)  Adequate-Excellent construct validity for items in the Adaptablility subscale (r=0.537 to 0.783)  Excellent construct validity for items in the Fit to Use subscale (r= 0.691 to 0.801)  Adequate-Excellent construct validity for items in the Socializing (r= 0.498 to 0.767)  Low correlation coefficients between each subscale, indicating subscales measure unique constructs Improvements in person-centered assistive technology services and outcomes assessment are needed, given reports of a high level of dissatisfaction and nonuse of technology by consumers. It is important to ensure an evidence-based, client-centered assessment for determining the match of individuals with the most appropriate technologies for their use. Achieving a desired outcome begins at the point of technology consideration and then progresses to product selection. ABSTRACT Cognitive impairment often results in a range of functional and lifestyle changes for many individuals. This article discusses the development and evolution of a multidisciplinary model of cognitive rehabilitation outpatient practice that integrates technology to improve patient outcomes. The described interdisciplinary treatment approach highlights the need for collaboration by treating providers; focuses on the individual being an active participant in treatment; and discusses the value that assistive technology can bring to cognitive rehabilitation work as it relates to patient success, functional improvement, and implementation of appropriate and patient specific technological strategies.

Bandarban Sandbox: Needs assessment and hypothesis development - Tanweer, Rabia; Nashtaran, Trishia; Plaut, Daniel; Rahman, Asad; Ahmed, Shakil; Chowdhury, Dilruba; Rabbi, BM Fazley; Hoque, Rashedul; Nahar, Nurun; Afroze, Sadia (EdTech Hub, 2022)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners, working closely with the government and EdTech Hub to identify how EdTech can best be harnessed to support learning in Bangladesh. This partnership uses the sandbox approach — which provides a space for partners to test and grow ideas in conditions of uncertainty — to test how EdTech modalities that aim to improve numeracy outcomes for Grade 6 learners (early secondary) in Bandarban, one of the most remote areas of Bangladesh, can be used most effectively by learners and educators. This report outlines the process and findings from the needs assessment and hypothesis development phase. These findings (as well as the data collection which informs them) are organised around five research questions developed by EdTech Hub in partnership with Agami Education Foundation, the implementing agency for the sandbox. The findings of the research were distributed in themes that outlined the availability and utilisation of technology and a valid level of knowledge and interest in teachers and students towards using technology for education. While some findings shed light on the technical aspects of the context, some human factors also played a role in resisting the acceptance of technology in education. Building on the learning from this needs assessment phase, Agami Education Foundation and EdTech Hub have agreed to test this implementation plan in the upcoming staggered deployment phase. Keywords: EdTech; sandbox; numeracy; Bandarban; Bangladesh; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Cost-Effective EdTech Paper 1: A position piece on how the sector can make progress - Mitchell, Joel; D'Rozario, Jonny (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

MEWAKA National Teacher Development Reform in Tanzania: Design-Based Implementation Research: Cycle 1 Findings - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, G.; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fred; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2024)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teacher Continuous Professional Development [TCPD]) is a landmark, school-based teacher professional development programme being implemented nationally by the Government of Tanzania, with the ultimate aim of raising learning outcomes in schools. EdTech Hub, Aga Khan University, and the Tanzania Institute of Education (TIE) are conducting research to iteratively enhance the MEWAKA implementation at primary school level and to understand the role that technology can play in scaling TCPD. This report presents the findings and recommendations from the first cycle of design-based implementation research (DBIR) conducted in rural schools in the Lindi region. Following a pilot peer facilitator workshop, data was collected through observation and self-reporting methods between September and December 2022. The aims were to capture stakeholders' perspectives at all levels of the education system and to see how schools are implementing the programme on the ground. The emerging findings and recommendations are being used to inform the redesign and further implementation of this TCPD model, and were used to identify key areas to test and investigate in the second cycle of the DBIR in 2023. Keywords: teacher professional development; design-based implementation research; Tanzania; primary education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Child-directed Tablet-based Learning: Project Launch, Monitoring, and Improvement Toolkit - Imagine Worldwide (2020)

Malaysia – Empowering teachers to deliver blended learning after school reopening - UNICEF (2020)

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)

Child-directed Tablet-based Learning: Project Preparation Toolkit - Imagine Worldwide (2020)

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

School leadership and early grade reading: Examining the evidence in Zambia - Rakusin, M; Bostock (Cultivating Dynamic Educators: Case Studies in Teacher Behavior Change in Africa and Asia. RTI Press Publication BK-0022-1809., 2018)

Mapeo y análisis de programas EdTech en América Latina y el Caribe - Myers, Christina; Wyss, Natalie; Villavicencio Peralta, Xuzel; Coflan, Caitlin (EdTech Hub, 2022)
Este documento se elaboró ​​en respuesta a una solicitud de la Oficina Regional de UNICEF para América Latina y el Caribe al Servicio de Asistencia de EdTech Hub en octubre de 2021. El equipo de UNICEF solicitó una lista seleccionada de programas de EdTech en la región de América Latina y el Caribe (ALC) y un análisis de un conjunto de programas preseleccionados con la intención de explorar su potencial para la implementación y el impacto a escala. Este informe no pretende cubrir todos los programas EdTech innovadores en la región de ALC. Más bien, presenta una lista de programas EdTech prometedores y analiza su diseño e implementación con el fin de explorar su relevancia y potencial para lograr un impacto a gran escala. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen